Lithium-ion battery with cross-linked separator

JP7626549B2Active Publication Date: 2025-02-14ASAHI KASEI BATTERY SEPARATOR CORP
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
JP2021140057
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-07-31
Filing Date
2021-08-30
Publication Date
2025-02-14
Estimated Expiration
2039-10-11

AI Technical Summary

Benefits of technology

【0024】 本発明によれば、蓄電デバイス用セパレータの低温シャットダウン機能と高温耐破性を両立させて、その製造プロセスにおいて未溶融樹脂凝集物の発生も抑制して生産性及び経済性に寄与することができ、さらに良好なサイクル特性と高い安全性を有する蓄電デバイスとその組み立てキットを提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626549000095
    Figure 0007626549000095
  • Figure 0007626549000096
    Figure 0007626549000096
  • Figure 0007626549000097
    Figure 0007626549000097
Patent Text Reader

Abstract

To provide: a separator for an electricity storage device that can exhibit both a shutdown function and high-temperature puncture resistance, while ensuring electricity storage device safety, output and / or cycle stability; and a novel crosslinking method suitable for its production process, and an assembly kit or production method for the electricity storage device.SOLUTION: The present invention provides: a separator for an electricity storage device comprising a silane-modified polyolefin, where silane crosslinking reaction of the silane-modified polyolefin is initiated when it contacts an electrolyte solution; and a method for producing the separator.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a separator for an electricity storage device and a crosslinking method thereof, an electricity storage device assembly kit, a manufacturing method for an electricity storage device, and the like. [Background technology]

[0002] Microporous membranes are widely used as separation or permselective separation membranes for various substances, separators, etc., and examples of their applications include precision filtration membranes, separators for fuel cells and capacitors, base materials for functional membranes in which functional materials are filled into the pores to exhibit new functions, separators for electricity storage devices, etc. Among these, polyolefin microporous membranes are suitably used as separators for lithium ion batteries, which are widely used in notebook personal computers, mobile phones, digital cameras, etc.

[0003] In order to ensure the safety of a battery, the separator is required to achieve both the activation of a shutdown function and an improvement in the film rupture temperature. For example, Patent Document 1 describes that the high-order physical properties of polyolefin resin, which is an essential component of a separator for a lithium-ion battery, have been adjusted. In addition, as shown in Patent Document 2, it is known that in a specific crystallinity and gel fraction range, the shutdown function suppresses heat generation due to a short circuit inside the battery, while the battery has a performance that does not rupture even if a high-temperature portion occurs partially in the battery cell (breakdown at 170°C or higher), thereby ensuring the safety of the battery. In more detail, Patent Documents 1 and 2 have been experimentally shown to be able to exhibit high-temperature film rupture properties by constructing a silane crosslinking portion (gelation structure) in a polyolefin separator.

[0004] For example, Patent Documents 1 to 6 describe a silane crosslinked structure formed by contacting a silane-modified polyolefin-containing separator with water. Patent Document 8 describes a crosslinked structure formed by ring-opening of norbornene by irradiation with ultraviolet light, electron beams, etc. Patent Document 9 describes that the insulating layer of a separator has a (meth)acrylic acid copolymer having a crosslinked structure, a styrene-butadiene rubber binder, etc. Also, for example, a separator has been proposed in which the thickness ratio between layer A having a shutdown property and layer B containing an aramid resin and an inorganic material is adjusted within a predetermined range (see Patent Document 11).

[0005] The components used in lithium-ion batteries include positive and negative electrode materials, electrolytes, and separators. Of these components, the separator is required to be inert to electrochemical reactions or surrounding components due to its insulating properties. On the other hand, for the negative electrode material of lithium-ion batteries, a technology has been established since the beginning of their development to suppress the decomposition of the electrolyte on the surface of the negative electrode by forming a solid electrolyte interface (SEI) through a chemical reaction during the first charge (Non-Patent Document 1). Even if polyolefin resin is used for the separator, an oxidation reaction is induced on the positive electrode surface under high voltage, and cases of blackening of the separator and surface deterioration have been reported.

[0006] Based on the above idea, polyolefin microporous membranes have been widely developed and put to practical use as materials for separators for power storage devices, in order to adopt a chemical structure that is inactive against electrochemical reactions or other chemical reactions. However, as long as polyolefin is used as the resin, there is a limit to the performance improvement even if the mechanical microporous structure of the separator is improved. For example, the heat resistance stability of the separator above the melting point of polyolefin or the electronegativity of the olefin unit makes the affinity or liquid retention with the electrolyte insufficient, and therefore the permeability of Li ions or their solvated ion clusters through the separator is not satisfactory.

[0007] Thus, due to the above limitations, it is not expected that current approaches will be able to satisfy the high-speed charge / discharge or heat resistance stability required in modern battery development. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 9-216964 [Patent Document 2] WO 97 / 44839 [Patent Document 3] Japanese Patent Application Publication No. 11-144700 [Patent Document 4] Japanese Patent Application Publication No. 11-172036 [Patent Document 5] JP 2001-176484 A [Patent Document 6] JP 2000-319441 A [Patent Document 7] JP 2017-203145 A [Patent Document 8] JP 2011-071128 A [Patent Document 9] JP 2014-056843 A [Patent Document 10] Japanese Patent Application Publication No. 10-261435 [Patent Document 11] JP 2007-299612 A [Patent Document 12] International Publication No. 2010 / 134585 [Patent Document 13] JP 2016-072150 A [Non-patent literature]

[0009] [Non-Patent Document 1] Lithium-ion Secondary Battery (2nd Edition) Published by Nikkan Kogyo Shimbun [Non-Patent Document 2] Basic Polymer Chemistry, Tokyo Kagaku Dojin Summary of the Invention [Problem to be solved by the invention]

[0010] In recent years, the output and energy density of lithium-ion secondary batteries for use in mobile devices or vehicles have been increasing, while miniaturization of battery cells and stable cycle charge / discharge performance during long-term use are being demanded. For this reason, separators that are thin (e.g., 15 μm or less) and of high quality (e.g., having uniform physical properties and no resin aggregates) are required. Furthermore, the standard of battery safety has become stricter than before, and as described in Patent Documents 1 and 2, shutdown function and high-temperature film rupture property are required, and the development of a separator resin composition and a manufacturing method that enable stable production is expected. In this regard, the shutdown temperature level is preferably lower than 150° C., and the film rupture temperature level is preferably higher.

[0011] For example, in the method described in Patent Document 3, a crosslinking catalyst master batch is used during the extrusion process to promote the crosslinking reaction of silane-modified polyethylene in an extruder, but resin aggregates are also generated, which reduces the uniformity of the separator's physical properties. In contrast to this method, the methods described in Patent Documents 4, 5, and 6 take measures by providing a plasticizer extraction process or a silane gel crosslinking process, controlling the gel fraction of the resin film, or passing the uncrosslinked resin through hot water to form it and then dehydrating it. In addition, Patent Document 7 proposes providing a heat-resistant resin microporous film with low heat shrinkage, low fluidity, and excellent meltdown resistance by adjusting the gel fraction of the polyolefin microporous film, the storage modulus at temperatures of 40°C to 250°C in dynamic viscoelasticity (DMA) measurement, the maximum shrinkage rate by thermomechanical analysis (TMA), and the amount of radicals measured by electron spin resonance (ESR).

[0012] Furthermore, with regard to separators for power storage devices, from the viewpoints of dimensional stability, maintaining the shutdown function while improving the membrane rupture temperature, and dimensional stability, it has been proposed to dispose an inorganic porous layer containing inorganic particles such as calcined kaolin or boehmite and a resin binder on at least one surface of a polyolefin microporous membrane (Patent Documents 12 and 13).

[0013] However, the method shown in Patent Document 4 does not allow the silane crosslinking reaction to proceed sufficiently, making it difficult to obtain high-temperature film rupture resistance. In the plasticizer extraction process described in Patent Documents 3 and 4, a tin (II)-based crosslinking catalyst is used, which allows the crosslinking reaction to proceed, but there is a concern that the crosslinking catalyst will remain afterwards.

[0014] The heat-resistant resin microporous film described in Patent Document 7 is obtained by simply applying a photopolymerizable coating liquid to a film that has been made porous by a dry method. In addition, in Example 5 of Patent Document 7, a low molecular weight silane coupling agent such as γ-methacryloxypropyltrimethoxysilane is added to the porous film, but if a low molecular weight silane coupling agent is used in a wet porosity method, it is expected that the low molecular weight silane coupling agent will not bond with the resin of the porous film because it is likely to react or bond with the plasticizer used for porosity. Furthermore, a battery having a heat-resistant resin microporous film as described in Patent Document 7 as a separator has poor cycle characteristics, and during long-term use, it induces unexpected side reactions in the battery, which may lead to a decrease in battery safety.

[0015] In addition, the coating layer described in Patent Document 7 is formed by a crosslinking reaction caused by an external stimulus after a compound having a polymerizable functional group is applied to a resin porous membrane, so that it is expected that liquid will penetrate into a part of the resin porous membrane at the same time as the coating layer is applied, and after the crosslinking reaction progresses, a mixed region is also expected to be formed near the interface between the coating layer and the resin porous membrane. As a result, good TMA heat shrinkage performance is obtained, but it is expected that the battery cycle characteristics will be reduced due to clogging of the resin porous membrane or that the fuse (shutdown) performance will be reduced due to the melting phenomenon of the resin porous membrane. Furthermore, a small amount of radical species compound is detected by ESR in the composite microporous membrane obtained by the method described in Patent Document 7, and since it remains, when the composite microporous membrane is incorporated into a battery, a radical reaction will progress with other components, particularly with the electrolyte, and a chain reaction that decomposes the electrolyte is predicted, which is thought to significantly deteriorate the battery performance.

[0016] Furthermore, the microporous membranes and separators described in Patent Documents 1, 2, and 7 are not well studied with respect to disposing an inorganic porous layer containing inorganic particles and a resin binder on their surfaces. Conventional separators having an inorganic porous layer on a microporous membrane appear to have an improved membrane rupture temperature on the temperature-resistance curve of an electricity storage device. However, in reality, the resin may dissolve from the microporous membrane into the inorganic porous layer, so that the membrane of the separator as a whole is expected to be reduced and the stress resistance is thereby reduced. Therefore, although the multilayer porous membranes described in Patent Documents 12 and 13 have a polyolefin microporous membrane and an inorganic porous layer, there is room for study on the compatibility of low-temperature shutdown function and high-temperature membrane rupture property as a separator for an electricity storage device, or improvement of cycle characteristics and nail puncture safety of the battery of the electricity storage device.

[0017] Furthermore, batteries using separators such as those described in Patent Documents 3 to 7 have poor cycle characteristics, and when used for a long period of time, unexpected side reactions are induced in the battery, raising concerns about a decrease in battery safety.

[0018] In general molded products such as hot water pipes, tin (Sn)-based catalysts are added to the extruder during the extrusion process. On the other hand, the wet manufacturing process of separators for power storage devices usually includes steps such as extrusion / sheet molding, stretching, plasticizer extraction (porosity), heat treatment, and winding. If silane crosslinking is promoted in the extruder during the sheet molding process, gelled parts will cause production defects and the silane crosslinked polyolefin will be difficult to stretch in the subsequent stretching process. Therefore, there is still room for investigation into new separators for power storage devices that are compatible with the manufacturing process.

[0019] Furthermore, the crosslinking methods described in Patent Documents 1 to 6, 8, and 9 are all performed in-process during separator film formation or in a batch immediately after separator film formation. Therefore, after the formation of the crosslinked structure described in Patent Documents 1 to 6, 8, and 9, the separator must be coated and slit, and the internal stress increases in the subsequent lamination and winding process with the electrodes, which may cause deformation of the produced battery. For example, when a crosslinked structure is formed by heating, the internal stress of the separator having the crosslinked structure may increase at normal temperature or room temperature. Furthermore, when a crosslinked structure is formed by irradiation with light such as ultraviolet light or electron beams, the light irradiation may become non-uniform, resulting in a non-homogeneous crosslinked structure. This is believed to be because the periphery of the crystal parts of the resin that constitutes the separator is easily crosslinked by the electron beam.

[0020] Patent Document 10 describes a technique for improving the cycle characteristics of a lithium-ion secondary battery by adding succinimides or the like to an electrolyte solution. However, the technique described in Patent Document 10 does not aim to improve the cycle characteristics by specifying the structure of the separator.

[0021] Furthermore, the separators for electricity storage devices described in Patent Documents 1, 2 and 11 still have room for improvement in terms of improving the performance of the electricity storage device.

[0022] In view of the above problems, the present invention aims to provide a separator for an electricity storage device that combines a shutdown function with high-temperature rupture resistance and can ensure the safety, output and / or cycle stability of the electricity storage device, and a new crosslinking method compatible with the manufacturing process thereof, or an assembly kit or manufacturing method for the electricity storage device. [Means for solving the problem]

[0023] The above problems are solved by the following technical means. [1] A separator for an electricity storage device, comprising a silane-modified polyolefin, wherein a silane crosslinking reaction of the silane-modified polyolefin is initiated when the separator for an electricity storage device comes into contact with an electrolyte. [2] 2. The separator for an electricity storage device according to item 1, wherein the silane-modified polyolefin is not a masterbatch resin containing a dehydration condensation catalyst that crosslinks the silane-modified polyolefin. [3] 3. The separator for an electricity storage device according to item 1 or 2, wherein the separator for an electricity storage device contains polyethylene in addition to the silane-modified polyolefin. [4] 4. The separator for an electricity storage device according to item 3, wherein a mass ratio of the silane-modified polyolefin to the polyethylene (mass of silane-modified polyolefin / mass of polyethylene) is 0.05 / 0.95 to 0.40 / 0.60. [5] A separator for an electricity storage device comprising 5 to 40 mass % of a silane-modified polyolefin and 60 to 95 mass % of a polyolefin other than the silane-modified polyolefin, the separator comprising a polyolefin represented by the following formula (1): R ΔE’ =E' S / E' j (1) {where, E' j is the storage modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E' Sis the storage modulus of the separator for an electricity storage device after the silane-modified polyolefin has undergone a crosslinking reaction, measured at 160°C to 220°C, and E' j or E' S The conditions for measuring the storage modulus E' are defined by the following configurations (i) to (iv). (i) Dynamic viscoelasticity measurements were performed under the following conditions: Measurement device used: RSA-G2 (manufactured by TA Instruments) -Sample thickness: range of 5μm~50μm Measurement temperature range: -50~225℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.5N Initial gap distance (at 25°C): 25mm Auto strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N) It is done by. (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each periodic motion, and the sinusoidal load refers to a vibration stress centered on the static tensile load. (iii) The sinusoidal tensile mode refers to measuring the vibratory stress while performing periodic motion with a fixed amplitude of 0.2%. In the sinusoidal tensile mode, the vibratory stress is measured by varying the gap distance and the static tensile load so that the difference between the static tensile load and the sinusoidal load is within 20%. When the sinusoidal load becomes 0.02 N or less, the amplitude value is amplified so that the sinusoidal load is within 5 N and the increase in the amplitude value is within 25%, and the vibratory stress is measured. (iv) The relationship between the obtained sinusoidal load and the amplitude value, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E * ε* E * =E'+iE'' (In the formula, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: difference between measured oscillatory stress and static tensile load The storage modulus E' is calculated from The storage modulus change ratio (R ΔE’ ) is 1.5 to 20 times the thickness of the separator for an electricity storage device. [6] A separator for an electricity storage device comprising 5 to 40 mass% of a silane-modified polyolefin and 60 to 95 mass% of a polyolefin other than the silane-modified polyolefin, the separator comprising a polyolefin represented by the following formula (3): R ΔE’’ =E'' S / E'' j (3) {in formula, E'' j is the loss modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E'' S is the loss modulus of the separator for an electricity storage device after the silane-modified polyolefin has undergone a crosslinking reaction, measured at 160°C to 220°C, and E'' j or E'' S The measurement conditions for the loss modulus E″ are defined by the following configurations (i) to (iv). (i) Dynamic viscoelasticity measurements were performed under the following conditions: Measurement device used: RSA-G2 (manufactured by TA Instruments) -Sample thickness: range of 5μm~50μm Measurement temperature range: -50~225℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.5N Initial gap distance (at 25°C): 25mm Auto strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N) It is done by. (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each periodic motion, and the sinusoidal load refers to a vibration stress centered on the static tensile load. (iii) The sinusoidal tensile mode refers to measuring the vibratory stress while performing periodic motion with a fixed amplitude of 0.2%. In the sinusoidal tensile mode, the vibratory stress is measured by varying the gap distance and the static tensile load so that the difference between the static tensile load and the sinusoidal load is within 20%. When the sinusoidal load becomes 0.02 N or less, the amplitude value is amplified so that the sinusoidal load is within 5 N and the increase in amplitude value is within 25%, and the vibratory stress is measured. (iv) The obtained sinusoidal load and amplitude values, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E * ε * E * =E'+iE'' (In the formula, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: difference between measured oscillatory stress and static tensile load Calculate the loss modulus E'' from The loss modulus change ratio (R ΔE’’ ) is 1.5 to 20 times the thickness of the separator for an electricity storage device. [7] A separator for an electricity storage device, characterized in that a silane crosslinking reaction of a silane-modified polyolefin occurs when the separator for an electricity storage device comes into contact with an electrolyte. [8] A separator for an electricity storage device comprising 5 to 40 mass % of a silane-modified polyolefin and 60 to 95 mass % of a polyolefin other than the silane-modified polyolefin, the separator comprising a polyolefin represented by the following formula (2): R E’mix =E' a / E'0(2) {where, E' a is the storage modulus of the separator for an electric storage device measured at 160°C to 220°C, and E'0 is the storage modulus of the separator for an electric storage device not containing the silane-modified polyolefin measured at 160°C to 220°C, and E' a The measurement conditions for the storage modulus E', which is equal to or less than E'0, are defined by the following configurations (i) to (iv). (i) Dynamic viscoelasticity measurements were performed under the following conditions: Measurement device used: RSA-G2 (manufactured by TA Instruments) -Sample thickness: range of 5μm~50μm Measurement temperature range: -50~225℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.5N Initial gap distance (at 25°C): 25mm Auto strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N) It is done by. (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each periodic motion, and the sinusoidal load refers to a vibration stress centered on the static tensile load. (iii) The sinusoidal tensile mode refers to measuring the vibratory stress while performing periodic motion with a fixed amplitude of 0.2%. In the sinusoidal tensile mode, the vibratory stress is measured by varying the gap distance and the static tensile load so that the difference between the static tensile load and the sinusoidal load is within 20%. When the sinusoidal load becomes 0.02 N or less, the amplitude value is amplified so that the sinusoidal load is within 5 N and the increase in the amplitude value is within 25%, and the vibratory stress is measured. (iv) The relationship between the obtained sinusoidal load and the amplitude value, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E * ε * E * =E'+iE'' (In the formula, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: difference between measured oscillatory stress and static tensile load The storage modulus E' is calculated from The mixed storage modulus ratio (R E’mix ) is 1.5 to 20 times the thickness of the separator for an electricity storage device. [9] A separator for an electricity storage device comprising 5 to 40 mass % of a silane-modified polyolefin and 60 to 95 mass % of a polyolefin other than the silane-modified polyolefin, the separator comprising a polyolefin represented by the following formula (4): R E’’mix=E'' a / E''0(4) {in formula, E'' a is the loss modulus of the separator for an electric storage device measured at 160°C to 220°C, and E''0 is the loss modulus of the separator for an electric storage device not containing the silane-modified polyolefin measured at 160°C to 220°C, and E'' a The measurement conditions for the loss modulus E'', which is equal to or less than E'', are specified by the following configurations (i) to (iv). (i) Dynamic viscoelasticity measurements were performed under the following conditions: Measurement device used: RSA-G2 (manufactured by TA Instruments) -Sample thickness: range of 5μm~50μm Measurement temperature range: -50~225℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.5N Initial gap distance (at 25°C): 25mm Auto strain adjustment: Enabled (range: amplitude 0.05-25%, sine wave load 0.02-5N) It is done by. (ii) The static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each periodic motion, and the sinusoidal load refers to a vibration stress centered on the static tensile load. (iii) The sinusoidal tensile mode refers to measuring the vibratory stress while performing periodic motion with a fixed amplitude of 0.2%. In the sinusoidal tensile mode, the vibratory stress is measured by varying the gap distance and the static tensile load so that the difference between the static tensile load and the sinusoidal load is within 20%. When the sinusoidal load becomes 0.02 N or less, the amplitude value is amplified so that the sinusoidal load is within 5 N and the increase in amplitude value is within 25%, and the vibratory stress is measured. (iv) The obtained sinusoidal load and amplitude values, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E * ε * E * =E'+iE'' (In the formula, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: difference between measured oscillatory stress and static tensile load Calculate the loss modulus E'' from The mixed loss modulus ratio (R E’’mix ) is 1.5 to 20.0 times.

[10] 10. The separator for an electricity storage device according to item 8 or 9, wherein the separator for an electricity storage device not containing a silane-modified polyolefin is a microporous membrane made of a non-silane-modified polyolefin and has a gelation degree of 0% or more and 10% or less.

[11] A separator for an electric storage device comprising 5 to 40 mass% of a silane-modified polyolefin and 60 to 95 mass% of a polyolefin other than the silane-modified polyolefin, wherein the transition temperature between a rubber-like plateau region and a crystalline melting flow region in the temperature change of the storage elastic modulus of the separator for the electric storage device is 135°C to 150°C.

[12] A separator for an electricity storage device comprising a polyolefin microporous membrane, In the solid viscoelasticity measurement of the separator for an electricity storage device at a temperature of -50°C to 250°C, The minimum storage modulus is 1.0 MPa to 10 MPa, and the maximum storage modulus is 100 MPa to 10,000 MPa; and The minimum loss modulus is 0.1 MPa to 10 MPa, and the maximum loss modulus is 10 MPa to 10,000 MPa; The solid viscoelasticity measurement conditions for measuring the storage modulus and the loss modulus are as follows: (i) Dynamic viscoelasticity measurements were performed under the following conditions: Measurement device used: RSA-G2 (manufactured by TA Instruments) Sample thickness: 200μm to 400μm (However, if the thickness of the sample itself is less than 200μm, multiple samples are stacked together and the dynamic viscoelasticity measurement is performed so that the total thickness is within the range of 200μm to 400μm.) Measurement temperature range: -50℃~250℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.2N Initial gap distance (at 25°C): 10mm Auto strain adjustment: Disabled Do with; (ii) the static tensile load refers to the intermediate value between the maximum stress and the minimum stress in each periodic motion, and the sinusoidal load refers to an oscillatory stress centered on the static tensile load; (iii) the sine wave tension mode refers to measuring the vibration stress while performing periodic motion with a fixed amplitude of 0.1%, and in the sine wave tension mode, the gap distance and the static tensile load are varied so that the difference between the static tensile load and the sine wave load is within 5%, and the vibration stress is measured, and when the sine wave load becomes 0.1 N or less, the static tensile load is fixed at 0.1 N to measure the vibration stress; (iv) The relationship between the obtained sinusoidal load and the amplitude value, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E* ε * E * =E'+iE'' {where, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: the difference between the measured oscillatory stress and the static tensile load Calculating the storage modulus and the loss modulus from A separator for an electricity storage device as defined in claim 1.

[13] A separator for an electricity storage device comprising a polyolefin microporous membrane, the separator for an electricity storage device having an average storage modulus of 1.0 MPa to 12 MPa and an average loss modulus of 0.5 MPa to 10 MPa in solid viscoelastic measurement from a membrane softening transition temperature to a membrane rupture temperature.

[14] Item 14. The separator for use in an electricity storage device according to item 13, wherein, in the solid viscoelasticity measurement, the film softening transition temperature is 140° C. to 150° C. and the film rupture temperature is 180° C. or higher.

[15] 15. The separator for an electricity storage device according to any one of items 12 to 14, comprising a silane-modified polyolefin and a polyolefin other than the silane-modified polyolefin.

[16] Item 16. The separator for an electricity storage device according to item 15, comprising 5% by mass to 40% by mass of a silane-modified polyolefin and 60% by mass to 95% by mass of a polyolefin other than the silane-modified polyolefin.

[17] A separator for an electricity storage device comprising a polyolefin, The polyolefin has one or more functional groups, and A separator for an electricity storage device, characterized in that after being stored in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a cross-linked structure.

[18] Item 18. The separator for an electricity storage device according to item 17, wherein the chemical substance is any one of an electrolyte, an electrolytic solution, an electrode active material, an additive, or a decomposition product thereof contained in the electricity storage device.

[19] A separator for an electricity storage device comprising a polyolefin, the separator having an amorphous part crosslinked structure in which an amorphous part of the polyolefin is crosslinked.

[20] The separator for an electricity storage device has the following formula (1): R E’X =E' Z / E' Z0 (1) {where, E' Z is a storage modulus measured in a temperature range of 160°C to 300°C after the crosslinking reaction of the separator for an electricity storage device has progressed in the electricity storage device, and E' Z0 is the storage modulus measured in a temperature range of 160° C. to 300° C. before the electricity storage device separator is incorporated into the electricity storage device.} The mixed storage modulus ratio (R E’x 20. The separator for an electricity storage device according to item 19, wherein the ratio of the surface area to the surface area of ​​the separator is 1.5 to 20 times. [twenty one] The separator for an electricity storage device has the following formula (3): R E’’X =E'' Z / E'' Z0 (3) {in formula, E'' Z is a loss modulus measured in a temperature range of 160°C to 300°C after the crosslinking reaction of the separator for an electricity storage device has progressed in the electricity storage device, and E'' Z0is the loss modulus measured in a temperature range of 160°C to 300°C before the electricity storage device separator is incorporated into the electricity storage device.} The mixed loss modulus ratio (R E’’x 21. The separator for an electricity storage device according to item 19 or 20, wherein the ratio of the surface area to the surface area of ​​the separator is 1.5 to 20 times. [twenty two] 22. The power storage device separator according to any one of items 19 to 21, wherein the amorphous portion is selectively crosslinked. [twenty three] The separator for an electricity storage device has the following formula (2): R E’mix =E' / E'0(2) In the formula, E' is a storage modulus measured at 160°C to 300°C when the electricity storage device separator has an amorphous crosslinked structure, and E'0 is the storage modulus of the electricity storage device separator not having an amorphous crosslinked structure, measured at 160°C to 300°C.} The mixed storage modulus ratio (R E’mix 23. The separator for an electricity storage device according to any one of items 17 to 22, wherein the ratio of the surface area to the surface area of ​​the separator is 1.5 to 20 times. [twenty four] The separator for an electricity storage device has the following formula (4): R E’’mix =E'' / E''0(4) In the formula, E″ is a loss modulus measured at 160° C. to 300° C. when the electricity storage device separator has an amorphous crosslinked structure, and E''0 is the loss modulus of the electricity storage device separator not having an amorphous crosslinked structure, measured at 160°C to 300°C.} The mixed loss modulus ratio (R E’’mix 24. The separator for an electricity storage device according to any one of items 17 to 23, wherein the ratio of the surface area to the surface area of ​​the separator is 1.5 to 20 times. [twenty five] 25. The separator for use in an electricity storage device according to any one of items 17 to 24, wherein the polyolefin is polyethylene.

[26] 26. The separator for an electricity storage device according to any one of items 17 to 25, wherein the polyolefin is a functional group-modified polyolefin or a polyolefin copolymerized with a monomer having a functional group.

[27] 27. The separator for an electricity storage device according to any one of items 17 to 26, wherein the crosslinked structure is formed by a reaction via any one of a covalent bond, a hydrogen bond, or a coordinate bond.

[28] The reaction via the covalent bond is represented by the following reactions (I) to (IV): (I) Condensation reactions of multiple identical functional groups; (II) Reactions between multiple heterogeneous functional groups; (III) chain condensation reaction of functional groups with the electrolyte; and (IV) reaction of functional groups with additives; Item 28. The separator for an electricity storage device according to item 27, wherein the separator is at least one selected from the group consisting of:

[29] The reaction via the coordinate bond is the following reaction (V): (V) A reaction in which multiple identical functional groups crosslink through coordinate bonds with metal ions; Item 28. The separator for an electricity storage device according to Item 27,

[30] Item 29. The separator for an electrical storage device according to item 28, wherein the reaction (I) and / or (II) is catalytically promoted by a chemical substance inside the electrical storage device.

[31] Item 29. The electricity storage device separator according to item 28, wherein the reaction (I) is a condensation reaction of a plurality of silanol groups.

[32] Item 29. The separator for an electricity storage device according to Item 28, wherein the reaction (IV) is a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction between a compound Rx constituting the electricity storage device separator and a compound Ry constituting the additive, and the compound Rx has a functional group x, and the compound Ry has a linking reaction unit y1.

[33] the reaction (IV) is a nucleophilic substitution reaction, The functional group x of the compound Rx is at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH; and The linking reaction unit y1 of the compound Ry is CH3SO2-, CF3SO2-, ArSO2-, CH3SO3-, CF3SO3-, ArSO3-, and the following formulas (y1-1) to (y1-6): [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} Item 33. The separator for an electricity storage device according to item 32, wherein the at least two are selected from the group consisting of monovalent groups represented by

[34] the reaction (IV) is a nucleophilic substitution reaction, The compound Ry has a chain unit y2 in addition to the linking reaction unit y1, and The chain unit y2 is represented by the following formulae (y2-1) to (y2-6): [ka] {In the formula, m is an integer of 0 to 20, and n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} Item 34. The separator for an electricity storage device according to item 32 or 33, wherein the R 1 -R 2 group is at least one selected from the group consisting of divalent groups represented by the following formula:

[35] Reaction (IV) is a nucleophilic addition reaction, The functional group x of the compound Rx is at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH; and The linking reaction unit y1 of the compound Ry is represented by the following formulae (Ay1-1) to (Ay1-6): [ka] [ka] [ka] [ka] In the formula, R is a hydrogen atom or a monovalent organic group. [ka] [ka] Item 33. The separator for use in an electricity storage device according to item 32, wherein the at least one group is selected from the group consisting of groups represented by the following formula:

[36] the reaction (IV) is a ring-opening reaction, The functional group x of the compound Rx is at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH; and The linking reaction unit y1 of the compound Ry is represented by the following formula (ROy1-1): [ka] In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent. 33. The separator for an electricity storage device according to item 32, wherein the at least two groups are represented by the following formula:

[37] In the following reaction (V), the metal ion is Zn 2+ , Mn 2+ , Co 3+ , Ni 2+ and Li + 30. The separator for an electricity storage device according to item 29, wherein the separator is at least one selected from the group consisting of:

[38] A separator for an electricity storage device comprising a first porous layer (layer A) containing a silane-modified polyolefin and capable of forming a crosslinked structure, and a second porous layer (layer B) containing inorganic particles, wherein the heat shrinkage rate at 150°C after the formation of the crosslinked structure is 0.02 to 0.91 times the heat shrinkage rate at 150°C before the formation of the crosslinked structure.

[39] Item 39. The separator for an electricity storage device according to item 38, wherein the crosslinked structure in the layer A is formed by an acid, a base, swelling, or a compound generated within the electricity storage device.

[40] A microporous membrane containing a silane-modified polyolefin; an inorganic porous layer including inorganic particles and a resin binder disposed on at least one surface of the microporous membrane; A separator for an electricity storage device comprising:

[41] Item 41. The separator for use in an electricity storage device according to item 40, wherein the content of the inorganic particles in the inorganic porous layer is 5% by weight to 99% by weight.

[42] Item 42. The separator for use in an electricity storage device according to item 40 or 41, wherein the content of the silane-modified polyolefin in the microporous film is 0.5% by weight to 40% by weight.

[43] 43. The separator for an electricity storage device according to any one of items 40 to 42, wherein the inorganic particles are at least one selected from the group consisting of alumina (Al2O3), silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, iron oxide, silicon nitride, titanium nitride, boron nitride, silicon carbide, aluminum oxide hydroxide (AlO(OH)), talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, diatomaceous earth, silica sand, and glass fiber.

[44] 44. The separator for use in an electricity storage device according to any one of items 40 to 43, wherein the resin binder has a glass transition temperature (Tg) of -50°C to 100°C.

[45] Item 45. The separator for an electricity storage device according to any one of items 40 to 44, wherein a silane crosslinking reaction of the silane-modified polyolefin is initiated when the separator for an electricity storage device is brought into contact with an electrolyte solution.

[46] The electricity storage device separator, when measured excluding the inorganic porous layer, has a molecular weight of 1.0 or more and a molecular weight of 1.0 or more. R △E’ =E' S / E' j (1A) {where, E' jis the storage modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E' S is the storage modulus measured at 160° C. to 220° C. of the separator for an electricity storage device after the silane-modified polyolefin has undergone a crosslinking reaction.} The storage modulus change ratio (R △E’ ) is 1.5 to 20 times, and / or the following formula (1B): R △E’’ =E'' S / E'' j (1B) {in formula, E'' j is the loss modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E'' S is the loss modulus of the electricity storage device separator after the silane-modified polyolefin has undergone a crosslinking reaction, measured at 160° C. to 220° C.} The loss modulus change ratio (R △E 46. ​​The separator for an electricity storage device according to any one of items 40 to 45, wherein the ratio of the surface area to the surface area of ​​the separator is 1.5 to 20 times.

[47] The electricity storage device separator, when measured excluding the inorganic porous layer, has a molecular weight of 1.0 or more and a molecular weight of 1.0 or more as represented by the following formula (2A): R E’mix =E' / E'0(2A) {In the formula, E' is the storage modulus of the electricity storage device separator measured at 160°C to 220°C, and E'0 is the storage modulus of the electricity storage device separator that does not contain the silane-modified polyolefin measured at 160°C to 220°C.} The mixed storage modulus ratio (R E’mix ) is 1.5 to 20 times, and / or the following formula (2B): R E’’mix =E'' / E''0(2B) {In the formula, E'' is the loss modulus of the electricity storage device separator measured at 160°C to 220°C, and E''0 is the loss modulus of the electricity storage device separator that does not contain the silane-modified polyolefin measured at 160°C to 220°C.} The mixed loss modulus ratio (R E’’mix 47. The separator for an electricity storage device according to any one of items 40 to 46, wherein the ratio of the surface area to the surface area of ​​the separator is 1.5 to 20 times.

[48] Item 48. The separator for use in an electricity storage device according to any one of items 40 to 47, wherein the transition temperature between the rubber-like flat region and the crystalline melt flow region in the change in storage modulus with temperature of the separator for use in an electricity storage device is 135°C to 150°C.

[49] 49. An electricity storage device comprising: an electrode; the separator for an electricity storage device according to any one of items 1 to 48; and a non-aqueous electrolyte solution.

[50] An electricity storage device comprising a separator containing polyethylene and an electrolytic solution or an additive, in which a crosslinked structure is formed by reacting a functionally modified polyethylene or a functional group graft copolymerized polyethylene with a chemical substance contained in the electrolytic solution or the additive.

[51] The process is as follows: (1) a sheet forming step of extruding a mixture of silane-modified polyolefin, polyethylene and a plasticizer, cooling and solidifying the mixture, and forming the mixture into a sheet; (2) a stretching step of stretching the sheet in at least one axial direction to obtain a stretched product; (3) a porous body forming step of extracting the plasticizer from the stretched material in the presence of an extraction solvent to make the stretched material porous, thereby forming a porous body; and (4) a heat treatment step of subjecting the porous body to a heat treatment; 51. A method for producing a separator for an electricity storage device according to any one of items 1 to 50, comprising:

[52] The process is as follows: (1) A sheet forming step in which the silane-modified polyolefin, polyethylene and plasticizer are extruded into a sheet using an extruder, cooled and solidified, and processed into a sheet-like molded product; (2) a stretching step in which the sheet-like molded product is biaxially stretched at an areal magnification of 20 times or more and 250 times or less to form a stretched product; (3) a porous body forming step of extracting the plasticizer from the stretched material to form a porous body; (4) a heat treatment step of subjecting the porous body to a heat treatment, stretching and relaxing in the width direction to obtain a heat-treated porous body; (8B) a coating step of forming an inorganic porous layer containing inorganic particles and a resin binder on at least one surface of the heat-treated porous body to form a silane crosslinking precursor; (9) an assembly step of housing a laminate or a wound body of the laminate of the electrodes and the silane cross-linked precursor, and a non-aqueous electrolyte solution in an exterior body, and bringing the silane cross-linked precursor into contact with the non-aqueous electrolyte solution; The method for producing a separator for an electricity storage device includes the steps of:

[53] The following two elements: (1) An exterior body housing an electrode and a laminate or a wound body of the separator for an electricity storage device according to any one of items 1 to 48; and (2) a container containing a nonaqueous electrolyte; An electricity storage device assembly kit comprising:

[54] Item 54. The electricity storage device assembly kit according to item 53, wherein the non-aqueous electrolyte solution contains a fluorine (F)-containing lithium salt.

[55] Item 55. The electricity storage device assembly kit according to item 53 or 54, wherein the non-aqueous electrolyte solution contains lithium hexafluorophosphate (LiPF6).

[56] 56. The electricity storage device assembly kit according to any one of items 53 to 55, wherein the non-aqueous electrolyte solution is an acid solution and / or a base solution.

[57] The following steps: A step of preparing an electricity storage device assembly kit according to any one of items 53 to 56; a step of initiating a silane crosslinking reaction of a silane-modified polyolefin by contacting the separator for an electricity storage device in an element (1) of the electricity storage device assembly kit with the nonaqueous electrolyte in an element (2); A method for manufacturing an electricity storage device comprising the steps of:

[58] Further steps: A step of connecting a lead terminal to the electrode of the element (1); performing at least one charge / discharge cycle; Item 58. A method for producing an electricity storage device according to Item 57, comprising:

[59] A method for producing an electricity storage device using a separator containing polyolefin, comprising the steps of: The polyolefin comprises one or more types of functional groups, and the process comprises the steps of: (1) a cross-linking step of forming a cross-linked structure by condensing the functional groups together, (2) reacting the functional groups with chemicals inside the power storage device, or (3) reacting the functional groups with other types of functional groups. A method for manufacturing an electricity storage device comprising the steps of:

[60] Item 60. The method for producing an electricity storage device according to item 59, wherein the crosslinking step is carried out at a temperature of 5°C to 90°C. Effect of the Invention

[0024] According to the present invention, it is possible to provide an electricity storage device and an assembly kit thereof having good cycle characteristics and high safety by achieving both a low-temperature shutdown function and high-temperature rupture resistance of a separator for an electricity storage device and suppressing the generation of unmolten resin agglomerates in the manufacturing process, thereby contributing to productivity and economy.

[0025] Moreover, according to the present invention, since it is not necessary to form a crosslinked structure during or immediately after the film formation process, it is possible to suppress an increase in the internal stress of the separator and deformation after the production of the electricity storage device, and / or it is possible to impart a crosslinked structure to the separator without using relatively high energy such as light irradiation or heating, thereby reducing uneven crosslinking. Furthermore, according to the present invention, a crosslinked structure is formed not only inside the separator, but also between the separator and the electrode or between the separator and the solid electrolyte interface (SEI), thereby improving the strength between multiple members of the electricity storage device, and suppressing gaps between the separator caused by the expansion and contraction of the electrodes during charging and discharging of the electricity storage device, thereby significantly improving cycle stability during long-term use. [Brief description of the drawings]

[0026] [Figure 1] FIG. 1 is an example of a graph for explaining the relationship between temperature and storage modulus, and shows the transition temperature between the rubber-like plateau region and the crystalline melt flow region by comparing the storage modulus of a reference film and a crosslinked film in the temperature range of −50° C. to 225° C. [Diagram 2] FIG. 2 is an example of a graph for explaining the relationship between temperature and loss modulus, and shows the transition temperature between the rubber-like plateau region and the crystalline melt flow region by comparing the loss modulus of a reference membrane and a crosslinked membrane in the temperature range of -50°C to 225°C. [Diagram 3] FIG. 3 is a graph showing the relationship between temperature and resistance of an electricity storage device including the separator obtained in Example I-1. [Figure 4] FIG. 4 is a graph illustrating the relationship among temperature, gap distance, storage modulus, and loss modulus in the viscoelasticity measurement of a separator for an electricity storage device, and illustrates graph (a) of Example II-1 and graph (b) of Comparative Example II-1. [Diagram 5] FIG. 5 is a graph for determining the film-softening transition temperature based on the temperature, gap distance, and first derivative value of gap displacement in the viscoelastic measurement of a separator for an electricity storage device, and illustrates graph (a) of Example II-1 and graph (b) of Comparative Example II-1. [Figure 6]FIG. 6 is a schematic diagram for explaining a crystalline polymer having a higher-order structure divided into lamellae (crystalline portions), amorphous portions, and intermediate layers between them. [Figure 7] FIG. 7 is a schematic diagram for explaining the crystal growth of polyolefin molecules. [Figure 8] FIG. 8 is a graph showing the change in X-ray crystal structure during a tensile fracture test of a film according to one embodiment of the present invention versus the strain amount versus crystal refinement rate. [Figure 9] FIG. 9 is an example of a graph illustrating the relationship between temperature and storage modulus, comparing the storage modulus of a reference film and a crosslinked film in the temperature range of −50° C. to 310° C., and showing the transition temperature between the rubber-like plateau region and the crystalline melt flow region. [Figure 10] FIG. 10 is an example of a graph for explaining the relationship between temperature and loss modulus, and shows the transition temperature between the rubber-like plateau region and the crystalline melt flow region by comparing the loss modulus of a reference membrane and a crosslinked membrane in the temperature range of −50° C. to 310° C. [Figure 11] FIG. 11 shows (a) a 1H-NMR chart and (b) a 13C-NMR chart of the silane-modified polyolefin raw material 1 obtained using polyolefin. [Figure 12] FIG. 12 shows (a) a 1H-NMR chart and (b) a 13C-NMR chart of the silane-modified polyolefin raw material 2 obtained using polyolefin. [Figure 13] FIG. 13 shows (a) a 1H-NMR chart and (b) a 13C-NMR chart of the separator obtained in Example I-1 in a pre-crosslinked state. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0027] Hereinafter, a detailed description will be given of an embodiment of the present invention (hereinafter, abbreviated as "embodiment"). Note that the present invention is not limited to the following embodiment, and can be modified in various ways within the scope of the present invention.

[0028] In this specification, the word "to" means that the numerical values ​​at both ends are the upper limit and the lower limit. In this specification, the upper limit and the lower limit of the numerical range can be arbitrarily combined. For example, the upper limit of a preferred numerical range may be combined with the lower limit of a more preferred numerical range, and conversely, the upper limit of a more preferred numerical range may be combined with the lower limit of a preferred numerical range.

[0029] In this specification, the terms "on" and "formed on the surface" do not limit the positional relationship of each component to "directly on top." For example, the expressions "layer B formed on layer A" and "layer B formed on the surface of layer A" do not exclude a case in which an arbitrary layer that does not fall into either of the categories of layer A and layer B is included between them.

[0030] The properties of only the microporous membrane described below can be measured after removing layers other than the microporous membrane (eg, inorganic porous layer) from the electricity storage device separator.

[0031] <Separators for power storage devices> One embodiment of the present invention is a separator for an electricity storage device (hereinafter, also simply referred to as "separator"). Since the separator needs to have insulating properties and ion permeability, it generally includes an insulating material having a porous structure, such as paper, a polyolefin nonwoven fabric, or a resin microporous film. In particular, in lithium ion batteries, a polyolefin microporous film is excellent in terms of the separator's resistance to oxidation-reduction deterioration and the ability to construct a dense and uniform porous structure. Here, the microporous membrane refers to a membrane (film) made of a porous body, and the average pore size thereof is preferably 10 nm or more and 500 nm or less, and more preferably 30 nm or more and 100 nm or less. When the separator is included in the power storage device, it is possible to remove the separator from the power storage device.

[0032] First, Second, Third, Fourth and Fifth Embodiments The separator according to the first embodiment includes a silane-modified polyolefin, and may include other polyolefins as desired. When the separator according to the first embodiment comes into contact with an electrolytic solution, a silane crosslinking reaction of the silane-modified polyolefin contained in the separator is initiated. Since the separator according to the first embodiment can crosslink the silane-modified polyolefin when it comes into contact with the electrolytic solution, the timing of crosslinking can be controlled, and therefore the crosslinking reaction can be performed in the manufacturing process of the electricity storage device without performing the crosslinking reaction in the manufacturing process of the separator.

[0033] The separator according to the second embodiment is characterized in that a silane crosslinking reaction of the silane-modified polyolefin occurs when the separator comes into contact with the electrolyte. In the second embodiment, regardless of whether the separator contains a silane-modified polyolefin, where the remaining silane-modified polyolefin is, and whether the silane crosslinking reaction starts first, occurs sequentially, or occurs continuously when the separator comes into contact with the electrolyte, the silane crosslinking reaction may be observed when the separator comes into contact with the electrolyte. The silane crosslinking reaction of the silane-modified polyolefin that occurs when the separator according to the second embodiment comes into contact with the electrolyte can achieve control of the crosslinking timing, regardless of the manufacturing or use process of the separator.

[0034] The separators according to the first and second embodiments can promote the crosslinking reaction when the electrolyte is poured into the exterior body that houses the separator, thereby avoiding production defects in the manufacturing process and achieving safety and high output of the electricity storage device in the manufacturing process of the electricity storage device. From the viewpoint of the components contained in the separator and the timing of the crosslinking reaction, it is preferable that the silane crosslinking reaction of the silane-modified polyolefin is initiated when the separator is mixed with or contacted with the electrolyte.

[0035] The separator according to the third embodiment contains 5 to 40 mass % of a silane-modified polyolefin and 60 to 95 mass % of a polyolefin other than the silane-modified polyolefin, and has a viscoelasticity measured by the following formula (1) (version 1) as described in the examples: R ΔE’ =E' S / E' j (1) {where, E' j is the storage modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E' S is the storage modulus measured at 160°C to 220°C of the separator for an electricity storage device after the silane-modified polyolefin has undergone a crosslinking reaction.} The storage modulus change ratio (R ΔE’ ) is 1.5 to 20 times, and / or the following formula (3): R ΔE’’ =E'' S / E'' j (3) {in formula, E'' j is the loss modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E'' S is the loss modulus of the electricity storage device separator after the silane-modified polyolefin has undergone a crosslinking reaction, measured at 160° C. to 220° C.} The loss modulus change ratio (R ΔE’’ In the third embodiment, the storage elastic modulus change ratio (R ΔE’ ) and / or the loss modulus change ratio (R ΔE’’ By setting the storage modulus change ratio (R ΔE’ ) and / or the loss modulus change ratio (R ΔE’’ ) is preferably 2 to 18 times. j and E' S and E'' j and E'' Sare the average values ​​of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160 to 220°C. In addition, when the separator is in the form of a laminated film, the storage modulus E' j and E' S and loss modulus E'' j and E'' S shall be measured.

[0036] The separator according to the fourth embodiment contains 5 to 40 mass % of a silane-modified polyolefin and 60 to 95 mass % of a polyolefin other than the silane-modified polyolefin, and has a viscoelasticity measured (version 1) as described in the examples and satisfies the following formula (2): R E’mix =E' a / E'0(2) {where, E' a is the storage modulus of the separator for an electricity storage device measured at 160°C to 220°C, and E'0 is the storage modulus of the separator for an electricity storage device that does not contain a silane-modified polyolefin measured at 160°C to 220°C.} The mixed storage modulus ratio (R E’mix ) is 1.5 to 20 times, and / or the following formula (4): R E’’mix =E'' a / E''0(4) {in formula, E'' a is the loss modulus of the electricity storage device separator measured at 160°C to 220°C, and E''0 is the loss modulus of the electricity storage device separator not containing the silane-modified polyolefin measured at 160°C to 220°C.} The mixed loss modulus ratio (R E’’mix In the fourth embodiment, the mixed storage modulus ratio (R E’mix ) and / or the blend loss modulus ratio (R E’’mix By setting the mixed storage modulus ratio (RE’mix ) and / or the blend loss modulus ratio (R E’’mix ) is preferably 2 to 18 times. a and E'0 and E'' a and E''0 are the average values ​​of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160 to 220°C. In addition, when the separator is in the form of a laminated film, the storage modulus E' a and E'0 and loss modulus E'' a and E''0 shall be measured.

[0037] The separator according to the fifth embodiment contains 5 to 40% by mass of a silane-modified polyolefin and 60 to 95% by mass of a polyolefin other than the silane-modified polyolefin, and in the viscoelasticity measurement (version 1) described in the examples, the transition temperature between the rubber-like flat region and the crystalline melting flow region is 135°C to 150°C in the temperature change of the storage modulus or loss modulus. In the fifth embodiment, the transition temperature between the rubber-like flat region and the crystalline melting flow region is within the range of 135°C to 150°C, so that both the shutdown function and high-temperature membrane rupture resistance can be achieved. The transition temperature between the rubber-like flat region and the crystalline melting flow region is preferably 137°C to 147°C, more preferably 140°C to 145°C, and even more preferably 140°C to 143°C. In addition, when the separator is in the form of a laminated film, only the silane-modified polyolefin-containing porous film is removed from the laminate, and the transition temperature between the rubber-like flat region and the crystalline melting flow region is measured.

[0038] Sixth and Seventh Embodiments The separator according to the sixth embodiment includes a polyolefin having one or more functional groups, and after being housed in an electricity storage device, (1) the functional groups of the polyolefin undergo a condensation reaction with each other, (2) the functional groups of the polyolefin react with chemicals inside the electricity storage device, or (3) the functional groups of the polyolefin react with other types of functional groups to form a crosslinked structure. It is considered that the functional groups contained in the polyolefin constituting the separator are not incorporated into the crystalline portion of the polyolefin, but are crosslinked in the amorphous portion, so that the separator according to the sixth embodiment forms a crosslinked structure by utilizing the surrounding environment or chemicals inside the electricity storage device after being housed in the electricity storage device, thereby suppressing an increase in internal stress or deformation of the produced electricity storage device. On the other hand, if a crosslinking reaction is carried out before being installed in an electricity storage device and processes such as winding and slitting are performed, the effects of stress such as tension generated during the process remain. In this case, if the stress is released after the electricity storage device is assembled, it is considered that it may cause deformation or damage to the electrode windings due to stress concentration, which is not preferable.

[0039] In the sixth embodiment, (1) the condensation reaction between functional groups of a polyolefin may be, for example, a reaction via a covalent bond between two or more functional groups A contained in the polyolefin. (3) The reaction between a functional group of a polyolefin and another type of functional group may be, for example, a reaction via a covalent bond between a functional group A and a functional group B contained in the polyolefin.

[0040] In addition, in the reaction (2) between the functional group of the polyolefin and a chemical substance inside the electricity storage device, for example, the functional group A contained in the polyolefin can form a covalent bond or a coordinate bond with any of the electrolyte, electrolytic solution, electrode active material, additives, or decomposition products thereof contained in the electricity storage device. In addition, according to the reaction (2), a crosslinked structure can be formed not only inside the separator but also between the separator and the electrode or between the separator and the solid electrolyte interface (SEI), thereby improving the strength between multiple members of the electricity storage device.

[0041] The separator according to the seventh embodiment contains a polyolefin and has an amorphous crosslinked structure in which the amorphous part of the polyolefin is crosslinked. Since the functional group contained in the polyolefin constituting the separator is not incorporated into the crystalline part of the polyolefin and is considered to be crosslinked in the amorphous part, the separator according to the seventh embodiment can suppress the increase in internal stress or the deformation of the produced electricity storage device while achieving both a shutdown function and high-temperature membrane rupture resistance, compared to a conventional crosslinked separator in which the crystalline part and its periphery are easily crosslinked, and thus can ensure the safety of the electricity storage device. From the same viewpoint, the amorphous part of the polyolefin contained in the separator according to the seventh embodiment is preferably selectively crosslinked, and more preferably, is significantly crosslinked compared to the crystalline part.

[0042] Although the crosslinking reaction mechanism and crosslinking structure in the seventh embodiment are not clear, the present inventors consider the following.

[0043] (1) Crystal structure in microporous high-density polyethylene membrane As shown in Figure 6, polyolefin resins such as high density polyethylene are generally crystalline polymers, and have a higher-order structure divided into lamellae (crystalline parts) of the crystal structure, amorphous parts, and intermediate layers between them. In the crystalline parts and the intermediate layers between the crystalline and amorphous parts, the mobility of the polymer chains is low and they cannot be separated, but relaxation phenomena can be observed in the 0 to 120°C range in solid viscoelasticity measurements. On the other hand, the mobility of the polymer chains in the amorphous parts is very high, and they are observed in the -150 to -100°C range in solid viscoelasticity measurements. This is closely related to the relaxation of radicals, radical migration reactions, crosslinking reactions, etc., which will be described later.

[0044] Furthermore, the polyolefin molecules that make up the crystals are not single; as shown in Figure 7, multiple polymer chains form small lamellae, which then aggregate to form crystals. This phenomenon is difficult to observe directly. In recent years, academic research has progressed through simulations and the phenomenon has become clearer. Note that here, a crystal is the smallest crystal unit that can be measured by X-ray structural analysis, and is the unit that can be calculated as the crystallite size. Thus, even in the crystalline portion (inside the lamella), it is predicted that there are some parts that are not constrained within the crystal and have a somewhat high degree of mobility.

[0045] (2) Crosslinking reaction mechanism by electron beam Next, the reaction mechanism of electron beam crosslinking (hereafter abbreviated to EB crosslinking) to polymers is as follows: (i) irradiation of an electron beam of tens to hundreds of kGy, (ii) penetration of the electron beam into the reaction target (polymer) and generation of secondary electrons, (iii) hydrogen abstraction reaction in the polymer chain by the secondary electrons and generation of radicals, (iv) adjacent hydrogen abstraction by radicals and movement of active sites, (v) crosslinking reaction or polyene formation by recombination of radicals. Here, the radicals generated in the crystal part have poor motion, so they exist for a long time, and impurities cannot enter the crystal, so the probability of reaction and quenching is low. Such radical species are called stable radicals, and remain for a long period of several months, and their lifespan was clarified by ESR measurement. As a result, it is considered that crosslinking reactions in the crystal are poor. However, in the unconstrained molecular chains that exist in small amounts inside the crystal or in the surrounding crystal-amorphous intermediate layer, the generated radicals have a somewhat long lifespan. Such radical species are called persistent radicals, and in a mobile environment, it is believed that cross-linking reactions between molecular chains will proceed with a high probability. On the other hand, since the mobility of the non-crystalline portion is very high, the generated radical species have a short life span, and it is believed that not only cross-linking reactions between molecular chains but also polyene reactions within a single molecular chain will proceed with a high probability. As described above, in a microscopic view at the crystal level, it can be assumed that the crosslinking reaction due to EB crosslinking is localized inside the crystal or its periphery.

[0046] (3) Crosslinking reaction mechanism by chemical reaction In the seventh embodiment of the present invention, it is preferable to use a functional group in the polyolefin resin and a chemical substance contained in the electricity storage device, or a chemical substance contained in the electricity storage device, as a catalyst. As mentioned above, polyolefin resins have crystalline and amorphous parts. However, the functional groups mentioned above are not present inside the crystals due to steric hindrance, but are localized in the amorphous parts. This is generally known, and although units such as methyl groups contained in small amounts in the polyethylene chain may be incorporated into the crystals, grafts that are bulkier than ethyl groups are not incorporated (Non-Patent Document 2). For this reason, crosslinking points resulting from reactions other than electron beam crosslinking are localized only in the amorphous parts.

[0047] (4) Relationship between differences in cross-linking structure and effects As described above, the morphology of the reaction product differs in the crosslinking reaction caused by a chemical reaction inside the battery used in the seventh embodiment of the present invention. In the research leading to the present invention, the phenomenon was elucidated by the following experiments in order to clarify the crosslinking structure and the changes in the physical properties of the microporous membrane that accompany the structural change. First, the mechanical properties of the membrane were investigated by tensile rupture tests. In addition, at the same time as the tensile rupture tests, the crystal structure change was analyzed by in-situ X-ray structural analysis using synchrotron radiation. As shown in Figure 8, the results show that, compared to a membrane that had not been EB crosslinked or chemically crosslinked (before), the EB crosslinked membrane suppressed the subdivision of the crystal part as the strain amount increased. This is because the inside or periphery of the crystal part was selectively crosslinked. Accordingly, the Young's modulus and rupture strength were significantly improved, and high mechanical strength was achieved. On the other hand, the chemically crosslinked membrane showed no difference in the subdivision of the crystal before and after the crosslinking reaction, suggesting that the non-crystalline part was selectively crosslinked. Furthermore, there was no change in the mechanical strength before and after the crosslinking reaction. Next, the behavior of both materials during crystal melting was examined by fuse / meltdown characteristic tests. As a result, the fuse temperature of the EB crosslinked film was significantly higher, with the meltdown temperature rising to 200°C or higher. On the other hand, the fuse temperature of the chemically crosslinked film remained unchanged before and after the crosslinking treatment, and it was confirmed that the meltdown temperature rose to 200°C or higher. From this, it is considered that the fuse (shutdown) characteristics caused by crystal melting in the EB crosslinked film were caused by crosslinking around the crystal parts, which resulted in an increase in melting temperature and a decrease in melting speed. On the other hand, it was concluded that the chemically crosslinked film did not affect the shutdown characteristics because it did not have a crosslinked structure in the crystal parts. In addition, in the high temperature range of around 200°C, both have a crosslinked structure after crystal melting, so the entire resin can be stabilized in a gel state, resulting in good meltdown characteristics.

[0048] The above findings are summarized in the table below. [Table 1]

[0049] From the viewpoints of forming an amorphous crosslinked structure, achieving both a shutdown function and high-temperature resistance to film rupture, etc., the separator according to the seventh embodiment satisfies the following formula (1) in the viscoelasticity measurement (version 2) described in the examples: R E’X =E' Z / E' z0 (1) {where, E' Z is a storage modulus measured in a temperature range of 160°C to 300°C after the crosslinking reaction of the separator for an electricity storage device has progressed in the electricity storage device, and E' z0 is the storage modulus measured in a temperature range of 160° C. to 300° C. before the electricity storage device separator is incorporated into the electricity storage device.} The mixed storage modulus ratio (R E’x ) and / or the following formula (3): R E’’X =E'' Z / E'' Z0(3) {in formula, E'' Z is a loss modulus measured in a temperature range of 160°C to 300°C after the crosslinking reaction of the separator for an electricity storage device has progressed in the electricity storage device, and E'' Z0 is the loss modulus measured in a temperature range of 160°C to 300°C before the electricity storage device separator is incorporated into the electricity storage device.} The mixed loss modulus ratio (R E’’x ) is preferably 1.5 to 20 times, more preferably 3 to 18 times. Z and E' z0 and E'' Z and E'' z0 The storage modulus and loss modulus are the average values ​​of the storage modulus and loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160°C to 300°C. In addition, when the separator is in the form of a laminated film, the storage modulus E' is measured by removing only the polyolefin porous film from the laminated film. Z and E' z0 and loss modulus E'' Z and E'' z0 shall be measured.

[0050] From the viewpoints of forming an amorphous crosslinked structure, achieving both a shutdown function and high-temperature resistance to film rupture, and the like, the separators according to the sixth and seventh embodiments have a viscoelasticity measurement (version 2) described in the examples below, which satisfies the following formula (2): R E’mix =E' / E'0(2) In the formula, E' is the storage modulus of a separator for an electricity storage device having an amorphous crosslinked structure measured at 160°C to 300°C, and E'0 is the storage modulus of an electricity storage device separator that does not have an amorphous crosslinked structure, measured at 160°C to 300°C.} The mixed storage modulus ratio (R E’mix ) and / or the following formula (4): R E’’mix =E'' / E''0(4) In the formula, E″ is a loss modulus measured at 160° C. to 300° C. when the electricity storage device separator has an amorphous crosslinked structure, and E''0 is the loss modulus of the electricity storage device separator not having an amorphous crosslinked structure, measured at 160°C to 300°C.} The mixed loss modulus ratio (R E’’mix ) is preferably 1.5 to 20 times, more preferably 3 to 19 times, and further preferably 5 to 18 times. E' and E'0, and E'' and E''0 are the average values ​​of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160°C to 300°C. When the separator is in the form of a laminated film, the storage modulus E' and E'0 and the loss modulus E'' and E''0 are measured by removing only the polyolefin porous film from the laminated film.

[0051] <Eighth embodiment> Viscoelastic behavior (viscoelasticity measurements explained in the Examples version 3) The separator according to the eighth embodiment is made of a polyolefin microporous film, and in the viscoelasticity measurement (version 3) described in the examples, the separator has a minimum storage modulus (E') of 0.01 to 0.15 mm (E' min ) is 1.0MPa to 10MPa, and the maximum value of E' (E' max ) is 100MPa to 10,000MPa, and / or the minimum value of the loss modulus (E'') is min ) is 0.1MPa to 10MPa, and the maximum value of E'' (E'' max ) is 10MPa to 10,000MPa. 1.0MPa≦E' min ≦10MPa and 100MPa≦E' max ≦10,000MPa and / or 0.1MPa≦E'' min ≦10MPa and 10MPa≦E'' maxIf the pressure is in the range of 1.1 MPa or less, E' will not only tend to achieve both the shutdown function and high-temperature membrane rupture resistance of the separator, but also avoid production defects in the manufacturing process of the separator or the electricity storage device, and achieve stability and safety of the electricity storage device. min ≦9.0MPa and / or ≦150MPa E' max ≦9,500MPa is preferable, and 1.2MPa≦E' min ≦8.0MPa and / or 233MPa≦E' max ≦9,000 MPa is more preferable. Also, 0.2 MPa ≦ E'' min ≦9.0MPa and / or 56MPa≦E'' max ≦9,000MPa is preferable, and 0.4MPa≦E'' min ≦8.0MPa and / or 74MPa≦E'' max It is more preferable that the pressure is ≦8,000 MPa.

[0052] In the solid viscoelasticity measurement (version 3), the average E' (E' ave ) is preferably 1.0 MPa to 12 MPa, more preferably 1.2 MPa to 10 MPa, even more preferably 1.8 MPa to 8.2 MPa, and / or the average E'' (E'' ave ) is preferably 0.5 MPa to 10 MPa, more preferably 0.8 MPa to 8.2 MPa or 0.9 MPa to 3.2 MPa. When E' and / or E'' are within the above numerical ranges at temperatures from the membrane softening transition temperature to the membrane rupture temperature, the cycle stability and safety of an electricity storage device including the separator tend to be improved.

[0053] In terms of achieving both a shutdown function and high-temperature membrane rupture resistance in solid viscoelasticity measurement (version 3), the membrane softening transition temperature of the separator made of a polyolefin microporous membrane is preferably 140° C. to 150° C., more preferably 141° C. to 149° C. or 146° C. to 149° C., and / or the membrane rupture temperature is preferably 180° C. or higher, more preferably 190° C. or higher, 200° C. or higher, 210° C. or higher, 220° C. or higher, 230° C. or higher, or 240° C. or higher, and even more preferably 250° C. or higher. The upper limit of the membrane rupture temperature is not limited, and it is understood in this technical field that the membrane rupture phenomenon may occur even at a temperature higher than 250° C.

[0054] The conditions for measuring E' and E'' in the solid viscoelasticity measurement (version 3) of the separator are described in the Examples. When the separator is in the form of a laminated film, only the polyolefin microporous film is removed from the laminated film, and E' and E'' of the removed polyolefin microporous film are measured. When the thickness of a single polyolefin microporous film is less than 200 μm, dynamic viscoelasticity measurement (version 3) is performed by stacking multiple polyolefin microporous films or folding a single polyolefin microporous film so that the total thickness is within the range of 200 μm to 400 μm.

[0055] From the viewpoint of achieving both a shutdown function at a relatively low temperature and membrane rupture resistance at a relatively high temperature and improving the cycle characteristics and safety of the electricity storage device, the separator according to the first to eighth embodiments can include a microporous membrane and an inorganic porous layer containing inorganic particles and a resin binder arranged on at least one surface of the microporous membrane. The separator can be in a state in which the microporous membrane is used as a substrate and the substrate and the inorganic coating layer are combined.

[0056] <Ninth embodiment> The separator according to the ninth embodiment comprises: A microporous membrane comprising a silane-modified polyolefin; an inorganic porous layer comprising inorganic particles and a resin binder disposed on at least one surface of the microporous membrane; The separator according to the ninth embodiment may include layers other than the microporous membrane and the inorganic porous layer, if desired.

[0057] In the ninth embodiment, the combination of a microporous film containing a silane-modified polyolefin and an inorganic porous layer tends to achieve both a shutdown function at temperatures lower than 150° C. and film rupture resistance at relatively high temperatures, and also improves the cycle characteristics and nail penetration safety of the battery of the electricity storage device. Since the silane-modified polyolefin in the microporous film is silane crosslinkable, the viscosity of the resin in the microporous film may increase when silane crosslinking occurs. Therefore, when a compressive force is applied between the multiple electrodes at an abnormally high temperature of the electricity storage device containing the separator according to the ninth embodiment, it is presumed that the crosslinked high-viscosity resin is unlikely to flow into the inorganic layer (i.e., is unlikely to be integrated), and sufficient clearance between the electrodes can be secured, thereby suppressing battery short-circuiting.

[0058] When the separator according to the ninth embodiment comes into contact with the electrolyte, it is preferable that the silane crosslinking reaction of the silane-modified polyolefin is initiated. More preferably, the silane crosslinking reaction is observed when the separator comes into contact with the electrolyte, regardless of whether the silane crosslinking reaction is initiated first, occurs sequentially, or occurs continuously when the separator comes into contact with the electrolyte. The silane crosslinking reaction of the silane-modified polyolefin that occurs when the separator comes into contact with the electrolyte not only controls the crosslinking timing of the separator and avoids production defects in the separator manufacturing process, but also achieves safety and high output in the manufacturing process of the electricity storage device. In addition, by contacting the separator with the electrolyte, a crosslinking reaction other than the silane crosslinking reaction can be initiated.

[0059] In the separator according to the ninth embodiment, when the viscoelasticity measurement (version 1) described in the examples is performed after removing the inorganic porous layer from the separator, the separator has a viscoelasticity represented by the following formula (1A): R △E’ =E' S / E' j (1A) {where, E' j is the storage modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E' S is the storage modulus measured at 160°C to 220°C of the separator for an electricity storage device after the silane-modified polyolefin has undergone a crosslinking reaction.} The storage modulus change ratio (R △E’ ) is preferably 1.5 to 20 times, and / or the following formula (1B): R △E’’ =E'' S / E'' j (1B) {in formula, E'' j is the loss modulus of the separator for an electricity storage device measured at 160°C to 220°C before the silane-modified polyolefin undergoes a crosslinking reaction, and E'' S is the loss modulus measured at 160°C to 220°C of the separator for an electricity storage device after the silane-modified polyolefin has undergone a crosslinking reaction.} The loss modulus change ratio (R △E The storage elastic modulus change ratio (R △E’ ) and / or the loss modulus change ratio (R △E’’ By setting the storage modulus change ratio (R ΔE’ ) and / or the loss modulus change ratio (R ΔE’’ ) is more preferably 2 to 18 times. j and E' S and E'' j and E'' S are the average values ​​of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160 to 220° C. In addition, when the separator is in the form of a laminated film or a composite film of a microporous film and an inorganic porous layer, only the silane-modified polyolefin-containing microporous film is removed from the laminated film or composite film, and the storage modulus E' of the silane-modified polyolefin-containing microporous film is measured. j and E' Sand loss modulus E'' j and E'' S shall be measured.

[0060] In the separator according to the ninth embodiment, when the viscoelasticity measurement (version 1) described in the examples is performed after removing the inorganic porous layer from the separator, the separator has a viscoelasticity represented by the following formula (2A): R E’mix =E' / E'0(2A) {In the formula, E' is the storage modulus of the electricity storage device separator measured at 160°C to 220°C, and E'0 is the storage modulus of the electricity storage device separator that does not contain the silane-modified polyolefin measured at 160°C to 220°C.} The mixed storage modulus ratio (R E’mix ) is preferably 1.5 to 20 times, and / or the following formula (2B): R E’’mix =E'' / E''0(2B) {In the formula, E'' is the loss modulus of the electricity storage device separator measured at 160°C to 220°C, and E''0 is the loss modulus of the electricity storage device separator that does not contain the silane-modified polyolefin measured at 160°C to 220°C.} The mixed loss modulus ratio (R E’’mix The mixed storage modulus ratio (R E’mix ) and / or the blend loss modulus ratio (R E’’mix By having the mixed storage modulus ratio (R E’mix ) and / or the blend loss modulus ratio (R E’’mix) is more preferably 2 to 18 times. E' and E'0, and E'' and E''0 are respectively the average values ​​of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is 160 to 220°C. When the separator is in the form of a laminated film or a composite film of a microporous film and an inorganic porous layer, the storage modulus E' and E'0 and the loss modulus E'' and E''0 of the silane-modified polyolefin-containing microporous film are measured by removing only the silane-modified polyolefin-containing microporous film from the laminated film or composite film. The separator for an electricity storage device that does not contain silane-modified polyolefin will be described in detail in the section on examples.

[0061] From the viewpoint of achieving both the shutdown function and high-temperature membrane rupture resistance, the separator according to the ninth embodiment preferably has a transition temperature between the rubber-like flat region and the crystalline melting flow region in the temperature change of its storage modulus of 135° C. to 150° C. The transition temperature between the rubber-like flat region and the crystalline melting flow region is preferably 137° C. to 147° C., more preferably 140° C. to 145° C., and even more preferably 140° C. to 143° C. When the separator is in the form of a laminated film or a composite film of a microporous film and an inorganic porous layer, only the silane-modified polyolefin-containing microporous film is removed from the laminate or composite film, and the transition temperature of the silane-modified polyolefin-containing microporous film is measured.

[0062] <Tenth embodiment> A separator for an electricity storage device according to a tenth embodiment (hereinafter, simply referred to as "separator") includes a first porous layer (A layer) containing silane-modified polyolefin and capable of forming a crosslinked structure, and a second porous layer (B layer) containing inorganic particles. Each of the A layer and the B layer is a single layer or multiple layers. The B layer is formed on only one side or both sides of the A layer. In LIBs, a typical example of an energy storage device, lithium (Li) ions shuttle between the positive and negative electrodes. By disposing a separator containing layers A and B between the positive and negative electrodes, it is possible to move Li ions between the positive and negative electrodes at a relatively high speed while avoiding contact between the electrodes.

[0063] (Thickness ratio) The A layer functions as a crosslinked microporous membrane, and the B layer functions as an inorganic porous layer formed on the microporous membrane. Here, the ratio (TA / TB) of the thickness (TA) of the A layer to the thickness (TB) of the B layer is preferably 0.22 or more and 14 or less. If the ratio (TA / TB) is 0.22 or more, the proportion of the A layer in the separator can be sufficiently ensured, and the A layer can exert its function. On the other hand, if the ratio (TA / TB) is 14 or less, the proportion of the B layer in the separator can be sufficiently ensured, and the B layer can exert its function.

[0064] By making the A layer and the B layer have specific structures and further setting the ratio (TA / TB) within the above range, a separator can be provided that can improve the cycle characteristics and safety of an electricity storage device. Such a separator can be suitably used as a constituent material of LIBs for mobile device or vehicle use, for example. From the viewpoint of the above-mentioned effects, the ratio (TA / TB) is preferably 0.8 or more, more preferably 1.0 or more, while the ratio (TA / TB) is preferably 5.5 or less, more preferably 3.2 or less.

[0065] The ratio (TA / TB) may be set to, for example, less than 2.5, 2.0 or less, or 1.0 or less. In this case, the thickness (TA) of layer A is less than 2.5 times the thickness (TB) of layer B and is smaller than the thickness (TB) of layer B, making it easier to reduce the thickness of layer A, and therefore the thickness of the separator.

[0066] The total thickness (TA+TB) of the A layer and the B layer is preferably 3.0 μm or more and 22 μm or less. If the total thickness (TA+TB) is 3.0 μm or more, the membrane strength of the separator tends to be improved. On the other hand, if the total thickness (TA+TB) is 22 μm or less, the ion permeability of the separator tends to be improved. From the viewpoint of the above-mentioned effects, the total thickness (TA+TB) is more preferably 3.5 μm or more, and further preferably 4.0 μm or more. On the other hand, the total thickness (TA+TB) is more preferably 20 μm or less, and further preferably 18 μm or less.

[0067] The total thickness (TA+TB) may be set to, for example, less than 11 μm, 10 μm or less, or 8 μm or less. Even with such a thin separator, within the scope of the present invention, the cycle characteristics and safety of the electricity storage device can be improved.

[0068] The ratio (TA / TB) and the total thickness (TA+TB) can be measured by the method described in the Examples section, and can be controlled by adjusting the thickness (TA) and / or the thickness (TB). The A layer and the B layer will be described later.

[0069] (Shutdown temperature and meltdown temperature) For layer A, it is preferable that the shutdown temperature (sometimes referred to as fuse temperature) is 130°C to 160°C and the meltdown temperature (sometimes referred to as membrane rupture temperature) is 200°C or higher, measured based on electrical resistance under a pressure of 0.1 MPa to 10.0 MPa (preferably under a pressure of 10 MPa).

[0070] If the shutdown temperature is 130° C. or higher, unnecessary operation of the shutdown function during normal reaction of the power storage device can be avoided, and sufficient output characteristics of the power storage device can be ensured. On the other hand, if the shutdown temperature is 160° C. or lower, the shutdown function can be suitably exerted during abnormal reaction of the power storage device. In addition, if the shutdown temperature is 200°C or higher, the abnormal reaction in the electricity storage device can be stopped before the temperature reaches an ultra-high temperature range, and melting and rupture of the separator can be prevented in the event of an abnormal reaction in the electricity storage device.

[0071] That is, by satisfying the above-mentioned conditions for the shutdown temperature and the meltdown temperature, a separator can be realized that can provide an electricity storage device with excellent heat resistance, pore blocking characteristics (shutdown function), and melting and film rupture characteristics (meltdown function), and the separator itself can ensure mechanical characteristics, ion permeability, etc. Therefore, by providing a separator whose shutdown temperature and meltdown temperature satisfy the above-mentioned conditions, the electricity storage device can improve its cycle characteristics and safety. From the viewpoint of the above-mentioned effects, the shutdown temperature is preferably higher than 130° C., more preferably 135° C. or higher, and even more preferably 136° C. or higher. On the other hand, the shutdown temperature is preferably 150° C. or lower, more preferably 148° C. or lower, and even more preferably 146° C. or lower. Similarly, from the viewpoint of the above effects, the meltdown temperature is preferably 175° C. or higher, more preferably 178° C. or higher, and even more preferably 180° C. or higher. On the other hand, the meltdown temperature is preferably 230° C. or lower, more preferably 225° C. or lower, and even more preferably 220° C. or lower. Regarding the meltdown temperature, even if it becomes impossible to measure accurately above 200°C, as long as the temperature is 200°C or higher, the above requirement of "meltdown temperature is 200°C or higher" is met.

[0072] In this specification, the terms "shutdown temperature" and "meltdown temperature" refer to values ​​obtained when measured based on electrical resistance under the above-mentioned pressure. That is, the above-mentioned pressure is applied to a laminate including a positive electrode, a separator, and a negative electrode, and the temperature of the laminate is raised, and the shutdown temperature and meltdown temperature are derived based on the AC resistance (AC resistance between electrodes) that increases with the pressure. In the tenth embodiment, the temperature at which the AC resistance exceeds a predetermined reference value (e.g., 1000Ω) for the first time is set as the shutdown temperature, and the temperature at which the AC resistance that exceeded the above-mentioned reference value is further heated and then falls to the above-mentioned reference value (e.g., 1000Ω) or less is set as the meltdown temperature. A hydraulic jack may be used to apply pressure to the laminate, but this is not limiting, and any other known pressurizing means may be used. An aluminum heater may be used to heat the laminate, but this is not limiting, and any other known heating means may be used. The shutdown temperature and meltdown temperature can be measured by the methods described in the Examples section, and can be controlled by adjusting the configuration or production method of the A layer.

[0073] (Heat shrinkage rate at 150℃) In the A layer, the heat shrinkage rate (T2) at 150°C after the formation of the crosslinked structure is 0.02 to 0.91 times the heat shrinkage rate (T1) at 150°C before the formation of the crosslinked structure. In other words, the ratio (T2 / T1) of the heat shrinkage rate (T2) at 150°C after the formation of the crosslinked structure to the heat shrinkage rate (T1) at 150°C before the formation of the crosslinked structure is 0.02 to 0.91. The heat shrinkage rate used here is the larger value of the heat shrinkage rate in the machine direction (MD) of the A layer and the heat shrinkage rate in the transverse direction (TD) of the A layer. Because layer A is capable of forming a cross-linked structure using silane-modified polyolefin, it becomes possible to focus on the change in the thermal shrinkage rate before and after the cross-linking.

[0074] If the ratio (T2 / T1) is 0.02 or more, the occurrence of a short circuit can be effectively suppressed, and thus the temperature rise of the entire electricity storage device and the smoke and even fire that may occur as a result can be reliably prevented. On the other hand, if the ratio (T2 / T1) is 0.91 or less, it can be determined that the crosslinking reaction in layer A has been sufficiently advanced. In other words, if the ratio (T2 / T1) is within the above range, it is possible to provide a separator for an electricity storage device that can improve the cycle characteristics and safety of the electricity storage device. Therefore, from the viewpoint of the above-mentioned effects, the ratio (T2 / T1) is preferably 0.03 or more, more preferably 0.05 or more, and even more preferably 0.07 or more. On the other hand, the ratio (T2 / T1) is preferably 0.7 or less, more preferably 0.5 or less, and even more preferably 0.4 or less.

[0075] The heat shrinkage rate (T1) at 150° C. before the formation of a crosslinked structure is preferably 70% or less, and more preferably 60% or less. The heat shrinkage rate (T2) at 150°C after the formation of the crosslinked structure is preferably 60% or less, more preferably 50% or less. However, since the formation of the crosslinked structure tends to reduce the heat shrinkage rate compared to before the formation of the crosslinked structure, the heat shrinkage rate (T2) is generally smaller than the heat shrinkage rate (T1).

[0076] The heat shrinkage rate at 150° C. can be measured by the method described in the Examples section, and can be controlled by adjusting the configuration or production method of the A layer.

[0077] The separators according to the above-described embodiments are interchangeable or can be combined with each other. The separator according to the ninth or tenth embodiment described above may include layers other than the microporous membrane and the inorganic porous layer, if desired. The components of the separators according to the first to tenth embodiments are described below.

[0078] [Microporous membrane] The microporous membrane can be formed of a polyolefin or a modified polyolefin.

[0079] The microporous membrane contains a silane-modified polyolefin and may contain other polyolefins as desired. Due to the silane crosslinking properties of the silane-modified polyolefin, the microporous membrane is capable of undergoing a crosslinking reaction during the separator manufacturing process.

[0080] The polyolefin contained in the microporous membrane is not particularly limited, and examples thereof include homopolymers of ethylene or propylene, or copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among these, high density polyethylene (homopolymer) or low density polyethylene is preferred, and high density polyethylene (homopolymer) is more preferred, from the viewpoint that the pores are not blocked and heat setting (sometimes abbreviated as "HS") can be performed at a higher temperature. The polyolefin may be used alone or in combination of two or more kinds.

[0081] From the viewpoint of resistance to oxidation-reduction degradation and dense and uniform porous structure, the microporous membrane is preferably produced by using both silane-modified polyolefin and ultra-high molecular weight polyethylene (UHMWPE) as raw materials. In general, it is known that the weight average molecular weight of ultra-high molecular weight polyethylene (UHMWPE) is 1,000,000 or more. More preferably, in the production of the microporous membrane or separator, the weight ratio of the silane-modified polyolefin to UHMWPE (weight of silane-modified polyolefin / weight of UHMWPE) is 0.05 / 0.95 to 0.40 / 0.60.

[0082] The content of polyolefin contained in the microporous membrane is preferably 50% by weight or more and 100% by weight or less, preferably 70% by weight or more and 100% by weight or less, and preferably 80% by weight or more and 100% by weight or less. In addition, the microporous membrane preferably contains polyolefin having a weight average molecular weight of 100,000 or more and less than 1,000,000 (preferably 40% by weight or more, more preferably 80% by weight or more with respect to the total polyolefin). The weight average molecular weight of the polyolefin is more preferably 120,000 or more and less than 950,000, and even more preferably 130,000 or more and less than 930,000. By using polyolefin having a weight average molecular weight of 100,000 or more and less than 1,000,000, the contraction of the polymer is relaxed early in the heating test of the electric storage device, and the safety tends to be easily maintained, especially in the heating safety test. By adjusting the weight-average molecular weight of the microporous membrane to less than 1,000,000, it is possible to suppress molding defects (membrane patterns) during extrusion called melt fracture. On the other hand, by adjusting the weight-average molecular weight of the microporous membrane to 100,000 or more, it is possible to suppress the transfer of dents when the microporous membrane is wound around a core (winding core).

[0083] The microporous membrane has a viscosity average molecular weight at the time of removing the inorganic porous layer and at the time of uncrosslinking treatment, from the viewpoint of preventing the generation of polymer powder due to frictional shear during roll transport of the separator, of preferably 100,000 or more and 1,200,000 or less, and more preferably 150,000 or more and 800,000 or less.

[0084] The thickness of the microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more, 4.0 μm or more, or 4.5 μm or more. When the thickness of the microporous membrane is 1.0 μm or more, the membrane strength tends to be further improved. In addition, the thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less, 22 μm or less, or 19 μm or less. When the thickness of the microporous membrane is 500 μm or less, the ion permeability tends to be further improved. The thickness of the microporous membrane can be measured by the method described in the Examples.

[0085] When the microporous membrane is a separator used in recent relatively high-capacity lithium ion secondary batteries, the membrane thickness is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less. In this case, the membrane thickness of 25 μm or less tends to further improve permeability. In this case, the lower limit of the membrane thickness may be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, 6.0 μm or more, or 7.5 μm or more.

[0086] From the viewpoint of high-temperature film rupture resistance of the separator for the electric storage device and safety of the electric storage device, the microporous film as the separator preferably has a melting and film rupture temperature of 180°C to 220°C, more preferably 180°C to 200°C, when measured by thermomechanical analysis (TMA). In general, when the electric storage device generates heat due to an unexpected runaway reaction, the separator for the electric storage device made of polyolefin fuses at a low temperature (for example, 150°C or lower), and the movement of Li ions and the accompanying discharge inside or outside the electric storage device are stopped early. Thereafter, the entire electric storage device is cooled by the outside air or refrigerant of the electric storage device, and it is expected that the ignition of the electrolyte or the decomposition and exothermic reaction of the electrolyte can be prevented, and safety can be ensured. However, the runaway reaction occurring in the electric storage device continues to generate heat without being stopped by the fuse of the separator, and the separator melts and ruptures, making it impossible to ensure the safety of the device. Therefore, it is important that the separator does not melt and break down until the entire storage device is sufficiently cooled. Also, if the temperature rises to an ultra-high temperature range of 220°C or more, the decomposition reaction of the electrolyte or electrolyte will proceed vigorously, causing the decomposition products to corrode the electrodes, generating heat and resulting in an explosion. In that case, the separator will melt and break down, seeping into both electrodes and coating the active material, preventing the corrosion reaction.

[0087] [First porous layer (A layer)] The A layer contains a silane-modified polyolefin and can form a crosslinked structure. In order to ensure resistance to oxidation and reduction and to ensure a dense and uniform porous structure, the A layer preferably further contains polyethylene as a polyolefin different from the silane-modified polyolefin. The A layer may contain components other than the silane-modified polyolefin and polyethylene.

[0088] Examples of the polyolefin constituting the silane-modified polyolefin in the A layer include homopolymers of ethylene or propylene; copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among them, the polyolefin is preferably a homopolymer of ethylene (polyethylene), more preferably a high-density polyethylene and / or a low-density polyethylene, and even more preferably a high-density polyethylene, from the viewpoint of enabling heat fixation at a higher temperature while avoiding clogging of pores. The polyolefin may be used alone or in combination of two or more kinds.

[0089] Layer A may contain a polymer (other polymer) that does not fall under either the silane-modified polyolefin or polyethylene, as long as the effect of the present invention is not excessively hindered. The weight average molecular weight of the entire layer A is preferably 100,000 or more and 1,200,000 or less, and more preferably 150,000 or more and 800,000 or less.

[0090] (Thickness of layer A) The thickness (TA) of the A layer is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more. If the thickness (TA) is 1 μm or more, the membrane strength tends to be improved. On the other hand, the thickness (TA) is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less. If the thickness (TA) is 500 μm or less, the ion permeability tends to be improved. The thickness (TA) may be set to, for example, 1.00 μm or more, 2.00 μm or more, or 3.00 μm or more.

[0091] When the separator is a LIB separator, the thickness (TA) is preferably less than 22 μm, more preferably 21 μm or less, and even more preferably 20.5 μm or less. When the separator is a LIB separator, the upper limit of the thickness (TA) may be set to less than 13 μm or 8.5 μm or less. If the thickness (TA) is 25 μm or less, the permeability tends to be further improved. The thickness (TA) may be set to, for example, less than 22.00 μm, 21.00 μm or less, 20.00 μm or less, less than 13.00 μm, or 8.50 or less. The lower limit of the thickness (TA) may be the same as above. The thickness (TA) can be measured by the method described in the Examples section, and can be controlled by changing the stretch ratio of the A layer, or the like.

[0092] When the layer A is a single layer, the thickness of the layer A is treated as the thickness (TA). When the layer A is a multi-layer, the total thickness of the multi-layer A is treated as the thickness (TA).

[0093] (Break temperature of layer A) The film rupture temperature of layer A, as measured by thermomechanical analysis (TMA), is preferably 180° C. or higher and 220° C. or lower. Even if the energy storage device abnormally heats up due to an unexpected runaway reaction, it is expected that the separator's shutdown function will stop the movement of Li ions and the associated discharge inside or outside the energy storage device. It is then expected that the entire energy storage device will be cooled by the refrigerant, ensuring safety. On the other hand, by keeping the film rupture temperature within the above range, even if the entire energy storage device is not sufficiently cooled or if it should reach an ultra-high temperature range, the separator will melt and rupture, seeping into both electrodes and coating the active material, which makes it easier to suppress further heat generation. The film rupture temperature can be measured by the method described in the Examples section, and can also be controlled by changing the stretching temperature and / or the stretching ratio in the production process.

[0094] (Porosity of microporous membrane or A layer) The porosity of the microporous membrane or the A layer is preferably 20% or more, more preferably 25% or more, even more preferably 28% or more, 30% or more, 32% or more, or 35% or more. If the porosity is 20% or more, the ability to follow the rapid movement of Li ions tends to be improved. On the other hand, the porosity is preferably 90% or less, more preferably 80% or less, and even more preferably 60% or less. If the porosity is 90% or less, the film strength tends to be improved and self-discharge tends to be suppressed. The porosity can be measured by the method described in the Examples section, and can also be controlled by changing the stretching temperature and / or the stretching ratio in the production process.

[0095] (Air permeability of microporous membrane or layer A) The air permeability of the microporous membrane or layer A is preferably 1 sec / 100 cm 3 More than 50 seconds / 100cm 3 More preferably, 55 seconds / 100 cm 3 More preferably, the air permeability is 1 sec / 100 cm. 3 If the thickness is more than 400 s / 100 cm, the balance between the membrane thickness, the porosity, and the average pore size tends to be improved. On the other hand, the air permeability is preferably 400 s / 100 cm 3 Less than 300 seconds / 100 cm 3 , and more preferably 270 sec / 100 cm 3 Air permeability is 400 sec / 100 cm 3 If it is equal to or less than this, the ion permeability tends to be further improved. The air permeability can be measured by the method described in the Examples section, and can also be controlled by changing the stretching temperature and / or the stretching ratio in the production process.

[0096] (Puncture strength of microporous membrane or layer A) The puncture strength of the microporous membrane or the A layer is preferably 200 gf / 20 μm or more, more preferably 300 gf / 20 μm or more. If the puncture strength is 200 gf / 20 μm or more, even if the active material falls off when the separator and the electrode laminate is wound, it is easy to suppress the membrane from being broken by the fallen active material. In addition, it is easy to reduce the possibility of short circuit due to the expansion and contraction of the electrode accompanying charging and discharging. On the other hand, the puncture strength is preferably 4000 gf / 20 μm or less, more preferably 3800 gf / 20 μm or less. If the puncture strength is 3500 gf / 20 μm or less, it is easy to reduce thermal contraction during heating. The pin puncture strength can be measured by the method described in the Examples section, and can also be controlled by changing the stretching temperature and / or the stretching ratio in the production process.

[0097] [Tensile strength of microporous membrane or layer A] The tensile strength of the microporous membrane or layer A is preferably 1000 kgf / cm in both MD (the longitudinal direction of the membrane or layer A, the machine direction or flow direction) and TD (the direction perpendicular to MD, the width direction of the membrane or layer A). 2 More preferably, it is 1050 kgf / cm 2 More preferably, it is 1100 kgf / cm 2 More than 1000kgf / cm 2 By being equal to or greater than this, there is a tendency that slitting or breakage during winding of the electricity storage device is more suppressed, or that short circuits due to foreign matter or the like in the electricity storage device are more suppressed. On the other hand, the tensile strength is preferably 5000 kgf / cm 2 More preferably, it is 4500 kgf / cm or less. 2 More preferably, it is 4000 kgf / cm or less. 2 Tensile strength is 5000kgf / cm or less. 2 or less, the microporous membrane or layer A will relax early during the heat test, weakening the contractile force, and as a result, safety will tend to be increased.

[0098] [Tensile modulus of microporous membrane or layer A] The tensile modulus of the microporous membrane or the A layer is preferably 120 N / cm or less, more preferably 100 N / cm or less, and even more preferably 90 N / cm or less in both MD and TD. A tensile modulus of 120 N / cm or less indicates that the separator for a lithium ion secondary battery is not extremely oriented, and in a heating test or the like, for example, when a blocking agent such as polyethylene melts and shrinks, the polyethylene etc. causes stress relaxation early, which suppresses the shrinkage of the separator in the battery and tends to easily prevent short circuits between electrodes (i.e., the safety of the separator during heating can be improved). Such a low tensile modulus is easily achieved by including polyethylene having a weight average molecular weight of 500,000 or less in the polyolefin forming the microporous membrane or the A layer. On the other hand, the lower limit of the tensile modulus is not particularly limited, but is preferably 10 N / cm or more, more preferably 30 N / cm or more, and even more preferably 50 N / cm or more. The tensile modulus can be appropriately adjusted by adjusting the degree of stretching in the production process and, if necessary, by relaxing after stretching.

[0099] <Polyolefin> The polyolefin is not particularly limited, but examples thereof include homopolymers of ethylene or propylene, and copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among these, high density polyethylene or low density polyethylene is preferred, and high density polyethylene is more preferred, from the viewpoint that heat setting (sometimes abbreviated as "HS") can be performed at a higher temperature without blocking pores. The polyolefin may be used alone or in combination of two or more kinds.

[0100] The separator preferably contains a polyolefin having a weight average molecular weight (Mw) of less than 2,000,000, more preferably 40% by mass or more, and even more preferably 80% by mass or more, of the polyolefins having a Mw of less than 2,000,000. By using a polyolefin having a Mw of less than 2,000,000, the polymer shrinkage is relaxed early in the heating test of the power storage device, and the safety tends to be easily maintained, especially in the heating safety test. In addition, when a polyolefin having a Mw of less than 2,000,000 is used, the elastic modulus in the thickness direction of the obtained microporous film tends to be smaller than that when a polyolefin having a Mw of 1,000,000 or more is used, and therefore a microporous film to which the unevenness of the core is relatively easily transferred is obtained. The weight average molecular weight of the entire polyolefin microporous film constituting the separator is preferably 100,000 or more and 2,000,000 or less, and more preferably 150,000 or more and 1,500,000 or less.

[0101] (Polyolefins having one or more functional groups) From the viewpoints of forming a crosslinked structure, resistance to oxidation-reduction deterioration, and dense and uniform porous structure, the separator preferably contains a functional group-modified polyolefin or a polyolefin copolymerized with a monomer having a functional group as a polyolefin having one or more functional groups. In this specification, the functional group-modified polyolefin refers to a polyolefin to which a functional group is bonded after production. The functional group is bonded to the polyolefin skeleton or can be introduced into a comonomer, and is preferably involved in selective crosslinking of the amorphous part of the polyolefin, and can be at least one selected from the group consisting of a carboxyl group, a hydroxyl group, a carbonyl group, a polymerizable unsaturated hydrocarbon group, an isocyanate group, an epoxy group, a silanol group, a hydrazide group, a carbodiimide group, an oxazoline group, an acetoacetyl group, an aziridine group, an ester group, an active ester group, a carbonate group, an azide group, a linear or cyclic heteroatom-containing hydrocarbon group, an amino group, a sulfhydryl group, a metal chelate group, and a halogen-containing group.

[0102] From the viewpoints of the separator's strength, ion permeability, resistance to oxidation-reduction degradation, and dense and uniform porous structure, it is preferable that the separator contains both a polyolefin having one or more functional groups and a silane-unmodified polyethylene. When a polyolefin having one or more functional groups and a silane-unmodified polyethylene are used in combination, the mass ratio of the polyolefin having one or more functional groups to the silane-unmodified polyethylene in the separator (mass of the polyolefin having one or more functional groups / mass of the silane-unmodified polyethylene) is preferably 0.05 / 0.95 to 0.80 / 0.20.

[0103] (Crosslinked structure) The crosslinked structure of the separator contributes to achieving both the shutdown function and high-temperature rupture resistance of the separator and to the safety of the power storage device, and is preferably formed in the amorphous portion of the polyolefin contained in the separator. The crosslinked structure can be formed, for example, by a reaction via a covalent bond, a hydrogen bond, or a coordinate bond. Among these, the reaction via a covalent bond includes the following reactions (I) to (IV): (I) Condensation reaction of multiple identical functional groups (II) Reactions between multiple different functional groups (III) Chain condensation reaction of functional groups with electrolytes (IV) Chain condensation reaction of functional groups with additives It is preferable that the at least one selected from the group consisting of: The reaction via a coordinate bond is shown in the following reaction (V): (V) A reaction in which multiple identical functional groups crosslink through coordinate bonds with eluted metal ions It is preferable that:

[0104] Reaction (I) A schematic scheme and specific examples of reaction (I) are shown below, where the first functional group of the separator is A. [ka] {In the formula, R is an alkyl group or heteroalkyl group having 1 to 20 carbon atoms which may have a substituent.}

[0105] When the functional group A for the reaction (I) is a silanol group, the polyolefin contained in the separator is preferably silane-graft modified. The silane-graft modified polyolefin has a structure in which the main chain is a polyolefin and the main chain has an alkoxysilyl as a graft. Examples of the alkoxide substituted with the alkoxysilyl include methoxide, ethoxide, and butoxide. For example, in the above formula, R can be methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl. In addition, the main chain and the graft are connected by a covalent bond, and examples of the structure include alkyl, ether, glycol, and ester. Considering the manufacturing process of the separator according to this embodiment, the silane-graft modified polyolefin preferably has a silicon to carbon ratio (Si / C) of 0.2 to 1.8%, and more preferably 0.5 to 1.7%, before the crosslinking treatment step.

[0106] The preferred silane-grafted polyolefin has a density of 0.90 to 0.96 g / cm 3 and the melt flow rate (MFR) at 190°C is 0.2 to 5 g / min. From the viewpoint of suppressing the generation of resin aggregates in the separator manufacturing process and maintaining silane crosslinking until contact with the electrolyte, it is preferable that the silane-grafted modified polyolefin is not a masterbatch resin containing a dehydration condensation catalyst. It is known that the dehydration condensation catalyst also functions as a catalyst for the siloxane bond formation reaction of an alkoxysilyl group-containing resin. In this specification, a compound obtained by adding a dehydration condensation catalyst (e.g., an organometallic catalyst) to an alkoxysilyl group-containing resin or other kneaded resin in advance during a continuous process of resin kneading using an extruder and compounding the resulting material is called a masterbatch resin.

[0107] Reaction (II) A schematic scheme and a specific example of reaction (II) in which the first functional group of the separator is A and the second functional group is B are shown below. [ka] [ka] [ka] [ka]

[0108] Reactions (I) and (II) can be catalyzed, for example, catalytically promoted, by chemicals within the electrical storage device in which the separator is incorporated. The chemicals can be, for example, any of the electrolytes, electrolytic solutions, electrode active materials, additives, or decomposition products thereof contained in the electrical storage device.

[0109] Reaction (III) A schematic scheme and a specific example of reaction (III) are shown below, where the first functional group of the separator is A and the electrolyte is Sol. [ka] [ka] [ka] [ka]

[0110] Reaction (IV) A schematic scheme of reaction (IV) is shown below, where the first functional group of the separator is A, the second functional group that is optionally incorporated is B, and the additive is Add. [ka]

[0111] From the viewpoint of forming a covalent bond represented by a dotted line in the above scheme, the reaction (IV) is preferably a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction between a compound Rx constituting the separator and a compound Ry constituting the additive (Add). The compound Rx may be a polyolefin, such as polyethylene or polypropylene, contained in the separator, and preferably the polyolefin is modified with a functional group x, such as at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH, and -SH.

[0112] Since the multiple compounds Rx are crosslinked via the compound Ry as an additive, it is preferred that the compound Ry has two or more linking reaction units y1. The multiple linking reaction units y1 may be any structure or group, may be substituted or unsubstituted, may contain heteroatoms or inorganic substances, and may be the same or different from each other, as long as they can undergo a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction with the functional group x of the compound Rx. In addition, when the compound Ry has a chain structure, the multiple linking reaction units y1 can each independently be a terminal group, be incorporated into the main chain, or be a side chain or pendant.

[0113] When reaction (IV) is a nucleophilic substitution reaction, the following description will be given by regarding the functional group x of compound Rx as a nucleophilic group and the linking reaction unit y1 of compound Ry as a leaving group, merely as an example. In this embodiment, however, both the functional group x and the linking reaction unit y1 can be a leaving group depending on their nucleophilicity.

[0114] From the viewpoint of the nucleophilic agent, the functional group x of the compound Rx is preferably an oxygen-based nucleophilic group, a nitrogen-based nucleophilic group, or a sulfur-based nucleophilic group. Examples of the oxygen-based nucleophilic group include a hydroxyl group, an alkoxy group, an ether group, and a carboxyl group, among which -OH and -COOH are preferred. Examples of the nitrogen-based nucleophilic group include an ammonium group, a primary amino group, and a secondary amino group, among which -NH2 and -NH- are preferred. Examples of the sulfur-based nucleophilic group include, for example, -SH and a thioether group, among which -SH is preferred.

[0115] When the reaction (IV) is a nucleophilic substitution reaction, the linking reaction unit y1 of the compound Ry from the viewpoint of the leaving group may be an alkylsulfonyl group such as CH3SO2- or CH3CH2SO2-; an arylsulfonyl group (-ArSO2-); a haloalkylsulfonyl group such as CF3SO2- or CCl3SO2-; - -, CH3CH2SO3 - -; arylsulfonate groups (ArSO3 - -);CF3SO3 - -, CCl3SO3 - - and other haloalkylsulfonate groups; and heterocyclic groups are preferred, and these can be used alone or in combination of two or more. Examples of heteroatoms contained in the heterocycle include nitrogen atoms, oxygen atoms, and sulfur atoms, and among these, nitrogen atoms are preferred from the viewpoint of leaving properties. Examples of leaving groups containing a nitrogen atom in the heterocycle include the following formulas (y1-1) to (y1-6): [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} A monovalent group represented by the following formula is preferred.

[0116] In the formulae (y1-1) to (y1-6), X is a hydrogen atom or a monovalent substituent. Examples of the monovalent substituent include an alkyl group, a haloalkyl group, an alkoxyl group, and a halogen atom.

[0117] When the reaction (IV) is a nucleophilic substitution reaction and the compound Ry has a chain structure, the compound Ry has, in addition to the linking reaction unit y1, the following formulae (y2-1) to (y2-6) as the chain unit y2: [ka] {In the formula, m is an integer of 0 to 20, and n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} In addition, when the compound Ry contains a plurality of chain units y2, they may be the same or different, and their arrangement may be block or random.

[0118] In formula (y2-1), m is an integer of 0 to 20, and from the viewpoint of the crosslinked network, preferably 1 to 18. In formulae (y2-1) to (y2-6), n is an integer of 1 to 20, and from the viewpoint of the crosslinked network, preferably 2 to 19 or 3 to 16. In formulae (y2-5) to (y2-6), X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and from the viewpoint of the stability of the chain structure, preferably a methylene group, an ethylene group, an n-propylene group, an n-butylene group, an n-hexylene group, an n-heptylene group, an n-octylene group, an n-dodecylene group, an o-phenylene group, an m-phenylene group, or a p-phenylene group.

[0119] When the reaction (IV) is a nucleophilic substitution reaction, preferred combinations of the functional group x of the compound Rx and the linking reaction unit y1 and chain unit y2 of the compound Ry are shown in Tables 2 to 4 below.

[0120] [Table 2]

[0121] [Table 3]

[0122] [Table 4]

[0123] As a specific example 1 of the nucleophilic substitution reaction, the functional group x of the polyolefin is -NH2, the linking reaction unit y1 of the additive (compound Ry) is a skeleton derived from succinimide, and the chain unit y2 is -(O-C2H5) nThe reaction scheme for the case where - is shown below. [ka]

[0124] As specific example 2 of a nucleophilic substitution reaction, the reaction scheme is shown below in which the functional groups x of the polyolefin are -SH and -NH2, the linking reaction unit y1 of the additive (compound Ry) is a nitrogen-containing cyclic skeleton, and the chain unit y2 is o-phenylene. [ka]

[0125] When the reaction (IV) is a nucleophilic addition reaction, the functional group x of the compound Rx and the linking reaction unit y1 of the compound Ry can undergo an addition reaction. In the nucleophilic addition reaction, the functional group x of the compound Rx is preferably an oxygen-based nucleophilic group, a nitrogen-based nucleophilic group, or a sulfur-based nucleophilic group. Examples of the oxygen-based nucleophilic group include a hydroxyl group, an alkoxy group, an ether group, and a carboxyl group, among which -OH and -COOH are preferred. Examples of the nitrogen-based nucleophilic group include an ammonium group, a primary amino group, and a secondary amino group, among which -NH2 and -NH- are preferred. Examples of the sulfur-based nucleophilic group include, for example, -SH and a thioether group, among which -SH is preferred.

[0126] In the nucleophilic addition reaction, the linking reaction unit y1 of the compound Ry is represented by the following formulae (Ay1-1) to (Ay1-6): [ka] [ka] [ka] [ka] In the formula, R is a hydrogen atom or a monovalent organic group. [ka] [ka] It is preferable that the alkyl group is at least one selected from the group consisting of groups represented by the following formula:

[0127] In formula (Ay1-4), R is a hydrogen atom or a monovalent organic group, and preferably a hydrogen atom, C 1~20 It is an alkyl group, an alicyclic group, or an aromatic group, and more preferably a hydrogen atom, a methyl group, an ethyl group, a cyclohexyl group, or a phenyl group.

[0128] When reaction (IV) is a nucleophilic addition reaction, preferred combinations of the functional group x of compound Rx and the linking reaction unit y1 of compound Ry are shown in Tables 5 and 6 below.

[0129] [Table 5]

[0130] [Table 6]

[0131] As a specific example of a nucleophilic addition reaction, the reaction scheme in the case where the functional group x of the separator is -OH and the linking reaction unit y1 of the additive (compound Ry) is -NCO is shown below. [ka]

[0132] When reaction (IV) is a ring-opening reaction, the functional group x of compound Rx and the linking reaction unit y1 of compound Ry can undergo a ring-opening reaction, and from the viewpoint of availability of raw materials, it is preferable that the cyclic structure on the linking reaction unit y1 side opens. From the same viewpoint, it is more preferable that the linking reaction unit y1 is an epoxy group, it is even more preferable that compound Ry has at least two epoxy groups, and it is even more preferable that it is a diepoxy compound.

[0133] When the reaction (IV) is a ring-opening reaction, the functional group x of the compound Rx is preferably at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH, and / or the linking reaction unit y1 of the compound Ry is preferably represented by the following formula (ROy1-1): [ka] In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent. In formula (ROy1-1), each of the multiple Xs independently represents a hydrogen atom or a monovalent substituent, and preferably represents a hydrogen atom, C 1~20 The functional group x of the compound Rx and the linking reaction unit y1 of the compound Ry for the epoxy ring-opening reaction are preferably combined as shown in Table 7 below.

[0134] [Table 7]

[0135] Reaction (V) The first functional group of the separator is A and the metal ion is M. n+ A schematic scheme of reaction (V) and an example of functional group A are shown below. [ka]

[0136] In the above scheme, metal ion M n+ is preferably eluted from the electricity storage device (hereinafter, also referred to as eluted metal ion), for example, Zn 2+ , Mn 2+ , Co 3+ , Ni 2+ and Li + The functional group A may be at least one selected from the group consisting of -COO - The coordinate bond in the above case is exemplified below. [ka]

[0137] Functional group A is -COOH and the eluted metal ion is Zn 2+ A specific scheme of reaction (V) in the case of is shown below. [ka]

[0138] In the above scheme, hydrofluoric acid (HF) can be derived from, for example, the electrolyte, electrolytic solution, electrode active material, additive, or decomposition product or water absorption product thereof contained in the electricity storage device, depending on the charge / discharge cycle of the electricity storage device.

[0139] <Silane-modified polyolefin> Silane-modified polyolefins have a structure in which the main chain is a polyolefin and an alkoxysilyl group is grafted onto the main chain. Silane-modified polyolefins can be obtained by grafting an alkoxysilyl group onto the main chain of a silane-unmodified polyolefin. It is presumed that the alkoxysilyl group is converted to a silanol group through a hydrolysis reaction with water, and then undergoes a crosslinking reaction to form a siloxane bond (see the formula below; the ratio of T1 structure, T2 structure, and T3 structure is arbitrary). Examples of alkoxides substituted on the alkoxysilyl group include methoxide, ethoxide, and butoxide. In the formula below, R includes methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl. [ka]

[0140] The main chain and the graft are connected by a covalent bond. Examples of structures that form such covalent bonds include alkyl, ether, glycol, ester, etc. In the silane-modified polyolefin, the silanol unit is modified at a level of 2% or less relative to the main chain ethylene unit before the crosslinking reaction.

[0141] The preferred silane-grafted polyolefin has a density of 0.90 to 0.96 g / cm 3 and the melt flow rate (MFR) at 190°C is 0.2 to 5 g / min.

[0142] The amount of the silane-modified polyolefin is preferably 0.5% by mass or more or 3% by mass or more, more preferably 4% by mass or more, and even more preferably 5% by mass or more or 6% by mass or more, based on the total amount of the microporous membrane or the A layer, from the viewpoint of the effect of the present invention being well exhibited. The amount of the silane-modified polyolefin is preferably 40% by mass or less, more preferably 38% by mass or less, based on the total amount of the microporous membrane, from the viewpoint of the cycle property and safety of the electricity storage device. The amount of the silane-modified polyolefin may be 30% by mass or more or 50% by mass or more, or even 100% by mass, based on the total amount of the A layer.

[0143] The crosslinked structure in the microporous membrane or layer A is preferably formed by a compound generated within the electricity storage device. That is, in the production process of an electricity storage device, when the separator is brought into contact with a non-aqueous electrolyte, it is also preferable that a crosslinked structure in the microporous membrane or layer A forms an oligosiloxane bond by utilizing swelling of the microporous membrane or layer A and / or a compound generated in the electricity storage device, and the crosslinked structure in the microporous membrane or layer A. In this case, the crosslinked structure is a crosslinked structure obtained by actively promoting the crosslinking reaction in the production process of the electricity storage device, without actively promoting the crosslinking reaction in the production process of the separator, and therefore the self-crosslinking property of the separator can be maintained until it is housed in the electricity storage device.

[0144] From the viewpoint of suppressing the generation of resin aggregates in the separator manufacturing process and maintaining silane crosslinking properties until contact with the electrolyte, it is preferable that the silane-modified polyolefin is not a masterbatch resin containing a dehydration condensation catalyst. It is known that the dehydration condensation catalyst also functions as a catalyst for the siloxane bond formation reaction of an alkoxysilyl group-containing resin. In this specification, a compound obtained by adding a dehydration condensation catalyst (e.g., an organometallic catalyst) to an alkoxysilyl group-containing resin or other kneaded resin in advance during a continuous process having a resin kneading step using an extruder and compounding the resulting material is called a masterbatch resin.

[0145] (polyethylene) In this specification, polyethylene that can be further contained in addition to the silane-modified polyolefin (polyethylene further contained in the microporous membrane or layer A as a polyolefin other than the silane-modified polyolefin) means polyethylene that is a homoethylene polymer or a copolymer containing an alkane unit and has a weight-average molecular weight of 100,000 or more and 10,000,000 or less.

[0146] When the microporous membrane or layer A further contains polyethylene as a polyolefin different from the silane-modified polyolefin, the content thereof is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more, based on the total amount of the silane-modified polyolefin and the polyethylene. If the polyethylene content is 20% by mass or more, it becomes easy to ensure deterioration resistance against oxidation and reduction, and also tends to ensure a dense and uniform porous structure. On the other hand, the polyethylene content is preferably 97% by mass or less, more preferably 96% by mass or less, and even more preferably 95% by mass or less. When the polyethylene content is 97% by mass or less, the content of the silane-modified polyolefin in the microporous membrane or layer A can be ensured.

[0147] (Method for detecting silane-modified polyolefin contained in separator) In the crosslinked state, the silane-modified polyolefin contained in the separator is insoluble or has insufficient solubility in organic solvents, so that it may be difficult to measure the content of the silane-modified polyolefin directly from the separator. In this case, the silane-modified polyolefin contained in the separator can be detected by decomposing the siloxane bond into methoxysilanol using methyl orthoformate, which does not cause side reactions, as a pretreatment of the sample, and then performing solution NMR measurement. The pretreatment experiment can be performed with reference to Japanese Patent No. 3529854 and Japanese Patent No. 3529858.

[0148] Specifically, the silane-modified polyolefin used as a raw material in the manufacture of separators 1 H or 13 The C NMR identification can be used to detect silane-modified polyolefins contained in separators. 1 H and 13 An example of a C NMR measurement technique is described below.

[0149] ( 1 H NMR measurement) The sample is dissolved in o-dichlorobenzene-d4 at 140° C., and a 1H-NMR spectrum is obtained with a proton resonance frequency of 600 MHz. 1 The H-NMR measurement conditions are as follows. Equipment: Bruker AVANCE NEO 600 Sample tube diameter: 5mmφ Solvent: o-dichlorobenzene-d4 Measurement temperature: 130℃ Pulse angle: 30° Pulse waiting time: 1sec Number of times: 1000 or more Sample concentration: 1 wt / vol%

[0150] ( 13 C NMR measurement) The sample was dissolved in o-dichlorobenzene-d4 at 140°C. 13 Obtain a C-NMR spectrum. 13 The measurement conditions for C-NMR are as follows: Equipment: Bruker AVANCE NEO 600 Sample tube diameter: 5mmφ Solvent: o-dichlorobenzene-d4 Measurement temperature: 130℃ Pulse angle: 30° Pulse waiting time: 5sec Accumulation count: 10,000 times or more Sample concentration: 10 wt / vol%

[0151] Figures 11 and 12 show the results of the silane-modified polyolefin raw materials 1 and 2, which use two types of polyolefins. 1 H and 13 1 is a C-NMR chart, and Raw Materials 1 and 2 are different in melt index (MI), C3 graft amount, C4 graft amount, and / or silanol modification amount.

[0152] Figure 11 1 H and 13 The C-NMR measurement conditions are as follows. ( 1 H-NMR measurement conditions) Equipment: Bruker Avance NEO 600 Observation kernel: 1 H Observation frequency: 600MHz Pulse program: zg30 Pulse delay: 1sec Number of times: 1024 Measurement temperature: 130℃ Chemical shift reference: 7.219ppm (o-DCBz) Solvent: o-dichlorobenzene-d4 Sample concentration: 1wt / vol% Sample tube: 5mmφ ( 13 C-NMR measurement conditions) Equipment: Bruker Avance NEO 600 Observation kernel: 13 C Observation frequency: 150.91MHz Pulse program: zgpg30 Pulse delay: 5sec Number of times: 24,000 or 12,800 Measurement temperature: 130℃ Chemical shift reference: 132.39ppm (o-DCBz) Solvent: o-dichlorobenzene-d4 Sample concentration: 10wt / vol% Sample tube: 5mmφ

[0153] Figure 12 1 H and 13 The C-NMR measurement conditions are as follows. ( 1 H-NMR measurement conditions) Equipment: Bruker Avance NEO 600 Observation kernel: 1 H Observation frequency: 600MHz Pulse program: zg30 Pulse delay: 1sec Number of times: 1024 Measurement temperature: 130℃ Chemical shift reference: 7.219ppm (o-DCBz) Solvent: o-dichlorobenzene-d4 Sample concentration: 1wt / vol% Sample tube: 5mmφ ( 13 C-NMR measurement conditions) Equipment: Bruker Avance NEO 600 Observation kernel: 13 C Observation frequency: 150.91MHz Pulse program: zgpg30 Pulse delay: 5sec Number of times: 12800 Measurement temperature: 130℃ Chemical shift reference: 132.39ppm (o-DCBz) Solvent: o-dichlorobenzene-d4 Sample concentration: 10wt / vol% Sample tube: 5mmφ

[0154] FIG. 13 shows a state before crosslinking of a separator produced using the silane-modified polyolefin raw material 1 shown in FIG. 11 in Example I-1 described later. 1 H and 13 13 is a C-NMR chart. 1 H and 13 The C-NMR measurement conditions are as follows. ( 1 H-NMR measurement conditions) Equipment: Bruker Avance NEO 600 Observation kernel: 1 H Observation frequency: 600MHz Pulse program: zg30 Pulse delay: 1sec Number of times: 1024 Measurement temperature: 130℃ Chemical shift reference: 7.219ppm (o-DCBz) Solvent: o-dichlorobenzene-d4 Sample concentration: 1wt / vol% Sample tube: 5mmφ ( 13 C-NMR measurement conditions) Equipment: Bruker Avance NEO 600 Observation kernel: 13 C Observation frequency: 150.91MHz Pulse program: zgpg30 Pulse delay: 5 sec Number of times: 24,000 or 12,800 Measurement temperature: 130℃ Chemical shift reference: 132.39 ppm (o-DCBz) Solvent: o-dichlorobenzene-d4 Sample concentration: 10wt / vol% Sample tube: 5mmφ

[0155] Furthermore, the crosslinked state of the separator can be measured by NMR similar to that shown in FIG. 13 after the pretreatment described above (not shown).

[0156] As shown in Figures 11 to 13, 1 H and / or 13 By measuring C NMR, it is possible to confirm the amount of silane unit modification in the silane-modified polyolefin and the amount of alkyl group modification in the polyolefin in the polyolefin raw material, and to identify the content of silane-modified polyolefin in the separator (-CH2-Si: 1 H, 0.69 ppm, t; 13 C, 6.11 ppm, s) is possible.

[0157] [Combination of microporous membrane and inorganic porous layer] A combination of a microporous membrane containing silane-modified polyolefin and an inorganic porous layer tends to achieve both a shutdown function at temperatures below 150°C and membrane rupture resistance at relatively high temperatures, and also improves the cycle characteristics and nail penetration safety of the battery of an electricity storage device. The silane-modified polyolefin in the microporous membrane is silane-crosslinkable, and when silane crosslinking occurs, the viscosity of the resin in the microporous membrane can increase. Therefore, when a compressive force is applied between multiple electrodes at an abnormally high temperature of an electricity storage device including a separator, it is assumed that the crosslinked, highly viscous resin is less likely to flow into the inorganic layer (i.e., is less likely to be integrated), and sufficient clearance between the electrodes can be secured, thereby suppressing battery short circuits.

[0158] [Inorganic porous layer] The inorganic porous layer is a layer containing inorganic particles and a resin binder, and may further contain, if desired, a dispersant that disperses the inorganic particles in the binder resin.

[0159] From the viewpoints of ion permeability of the separator and charge / discharge capacity or cycle stability of the electricity storage device, the thickness of the inorganic porous layer is preferably 0.5 μm to 10 μm, 0.5 μm to 7 μm, 0.5 μm to 5 μm, or 0.5 μm to 4 μm. The thickness of the inorganic porous layer can be determined by the method described in the Examples.

[0160] [Second porous layer (B layer)] The B layer includes inorganic particles. The B layer can further include a resin binder. When the B layer includes inorganic particles and a resin binder, the B layer can be the inorganic porous layer described above. The B layer may include components other than the inorganic particles and the resin binder.

[0161] (Thickness of layer B) The thickness (TB) of the B layer is preferably 0.2 μm or more, more preferably 0.5 μm or more. If the thickness (TB) is 0.5 μm or more, the mechanical strength tends to be improved. On the other hand, the thickness (TB) is preferably less than 22 μm, more preferably 20 μm or less, and even more preferably 15 μm or less. If the thickness (TB) is 30 μm or less, the volume occupied by the separator in the electricity storage device is reduced, which tends to be advantageous in terms of increasing the capacity of the electricity storage device. It is also preferable from the viewpoint of preventing an excessive increase in the air permeability of the separator. The thickness (TB) may be set to, for example, 0.50 μm or more, 0.80 μm or more, or 1.00 μm or more, and may be set to less than 22.00 μm, 20.00 μm or less, or 15.00 μm or less. The thickness (TB) can be measured by the method described in the Examples section, and can be controlled by changing the coating amount of the coating liquid (slurry) for forming the B layer, or the like.

[0162] When the B layer is a single layer, the thickness of the B layer is treated as the above "Thickness (TB)". When the B layer is a single layer, the total thickness of the multiple B layers is treated as the above "Thickness (TB)". In addition, when layer B is arranged on both one side and the other side of layer A, the total thickness of layer B arranged on one side and layer B arranged on the other side is treated as the above-mentioned "thickness (TB)".

[0163] (Inorganic particles) Examples of inorganic particles include inorganic oxides (oxide ceramics) such as alumina (Al2O3), silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; inorganic nitrides (nitride ceramics) such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum oxide hydroxide (AlO(OH)), potassium titanate, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination of two or more.

[0164] The amount of inorganic particles is preferably 5% by mass or more, or 20% by mass or more, more preferably 30% by mass or more, based on the total amount of the inorganic porous layer or B layer, from the viewpoint of ensuring heat resistance. The amount of inorganic particles may be set to 50% by mass or more, more than 80% by mass or 85% by mass or more, based on the total amount of the inorganic porous layer or B layer. On the other hand, the amount of inorganic particles is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, or 99% by mass or less. The amount of inorganic particles may be set to, for example, 20.00% by mass or more, 30.00% by mass or more, 50.00% by mass or more, more than 80.00% by mass or 85.00% by mass or more, or may be set to 99.90% by mass or less or 99.50% by mass.

[0165] The shape of the inorganic particles may be, for example, plate-like, scaly, needle-like, columnar, spherical, polyhedral, spindle-like, or block-like. A combination of inorganic particles having these shapes may be used.

[0166] The number average particle size of the inorganic particles is, for example, 0.01 μm or more, 0.1 μm or more, or 0.3 μm or more, and preferably 0.5 μm or more. On the other hand, the number average particle size is, for example, 10.0 μm or less, 9.0 μm or less, or 6.0 μm or less, preferably 2.5 μm or less, more preferably 2.0 μm or less, and even more preferably 1.5 μm or less. It is preferable to adjust the number average particle size of the inorganic particles within the above range from the viewpoint of improving safety during short circuit. As a method for adjusting the number average particle size of the inorganic particles, a method of pulverizing the inorganic particles using an appropriate pulverizing device such as a ball mill, a bead mill, or a jet mill can be mentioned.

[0167] Regarding the particle size distribution of the inorganic particles, the minimum particle size is preferably 0.02 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. The maximum particle size is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 7 μm or less. The ratio of the maximum particle size / average particle size is preferably 50 or less, more preferably 30 or less, and even more preferably 20 or less. It is preferable to adjust the particle size distribution of the inorganic particles within the above range from the viewpoint of suppressing thermal shrinkage at high temperatures. In addition, there may be multiple particle size peaks between the maximum particle size and the minimum particle size. In addition, examples of methods for adjusting the particle size distribution of the inorganic particles include a method of pulverizing the inorganic filler using a ball mill, a bead mill, a jet mill, or the like, and adjusting it to a desired particle size distribution, and a method of preparing multiple fillers having multiple particle size distributions and then blending them.

[0168] (Resin binder) The resin binder contains a resin that bonds inorganic particles together. The glass transition temperature (Tg) of the resin binder is preferably −50° C. to 100° C., more preferably −35° C. to 95° C., from the viewpoint of ensuring the binding property with the inorganic particles and the stability of the inorganic porous layer or layer B in the separator manufacturing process, or the electricity storage device manufacturing process or charge / discharge process.

[0169] The glass transition temperature is determined from a DSC curve obtained by differential scanning calorimetry (DSC). Specifically, the temperature of the intersection between a straight line extending the low-temperature side baseline of the DSC curve to the high-temperature side and a tangent at the inflection point of the step-like change part of the glass transition can be adopted as the glass transition temperature. More specifically, it may be determined according to the method described in the Examples. In addition, "glass transition" refers to a change in heat quantity caused by a change in state of the polymer, which is a test piece, in DSC, on the endothermic side. Such a change in heat quantity is observed as a step-like change shape in the DSC curve. "Step-like change" refers to the part of the DSC curve where the curve moves away from the previous low-temperature side baseline to a new high-temperature side baseline. Note that a combination of a step-like change and a peak is also included in the step-like change. Furthermore, "inflection point" refers to the point where the gradient of the step-like change part of the DSC curve is maximum. In addition, it can also be expressed as the point where the upward convex curve changes to a downward convex curve in the step-like change part when the upper side is the heat generation side. "Peak" refers to the portion of the DSC curve where the curve leaves the low-temperature baseline and returns to the same baseline. "Baseline" refers to the temperature region of the DSC curve where no transition or reaction occurs in the test specimen.

[0170] Examples of the resin binder include the following 1) to 7). These may be used alone or in combination of two or more. 1) Polyolefins: for example, polyethylene, polypropylene, ethylene propylene rubber, and modified products thereof; 2) Conjugated diene polymers: for example, styrene-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene copolymers and their hydrogenated products, acrylonitrile-butadiene-styrene copolymers and their hydrogenated products; 3) Acrylic polymers: for example, methacrylate-acrylate copolymers, styrene-acrylate copolymers, and acrylonitrile-acrylate copolymers; 4) Polyvinyl alcohol-based resins: for example, polyvinyl alcohol and polyvinyl acetate; 5) Fluorine-containing resins: for example, PVdF, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymers, and ethylene-tetrafluoroethylene copolymers; 6) Cellulose derivatives: for example, ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; and 7) Resins having a melting point and / or glass transition temperature of 180°C or higher, or polymers having no melting point but a decomposition temperature of 200°C or higher: for example, polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester.

[0171] These types of resin binders can be obtained by using desired monomers as raw materials and following known manufacturing methods such as emulsion polymerization or solution polymerization, etc. In the polymerization, the polymerization temperature, the pressure during polymerization, the method of adding the monomers, and the additives used (polymerization initiator, molecular weight adjuster, pH adjuster, etc.) are not limited.

[0172] The amount of the resin binder is, for example, 0.5% by mass or more or 1.0% by mass or more based on the total amount of the inorganic porous layer or the B layer, and, on the other hand, for example, 50% by mass or less or 30% by mass or less. As described above, since the resin binder is an optional component for the B layer, the amount of the resin binder contained in the B layer may be less than 20% by mass, 15% by mass or less, or 0% by mass based on the total amount of the B layer. If the amount of the resin binder contained in the B layer is reduced, the room for containing the inorganic particles in the B layer can be increased accordingly.

[0173] (Dispersant) The dispersant is adsorbed to the surface of inorganic particles in the slurry for forming the inorganic porous layer or the B layer, and stabilizes the inorganic particles by electrostatic repulsion, etc., and may be, for example, polycarboxylate, sulfonate, polyoxyether, surfactant, etc. In addition to the above-mentioned components, the inorganic porous layer or the B layer may further contain other components that are usually added to water-based paints, etc., within the scope of their effects. Such other components are not particularly limited, and examples thereof include thickeners, film-forming assistants, plasticizers, crosslinking agents, antifreeze agents, defoamers, dyes, preservatives, ultraviolet absorbers, light stabilizers, etc. These other components may be used alone or in combination of two or more.

[0174] (Additives) The microporous membrane, the inorganic porous layer, the A layer, and / or the B layer may contain known additives as necessary. Examples of the additives include organometallic catalysts (dehydration condensation catalysts), plasticizers, antioxidants such as phenolic, phosphorus, and sulfuric antioxidants, metal soaps such as calcium stearate and zinc stearate, thickeners, film-forming assistants, crosslinking agents, antifreeze agents, antifoaming agents, preservatives, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, dyes, and coloring pigments. Layer B may also contain a crosslinking agent. Such a crosslinking agent may contain a functional group reactive with the inorganic particles.

[0175] <Separator properties> When the separator is used in a relatively high-capacity lithium-ion secondary battery, the thickness of the entire separator is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less. By making the thickness of the separator 25 μm or less, ion permeability tends to be further improved. The lower limit of the thickness of the entire separator may be, for example, 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, 6.0 μm or more, or 7.5 μm or more.

[0176] The separator's air permeability is 50 seconds / 100 cm 3 ~400 seconds / 100cm 3is preferable, and more preferably 75 seconds / 100 cm 3 ~275 seconds / 100cm 3 , and more preferably 100 seconds / 100 cm 3 ~200 seconds / 100cm 3 The separator is 50 seconds / 100 cm 3 If the air permeability is more than 400 sec / 100 cm, the material has adequate mechanical strength. 3 In view of permeability, the battery characteristics are improved if the air permeability is within this range, which is preferable.

[0177] [Electricity storage device assembly kit] In another embodiment of the present invention, there is provided an electricity storage device assembly kit including the above-described separator for an electricity storage device. The electricity storage device assembly kit includes the following two elements: (A) an exterior body housing a laminate or a wound body of an electrode and a separator for an electricity storage device according to each embodiment described above; and (B) a container containing a nonaqueous electrolyte; When the electricity storage device assembly kit is used, a cross-linked structure is formed in the separator by contacting the separator in element (A) with the nonaqueous electrolyte in element (B) and contacting the electrolyte with the laminate or wound body within the exterior body and / or by continuing the charge / discharge cycle of the assembled electricity storage device, thereby forming an electricity storage device that is both safe and has a high output.

[0178] Without wishing to be bound by theory, it is believed that when the electrolyte or electrolyte solution comes into contact with the electrodes and / or when the power storage device is charged and discharged, a substance that catalyzes the crosslinking reaction or a substance having a functional group that becomes part of the crosslinked structure is present in the electrolyte solution, on the inner surface of the exterior body, or on the surface of the electrodes, and dissolves in the electrolyte solution and uniformly swells and diffuses into the amorphous part of the polyolefin, thereby uniformly promoting the crosslinking reaction of the separator-containing laminate or wound body. The substance that catalyzes the crosslinking reaction may be in the form of an acid solution or film, and when the electrolyte contains lithium hexafluorophosphate (LiPF6), it can be hydrogen fluoride (HF) or a fluorine-containing organic substance derived from hydrogen fluoride (HF). The substance having a functional group that becomes part of the crosslinked structure can be, for example, a compound having the functional groups A and / or B described above, the electrolyte solution itself, various additives, etc.

[0179] From the viewpoint of promoting the cross-linking reaction of the separator, the nonaqueous electrolyte stored in element (2) is preferably a fluorine (F)-containing lithium salt such as LiPF6 that generates HF, or an electrolyte having an unshared electron pair such as LiN(SO2CF3)2 or LiSO3CF3, or alternatively LiBF4, LiBC4O8 (LiBOB), etc.

[0180] In order to promote the crosslinking reaction of the separator, the electricity storage device assembly kit may include, as an accessory (or element (C)), a separate container for containing a catalyst for promoting the crosslinking reaction, such as a mixture of an organometallic catalyst and water, an acid solution, a base solution, or the like.

[0181] [Electricity storage device] The separator described above can be used in an electricity storage device. The electricity storage device includes a positive electrode, a negative electrode, a separator according to the present embodiment disposed between the positive and negative electrodes, an electrolyte, and, if desired, an additive. When the separator is housed in a device exterior, the functionally modified polyethylene or the functionally grafted polyethylene reacts with the chemicals contained in the electrolyte or the additive to form a crosslinked structure, so that the produced electricity storage device has a crosslinked structure. The functionally modified polyethylene or the functionally grafted polyethylene can be derived from, but is not limited to, the polyolefin raw material of the microporous membrane, or can be derived from a polyolefin modified during the manufacturing process of the microporous membrane.

[0182] Specific examples of the power storage device include lithium batteries, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel hydrogen batteries, nickel cadmium batteries, electric double layer capacitors, lithium ion capacitors, redox flow batteries, lithium sulfur batteries, lithium air batteries, zinc air batteries, etc. Among these, from the viewpoint of practicality, lithium batteries, lithium secondary batteries, lithium ion secondary batteries, nickel hydrogen batteries, and lithium ion capacitors are preferred, and lithium batteries and lithium ion secondary batteries are more preferred. The additives may be, for example, a dehydration condensation catalyst, metal soaps such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, a coloring pigment, and the like.

[0183] [Lithium-ion secondary battery] The lithium ion secondary battery is a storage battery that uses a lithium transition metal oxide such as lithium cobalt oxide or lithium cobalt composite oxide as a positive electrode, a carbon material such as graphite or graphite as a negative electrode, and an organic solvent containing a lithium salt such as LiPF6 as an electrolyte. The electrolyte described above for the electricity storage device assembly kit may also be used for the lithium ion secondary battery. When a lithium-ion secondary battery is charged or discharged, ionized lithium travels back and forth between the electrodes. In order to prevent contact between the electrodes and to ensure that the ionized lithium travels between the electrodes at a relatively high speed, a separator is placed between the electrodes.

[0184] <Method for producing separator for power storage device> Another aspect of the present invention is a method for producing a separator for an electricity storage device. The method for producing a separator may include, for example, a step of producing a microporous membrane or an A layer, and, if desired, a step of producing an inorganic porous layer on the microporous membrane, or a step of producing a B layer on the A layer. Materials used in the method for producing a separator may be those described in the first to tenth embodiments, unless otherwise specified.

[0185] <Eleventh embodiment> The method for producing a separator according to the eleventh embodiment will be described below for a microporous membrane (flat membrane), but is not intended to exclude forms other than flat membranes. The method for producing a microporous membrane according to the eleventh embodiment includes the following steps: (1) Sheet forming process; (2) Stretching process; (3) a porous body forming step; and (4) Heat treatment process; By carrying out steps (1) to (4), the above-described layer A can also be formed.

[0186] The method for producing a separator according to the eleventh embodiment may, if desired, include the following steps in addition to steps (1) to (4): (8B) a coating step of forming an inorganic porous layer containing inorganic particles and a resin binder on at least one surface of the heat-treated porous body to form a silane crosslinking precursor; (9) an assembly step of housing a laminate or a wound body of the laminate of the electrodes and the silane cross-linked precursor, and a non-aqueous electrolyte solution in an exterior body, and bringing the silane cross-linked precursor into contact with the non-aqueous electrolyte solution; In the eleventh embodiment, the inorganic porous layer is applied to the microporous membrane that maintains silane crosslinkability in step (8B), and then the separator in the electricity storage device is contacted with the electrolyte in step (9), thereby improving the stress resistance of the electricity storage device and the separator therein, and thereby achieving the cycle stability and safety of the electricity storage device.

[0187] The method for producing a microporous membrane according to the eleventh embodiment may, if desired, include a kneading step before the sheet forming step (1) and / or a winding and slitting step after the heat treatment step (3), but from the viewpoint of maintaining silane crosslinkability until contact with an electrolytic solution, it is preferable not to include a silane crosslinking treatment step. The silane crosslinking treatment step is generally a step in which an object to be treated containing a silane-modified polyolefin is brought into contact with a mixture of an organometallic catalyst and water or immersed in a base solution or acid solution to carry out a silane dehydration condensation reaction to form an oligosiloxane bond.

[0188] The metal of the organometallic catalyst may be at least one selected from the group consisting of, for example, sulphur, titanium, vanadium, copper, zinc, aluminium, zirconium, palladium, gallium, tin and lead. The organometallic catalyst may be di-butyltin-di-laurate, di-butyltin-di-acetate, di-butyltin-di-octoate, etc., and is known to be able to overwhelmingly promote the reaction rate by the reaction mechanism proposed by Weij et al. (FW van. der. Weij: Macromol. Chem., 181, 2541, 1980.). In recent years, in order to avoid the damage to the environment and human health caused by organotin, it has been known that the Lewis function of copper and / or titanium chelate complexes can be used in combination with an organic base to promote the reaction of forming siloxane bonds between alkoxysilyl groups in the same way as organotin complexes.

[0189] The base solution has a pH of more than 7 and may contain, for example, alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkali metal phosphates, ammonia, amine compounds, etc. Among these, from the viewpoints of safety and silane crosslinking property of the electricity storage device, alkali metal hydroxides or alkaline earth metal hydroxides are preferred, alkali metal hydroxides are more preferred, and sodium hydroxide is even more preferred.

[0190] The acid solution has a pH of less than 7 and may include, for example, inorganic acids, organic acids, etc. Preferred acids are hydrochloric acid, sulfuric acid, carboxylic acids, or phosphoric acids.

[0191] In the kneading step, in this embodiment, the silane-modified polyolefin and, if desired, a plasticizer or inorganic material and other polyolefins can be kneaded using a kneader. From the viewpoint of suppressing the generation of resin aggregates in the manufacturing process and maintaining silane crosslinkability until contact with the electrolytic solution, it is preferable not to add a master batch resin containing a dehydration condensation catalyst to the kneaded mixture.

[0192] The plasticizer is not particularly limited, but examples thereof include organic compounds that can form a uniform solution with polyolefin at a temperature below the boiling point. More specifically, decalin, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decyl alcohol, nonyl alcohol, diphenyl ether, n-decane, n-dodecane, paraffin oil, etc. are included. Among these, paraffin oil and dioctyl phthalate are preferred. The plasticizer may be used alone or in combination of two or more. The ratio of the plasticizer is not particularly limited, but from the viewpoint of the porosity of the obtained microporous film, the polyolefin and the silane-modified polyolefin are preferably 20% by mass or more based on the total mass as necessary, and from the viewpoint of the viscosity during melt kneading, it is preferably 90% by mass or less.

[0193] The sheet forming process is a process in which the obtained kneaded product or a mixture of silane-modified polyolefin, polyethylene and plasticizer is extruded, cooled and solidified, and molded into a sheet to obtain a sheet. The method of forming the sheet is not particularly limited, but for example, a method of compressing and cooling the molten product extruded after melt kneading to solidify it is included. The cooling method includes a method of directly contacting the product with a cooling medium such as cold air or cooling water, a method of contacting the product with a roll and / or a press machine cooled with a refrigerant, etc., and the method of contacting the product with a roll and / or a press machine cooled with a refrigerant is preferred in terms of excellent film thickness controllability.

[0194] From the viewpoint of resin aggregates or maximum internal heat generation rate in the separator, the mass ratio of silane-modified polyolefin to polyethylene (mass of silane-modified polyolefin / mass of polyethylene) in the sheet molding process is preferably 0.05 / 0.95 to 0.4 / 0.6, and more preferably 0.06 / 0.94 to 0.38 / 0.62.

[0195] From the viewpoint of improving safety by suppressing thermal runaway upon breakdown of the electricity storage device while having low-temperature shutdown properties of 150°C or less and resistance to membrane rupture at high temperatures of 180 to 220°C, it is preferable that the silane-modified polyolefin in the sheet molding step is not a masterbatch resin that contains a dehydration condensation catalyst that crosslinks the silane-modified polyolefin before the sheet molding step.

[0196] The stretching step is a step of extracting plasticizer and / or inorganic material from the obtained sheet as necessary, and further stretching the sheet in one or more directions. Examples of the sheet stretching method include MD uniaxial stretching by a roll stretching machine, TD uniaxial stretching by a tenter, sequential biaxial stretching by a combination of a roll stretching machine and a tenter, or a tenter and a tenter, and simultaneous biaxial stretching by a simultaneous biaxial tenter or inflation molding. From the viewpoint of obtaining a more uniform film, simultaneous biaxial stretching is preferable. The total areal magnification is preferably 8 times or more, more preferably 15 times or more, and even more preferably 20 times or more or 30 times or more, from the viewpoint of the uniformity of the film thickness, the balance between the tensile elongation, the porosity, and the average pore size. By having a total areal magnification of 8 times or more, it tends to be easy to obtain a film with high strength and good thickness distribution. In addition, from the viewpoint of preventing breakage, this areal magnification may be 250 times or less.

[0197] The porous body forming step is a step of extracting a plasticizer from the stretched product after the stretching step to make the stretched product porous. The method of extracting the plasticizer is not particularly limited, but examples thereof include a method of immersing the stretched product in an extraction solvent and a method of showering the stretched product with the extraction solvent. The extraction solvent is not particularly limited, but for example, it is preferably a poor solvent for polyolefin and a good solvent for plasticizers and / or inorganic materials, and has a boiling point lower than the melting point of polyolefin. Such an extraction solvent is not particularly limited, but examples thereof include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as methylene chloride, 1,1,1-trichloroethane, and fluorocarbons; alcohols such as ethanol and isopropanol; ketones such as acetone and 2-butanone; and alkaline water. The extraction solvent may be used alone or in combination of two or more types.

[0198] The heat treatment step is a step of extracting a plasticizer from the sheet as necessary after the stretching step, and further performing heat treatment to obtain a microporous membrane. The heat treatment method is not particularly limited, but examples include a heat setting method in which stretching and relaxation operations are performed using a tenter and / or a roll stretching machine. The relaxation operation refers to a reduction operation performed at a predetermined temperature and relaxation rate in the machine direction (MD) and / or transverse direction (TD) of the membrane. The relaxation rate refers to the value obtained by dividing the MD dimension of the membrane after the relaxation operation by the MD dimension of the membrane before the operation, or the value obtained by dividing the TD dimension of the membrane after the relaxation operation by the TD dimension of the membrane before the operation, or when both MD and TD are relaxed, the value obtained by multiplying the relaxation rate of MD and the relaxation rate of TD.

[0199] [Inorganic Porous Layer Coating Process] The inorganic porous layer coating step (8B) is a step of forming an inorganic porous layer containing inorganic particles and a resin binder on at least one surface of the microporous membrane obtained above. The coating step (8B) can be performed while maintaining the silane crosslinkability of the silane-modified polyolefin.

[0200] By carrying out the coating step (8B), the B layer described above can also be formed. A known manufacturing method can be adopted as a method for forming the B layer. Examples of a method for producing a laminate including the A layer and the B layer include a method of coating the A layer with a slurry containing inorganic particles, a method of laminating and extruding the raw material of the B layer and the raw material of the A layer by a co-extrusion method, and a method of producing the A layer and the B layer separately and then bonding them together.

[0201] The inorganic porous layer can be formed, for example, by applying a slurry containing inorganic particles, a resin binder, water or an aqueous solvent (e.g., a mixture of water and alcohol), and optionally a dispersant, to at least one surface of the microporous membrane. The inorganic particles, the resin binder, and the dispersant may be as described in the first to tenth embodiments.

[0202] The solvent contained in the slurry is preferably one that can disperse or dissolve the inorganic particles uniformly and stably, such as N-methylpyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, toluene, hot xylene, methylene chloride, and hexane.

[0203] Examples of methods for preparing the inorganic particle-containing slurry include mechanical stirring methods using a ball mill, a bead mill, a planetary ball mill, a vibrating ball mill, a sand mill, a colloid mill, an attritor, a roll mill, high-speed impeller dispersion, a disperser, a homogenizer, a high-speed impact mill, ultrasonic dispersion, and a stirring blade.

[0204] Examples of methods for applying the inorganic particle-containing slurry include a gravure coater method, a small diameter gravure coater method, a reverse roll coater method, a transfer roll coater method, a kiss coater method, a dip coater method, a knife coater method, an air doctor coater method, a blade coater method, a rod coater method, a squeeze coater method, a cast coater method, a die coater method, a screen printing method, and a spray coating method.

[0205] Methods for removing the solvent from such a coating film include drying at a temperature equal to or lower than the melting point of the material constituting the microporous film, drying under reduced pressure at a low temperature, etc. Furthermore, some of the solvent may be allowed to remain within a range that does not significantly affect the device characteristics.

[0206] [Winding / Slitting process] The winding step is a step in which the obtained microporous membrane or the microporous membrane coated with the inorganic porous layer is slit as necessary and wound around a predetermined core.

[0207] [Electricity storage device assembly process] The electricity storage device assembly process is a process in which a separator precursor (hereinafter also referred to as a silane crosslinked precursor) that has maintained the silane crosslinking property and an electrode are laminated to form a laminate, the laminate is further wound as desired to form a wound body, and the laminate or wound body and a non-aqueous electrolyte are housed in an exterior body to bring the silane crosslinked precursor into contact with the non-aqueous electrolyte. The electricity storage device assembly process suppresses film loss of the microporous membrane, maintains morphology, and suppresses penetration of the polyolefin resin from the microporous membrane into the inorganic porous layer, thereby improving the stress resistance of the electricity storage device or separator.

[0208] Since the silane-modified polyolefin is crosslinked during or after the electricity storage device assembly step (9), the method is compatible with conventional electricity storage device manufacturing processes, and can also improve the safety of the electricity storage device by causing a silane crosslinking reaction in the separator after the electricity storage device is manufactured.

[0209] In the energy storage device assembly process, from the viewpoint of handling the electrolyte, it is preferable to enclose the laminate or wound body in an outer casing and then pour the nonaqueous electrolyte into the outer casing, or to pour the electrolyte into the outer casing and then enclose the laminate or wound body in the outer casing.

[0210] From the viewpoint of promoting the crosslinking reaction of the separator, the electrolyte of the nonaqueous electrolyte may be a fluorine (F)-containing lithium salt such as LiPF6 that generates hydrogen fluoride (HF), or an electrolyte having an unshared electron pair such as LiN(SO2CF3)2 or LiSO3CF3, or may be LiBF4, LiBC4O8 (LiBOB), etc.

[0211] Although not wishing to be bound by theory, it is presumed that the methoxysilane grafted portion is converted to silanol by a small amount of moisture contained in the power storage device (moisture contained in components such as electrodes, separators, and electrolyte), undergoes a crosslinking reaction, and changes to a siloxane bond. In addition, when the electrolyte or electrolyte comes into contact with the electrode, a substance that catalyzes the silane crosslinking reaction is generated in the electrolyte or on the electrode surface, and it is thought that these substances dissolve in the electrolyte and uniformly swell and diffuse into the amorphous portion of the polyolefin in which the silane-modified grafted portion exists, thereby uniformly promoting the crosslinking reaction of the separator-containing laminate or wound body. The substance that catalyzes the silane crosslinking reaction may be in the form of an acid solution or a film, and when the electrolyte contains lithium hexafluorophosphate (LiPF6), it can be HF generated by the reaction of LiPF6 with moisture, or a fluorine-containing organic substance derived from HF.

[0212] From the viewpoint of the efficiency of the silane crosslinking reaction, it is preferable to store the laminate or wound body and the nonaqueous electrolyte in the exterior of the electricity storage device, and then connect lead terminals to the electrodes and perform at least one cycle of charging and discharging. It is considered that a substance that has a catalytic effect on the silane crosslinking reaction is generated in the electrolyte or on the electrode surface by the charge and discharge cycle, thereby achieving the silane crosslinking reaction. The cycle charging and discharging can be performed by known methods and devices, and specifically, the method described in the Examples can be used.

[0213] [Method for manufacturing an electricity storage device] Another embodiment of the present invention is a method for producing an electricity storage device.

[0214] <Twelfth embodiment> A method for producing an electricity storage device according to a twelfth embodiment includes the following steps: (A) preparing the above-described electricity storage device assembly kit; (a) initiating a silane crosslinking reaction of the silane-modified polyolefin by contacting a separator in an element (1) of an electricity storage device assembly kit with a non-aqueous electrolyte in an element (2); (c) optionally connecting a lead terminal to the electrode of element (1); (d) optionally performing at least one charge / discharge cycle; Steps (a) to (d) can be performed by a method known in the art, except for using the separator for an electricity storage device according to this embodiment, and steps (a) to (d) can use a positive electrode, a negative electrode, an electrolyte, an exterior body, and a charge / discharge device known in the art.

[0215] For the step (a), a separator having a vertically elongated shape with a width of 10 to 500 mm (preferably 80 to 500 mm) and a length of 200 to 4000 m (preferably 1000 to 4000 m) can be produced. Next, in the step (a), the positive electrode-separator-negative electrode-separator or negative electrode-separator-positive electrode-separator are laminated in this order, and wound into a circular or flat spiral shape to obtain a wound body. In the steps (b) and (c), the wound body is stored in a device can (e.g., a battery can), and a nonaqueous electrolyte is further injected to produce an electricity storage device. Alternatively, an electricity storage device can be produced by folding the electrodes and the separator to form a wound body, placing it in a device container (e.g., an aluminum film), and injecting a nonaqueous electrolyte.

[0216] At this time, the wound body can be pressed. Specifically, the separator, the current collector, and the electrode having the active material layer formed on at least one surface of the current collector can be stacked and pressed.

[0217] The pressing temperature is preferably, for example, 20°C or higher, which is a temperature at which adhesiveness can be effectively exhibited. From the viewpoint of suppressing clogging of pores in the separator or thermal shrinkage due to heat pressing, the pressing temperature is preferably lower than the melting point of the material contained in the microporous membrane, and more preferably 120°C or lower. From the viewpoint of suppressing clogging of pores in the separator, the pressing pressure is preferably 20 MPa or lower. The pressing time may be 1 second or less when using a roll press, or may be surface pressing for several hours, but is preferably 2 hours or less from the viewpoint of productivity. The above manufacturing process can suppress press-back when a wound body made of electrodes and a separator is press-molded, which is preferable because it can suppress a decrease in yield in the device assembly process and shorten the production process time.

[0218] From the viewpoint of reliably carrying out the silane crosslinking reaction of the separator after step (a), it is preferable to carry out steps (c) and (d). It is considered that a substance that has a catalytic effect on the silane crosslinking reaction is generated in the electrolyte or on the electrode surface by the charge-discharge cycle, thereby achieving the silane crosslinking reaction.

[0219] For example, in the method for producing a separator, when the method for producing the A layer described above does not include a silane crosslinking treatment step, the crosslinking reaction can be actively promoted by contacting the separator with a nonaqueous electrolyte. Although not wishing to be bound by theory, it is presumed that the silane-modified graft portion is converted to silanol by a small amount of moisture contained in the power storage device (a small amount of moisture contained in the electrodes, separator, nonaqueous electrolyte, etc.), undergoes a crosslinking reaction, and changes to a siloxane bond. In addition, when the nonaqueous electrolyte comes into contact with the electrode, it is considered that a substance that catalyzes the silane crosslinking reaction is generated in the nonaqueous electrolyte or on the electrode surface. It is considered that such a substance that catalyzes the silane crosslinking reaction is dissolved in the nonaqueous electrolyte and uniformly swells and diffuses into the amorphous part of the polyolefin in which the silane-modified graft portion is present, thereby uniformly promoting the crosslinking reaction of the separator-containing laminate or wound body.

[0220] The substance that catalyzes the silane crosslinking reaction may be in the form of an acid solution or a film. When the electrolyte contains lithium hexafluorophosphate (LiPF6), hydrogen fluoride (HF) or a fluorine-containing organic substance derived from hydrogen fluoride (HF) generated by the reaction of LiPF6 with water is treated as a substance that catalyzes the silane crosslinking reaction (a compound generated in the electricity storage device).

[0221] <Thirteenth embodiment> A thirteenth embodiment is a method for producing an electricity storage device using a separator including a polyolefin having one or more functional groups, the method comprising the steps of: (1) A cross-linking step in which functional groups are condensed with each other, (2) functional groups are reacted with chemicals inside the energy storage device, or (3) functional groups of the polyolefin are reacted with other types of functional groups to form cross-linked structures. Includes.

[0222] The crosslinking step can be carried out in the same manner as the reaction for forming the crosslinked structure of the separator described above. In addition, since the crosslinking step can be carried out by utilizing the compounds in the electricity storage device and the environment around the device, it does not require excessive conditions such as electron beams or high temperatures of 100°C or higher, and mild conditions such as a temperature of 5°C to 90°C and / or the surrounding atmosphere can be adopted.

[0223] By carrying out a crosslinking step in the manufacturing process of an electricity storage device, the formation of a crosslinked structure during or immediately after the separator film-forming process can be omitted, and stress distortion after the production of the electricity storage device can be alleviated or eliminated, and / or a crosslinked structure can be imparted to the separator without the use of relatively high energy such as light irradiation or heating, thereby reducing uneven crosslinking, the occurrence of unmelted resin aggregates, and the burden on the environment.

[0224] During the crosslinking process, (2) functional groups are reacted with chemicals inside the electricity storage device, or (3) functional groups of the polyolefin are reacted with other types of functional groups, thereby forming crosslinked structures not only inside the separator, but also between the separator and the electrodes or between the separator and the solid electrolyte interface (SEI), thereby improving the strength between multiple components of the electricity storage device.

[0225] The separator described above crosslinks the silane-modified polyolefin when it comes into contact with an electrolyte solution, making it compatible with conventional manufacturing processes for electricity storage devices while allowing a silane crosslinking reaction to occur after the electricity storage device is manufactured, thereby improving the safety of the electricity storage device. EXAMPLES

[0226] The present invention will be described in more detail with reference to examples and comparative examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. The physical properties in the examples were measured by the following methods.

[0227] <Weight average molecular weight> A calibration curve was created by measuring standard polystyrene under the following conditions using a Waters ALC / GPC 150C (trademark). Chromatograms were also measured under the same conditions for each of the following polymers, and the weight-average molecular weight of each polymer was calculated based on the calibration curve by the following method. Column: Tosoh GMH6-HT (trademark) x 2 + GMH6-HTL (trademark) x 2 Mobile phase: o-dichlorobenzene Detector: Differential refractometer Flow rate: 1.0ml / min Column temperature: 140℃ Sample concentration: 0.1wt% (Weight average molecular weight of polyethylene) Each molecular weight component in the obtained calibration curve was multiplied by 0.43 (Q factor of polyethylene / Q factor of polystyrene=17.7 / 41.3) to obtain a molecular weight distribution curve converted into polyethylene, and the weight average molecular weight was calculated. (Weight average molecular weight of resin composition) The weight average molecular weight was calculated using the Q factor value of the polyolefin with the largest mass fraction, and otherwise in the same manner as in the case of polyethylene.

[0228] <Viscosity average molecular weight (Mv)> Based on ASTM-D4020, the intrinsic viscosity [η] in decalin solvent at 135°C was determined. The Mv of polyethylene was calculated using the following formula. [η]=6.77×10 -4 Mv 0.67

[0229] <Melt mass flow rate (MFR) (g / 10min)> Using a melt mass flow rate measuring instrument (Melt Indexer F-F01) manufactured by Toyo Seiki Seisakusho, the weight of the resin extruded in 10 minutes under conditions of 190° C. and a load of 2.16 kg was determined as the MFR value.

[0230] <Measurement of glass transition temperature> An appropriate amount of the aqueous dispersion (solid content = 38-42 wt%, pH = 9.0) containing the resin sample was placed on an aluminum dish and dried for 30 minutes in a hot air dryer at 130 °C to obtain a dry film. Approximately 17 mg of the dry film was filled into an aluminum container for measurement, and a DSC curve under a nitrogen atmosphere and a DSC curve were obtained using a DSC measuring device (Shimadzu Corporation, model name "DSC6220"). The measurement conditions were as follows. First stage heating program: Start at 70℃, heat up at a rate of 15℃ per minute. After reaching 110℃, maintain for 5 minutes. Second stage temperature reduction program: Reduce temperature from 110℃ at a rate of 40℃ per minute. After reaching -50℃, maintain temperature for 5 minutes. Third stage heating program: Heat from -50°C to 130°C at a rate of 15°C per minute. DSC and DDSC data were obtained during this third stage heating. The glass transition temperature (Tg) was determined as the intersection point between the baseline (a straight line extending the baseline of the obtained DSC curve toward the higher temperature side) and the tangent at the inflection point (the point where the upward convex curve changes to a downward convex curve).

[0231] <Film thickness (μm)> Using a micro-thickness gauge manufactured by Toyo Seiki Co., Ltd. and KBM (trademark), the film thickness of the microporous membrane or separator was measured at room temperature of 23 ± 2°C and relative humidity of 60%. Specifically, across the entire width in the TD direction, the film thicknesses at 5 points were measured at approximately equal intervals, and the average value thereof was obtained. The thickness of the inorganic porous layer can be calculated by subtracting the film thickness of the microporous membrane from the thickness of the separator composed of the microporous membrane and the inorganic porous layer.

[0232] <Thickness of layer A (TA) and thickness of layer B (TB)> Using a micro-thickness gauge manufactured by Toyo Seiki Co., Ltd. and KBM (trademark), the thickness of layer A (TA) was measured at room temperature of 23 ± 2°C and relative humidity of 60%. Specifically, across the entire width in the TD direction, the film thicknesses at 5 points were measured at approximately equal intervals, and the average value thereof was obtained. Also, by the same method, the thickness of the laminate including layer A and layer B was obtained. Then, the thickness of layer B (TB) was obtained by subtracting the thickness of layer A (TA) from the thickness of the obtained laminate. The thickness of the obtained laminate was treated as the total thickness (TA + TB) of layer A and layer B. Also, the ratio of thicknesses (TA / TB) was obtained by dividing the thickness (TA) by the thickness (TB).

[0233] <Porosity (%)> (i) Calculated from the density of the mixed composition A 10 cm × 10 cm square sample was cut out from the microporous membrane, and its volume (cm 3 ) and mass (g) were determined. From these and the density (g / cm 3 ), the porosity was calculated using the following formula. The density of the mixed composition was the value calculated and obtained from the densities and mixing ratios of the respective raw materials used. Porosity (%) = (Volume - Mass / Density of mixed composition) / Volume × 100

[0234] (ii) Calculated from the film density Alternatively, from the volume, mass, and film density (g / cm 3 ), the porosity of the microporous membrane was calculated by the following formula. Porosity (%) = (Volume - Mass / Film density) / Volume × 100 In the present disclosure, the film density refers to the value measured according to the D) density gradient tube method described in JIS K7112 (1999).

[0235] (iii) Porosity of the A layer A 10 cm × 10 cm square sample was cut from the A layer, and its volume (cm 3 ) and mass (g) were determined. Then, using these values and the density (g / cm 3 ), the porosity was calculated using the following formula. The density of the mixed composition was the value calculated from the density and mixing ratio of each of the raw materials used. Porosity (%) = (Volume - Mass / Density of the mixed composition) / Volume × 100

[0236] <Air permeability (sec / 100 cm 3 )> In accordance with JIS P-8117 (2009), the air permeability of the sample or the A layer was measured using a Gurley air permeability meter, model G-B2 (trademark), manufactured by Toyo Seiki Co., Ltd.

[0237] <Puncture strength of the A layer> Using a handy compression tester KES-G5 (model name) manufactured by Kato Tech Co., Ltd., the A layer was fixed with a sample holder having an opening diameter of 11.3 mm. Next, a puncture test was performed on the central part of the fixed A layer at a puncture speed of 2 mm / second in an atmosphere of 25°C using a needle with a tip curvature radius of 0.5 mm, and the maximum puncture load was measured. The value obtained by converting the maximum puncture load per 20 μm thickness was defined as the puncture strength (gf / 20 μm). When the thermoplastic polymer exists only on one side of the substrate, the needle can be punctured from the surface where the thermoplastic polymer exists.

[0238] <Quantification of resin aggregates in the separator> Resin aggregates in the separator are defined as regions having an area of 100 μm in length × 100 μm or more in width and not allowing light to pass through when the separator obtained through the film-forming processes of the examples and comparative examples described later is observed with a transmission optical microscope. In the observation with a transmission optical microscope, for a separator area of 1000 m 2The number of resin aggregates per unit area was measured.

[0239] <Storage modulus, loss modulus and transition temperature (version 1)> Dynamic viscoelasticity of the separator can be measured using a dynamic viscoelasticity measuring device, and the storage modulus (E'), loss modulus (E''), and transition temperature between the rubber-like plateau region and the crystalline melting flow region can be calculated. The storage modulus change ratio (R ΔE’ ) is expressed by the following formula (1), and the mixed storage modulus ratio (R E’mix ) is calculated according to the following formula (2): ΔE’’ ) is calculated according to the following formula (3): E’’mix ) were calculated according to the following formula (4). The measurement conditions were as follows (i) to (iv). (i) Dynamic viscoelasticity measurements were performed under the following conditions: Atmosphere: Nitrogen Measurement device used: RSA-G2 (manufactured by TA Instruments) -Sample thickness: range of 5μm~50μm Measurement temperature range: -50~225℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.5N Initial gap distance (at 25°C): 25mm ·Auto strain adjustment:Enabled (range: amplitude value 0.05~25%, sine wave load 0.02~5N) It was carried out in. (ii) The static tensile load refers to the midpoint between the maximum stress and the minimum stress in each periodic motion, and the sinusoidal load refers to an oscillatory stress centered on the static tensile load. (iii) The sinusoidal tensile mode refers to measuring the vibration stress while performing periodic motion with a fixed amplitude of 0.2%, and the gap distance and the static tensile load were changed so that the difference between the static tensile load and the sinusoidal load was within 20%. When the sinusoidal load became 0.02N or less, the amplitude was amplified so that the sinusoidal load was within 5N and the increase in the amplitude was within 25%, and the vibration stress was measured. (iv) The relationship between the obtained sinusoidal load and the amplitude value, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E * ε * E * =E'+iE'' {where, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: the difference between the measured oscillatory stress and the static tensile load The storage modulus and loss modulus were calculated from the above. E' S and E' j and E'' S and E'' j was the average value of each storage modulus or each loss modulus at 160°C to 220°C in the dynamic viscoelasticity measurement data. a and E'0 and E'' a and E''0 were taken as the average values ​​of each storage modulus or each loss modulus at 160°C to 220°C in the dynamic viscoelasticity measurement data. R ΔE’ =E' S / E' j (1) Comparison before and after injection into the cell RE’mix =E' a / E'0(2) Comparison of presence and absence of silane crosslinking R ΔE’’ =E'' S / E'' j (3) Comparison before and after injection into the cell R E’’mix =E'' a / E''0(4) Comparison of presence and absence of silane crosslinking

[0240] An example of a graph illustrating the relationship between temperature and storage modulus is shown in Figure 1. As shown in Figure 1, the storage modulus of a reference film (a separator for an electricity storage device that does not contain silane-modified polyolefin) in the temperature range of -50°C to 225°C is compared with that of the crosslinked film, and the transition temperature between the rubber-like plateau region and the crystalline melting flow region can be confirmed in Figure 1. The transition temperature is the temperature at the intersection of a straight line extending the baseline on the high temperature side to the low temperature side and a tangent drawn at the inflection point of the curve of the crystalline melting change portion. An example of a graph illustrating the relationship between temperature and loss modulus is shown in Figure 2. Figure 2 compares the loss modulus of a reference film (a separator for an electricity storage device that does not contain silane-modified polyolefin) and a crosslinked film in the temperature range of -50°C to 220°C, and shows the transition temperatures determined by the same method as in Figure 1. In this technical field, the storage modulus and loss modulus are expressed by the following formula: tan δ=E'' / E' {wherein tan δ represents the loss tangent, E' represents the storage modulus, and E'' represents the loss modulus.} It is compatible according to. In addition, the mixed storage modulus ratio (R E’mix ) or mixed loss modulus ratio (R E’’mix In the measurement of E', a microporous membrane made of silane-unmodified polyolefin with a gelation degree of about 0% was used as a separator for a storage device that does not contain silane-modified polyolefin. a , E' 0、 E'' aRegarding E''0, if no breakage (sudden drop in elastic modulus) was observed in the sample between 160°C and 220°C, it was calculated from the average value between 160°C and 220°C, and if breakage was observed in the sample between 160°C and 220°C, it was calculated from the average value from 160°C to the temperature at the breakage point. For example, the reference film shown in Figures 1 and 2 broke at 207°C.

[0241] <Storage modulus, loss modulus and transition temperature (version 2)> Dynamic viscoelasticity of the separator can be measured using a dynamic viscoelasticity measuring device, and the storage modulus (E'), loss modulus (E''), and transition temperature between the rubber-like plateau region and the crystalline melting flow region can be calculated. R E’X ) is expressed by the following formula (1), and the mixed storage modulus ratio (R E’mix ) is calculated according to the following formula (2): E’’x ) is calculated according to the following formula (3): E’’mix ) were calculated according to the following formula (4). The measurement conditions were as follows: RSA-G2 dynamic viscoelasticity measuring device manufactured by TA Instruments, measuring frequency 1 Hz, strain 0.2%, temperature range of -50℃ to 310℃ under nitrogen atmosphere, and other conditions were according to the above version 1. The storage modulus and loss modulus were measured. E' Z and E' Z0 and E'' Z and E'' Z0 was the average value of each storage modulus or each loss modulus at 160°C to 300°C in the dynamic viscoelasticity measurement data. E' and E'0, and E'' and E''0 were the average values ​​of each storage modulus or each loss modulus at 160°C to 300°C in the dynamic viscoelasticity measurement data. R E’X =E' Z / E' Z0 (1) Comparison before and after injection into the cell R E’mix =E' / E'0(2) Comparison of the presence or absence of amorphous cross-linked structure R E’’X =E'' Z / E'' Z0(3) Comparison before and after injection into the cell R E’’mix =E'' / E''0(4) Comparison of the presence or absence of amorphous cross-linked structure

[0242] An example of a graph illustrating the relationship between temperature and storage modulus is shown in Fig. 9. As shown in Fig. 9, the storage modulus of a reference film (a separator for an electricity storage device not having an amorphous crosslinked structure) in the temperature range of -50°C to 310°C is compared with that of the crosslinked film, and the transition temperature between the rubber-like plateau region and the crystalline melting flow region can be confirmed in Fig. 9. The transition temperature is defined as the temperature at the intersection of a straight line extending the high-temperature baseline to the low-temperature side and a tangent drawn at the inflection point of the curve of the crystalline melting change portion.

[0243] An example of a graph illustrating the relationship between temperature and loss modulus is shown in Fig. 10. Fig. 10 compares the loss modulus of a reference film (a separator for an electricity storage device that does not contain silane-modified polyolefin) and a crosslinked film in the temperature range of -50°C to 310°C, and shows the transition temperatures determined by the same method as in Fig. 9. In this technical field, the storage modulus and the loss modulus are expressed by the following formula: tan δ=E'' / E' {wherein tan δ represents the loss tangent, E' represents the storage modulus, and E'' represents the loss modulus.} It is compatible according to.

[0244] In addition, the mixed storage modulus ratio (R E’mix ) or mixed loss modulus ratio (R E’’mix In the measurement of E', E', a polyolefin microporous film with a gelation degree of about 0% was used as a separator for a storage device that does not have an amorphous crosslinked structure. 0、 Regarding E'' and E''0, if no breakage (sudden drop in elastic modulus) of the sample was observed between 160°C and 300°C, they were calculated from the average value between 160°C and 300°C, and if breakage of the sample was observed between 160°C and 300°C, they were calculated from the average value from 160°C to the temperature at the breakage point. For example, the reference film shown in Tables 11 and 12 and Figures 9 and 10 showed breakage at 210°C.

[0245] In this specification, the separator for an electric storage device not having a crosslinked structure in the amorphous part can be a separator manufactured with a composition in which any one selected from the group consisting of polyethylene:X (viscosity average molecular weight 100,000 to 400,000), PE:Y (viscosity average molecular weight 400,000 to 800,000) and PE:Z (viscosity average molecular weight 800,000 to 9 million) or two or three selected from the group consisting of X, Y and Z are mixed in any ratio. In addition, polyolefins composed only of a hydrocarbon skeleton such as low density polyethylene:LDPE, linear low density polyethylene:LLDPE, polypropylene:PP, and olefin-based thermoplastic elastomers may be added to the mixed composition. More specifically, the separator for an electric storage device not having a crosslinked structure in the amorphous part can mean a polyolefin microporous film in which the rate of change in solid content before and after heating at 160°C in a decalin solution (hereinafter referred to as "gelation degree") is 10% or less. In addition, when measuring the gelation degree, the solid content means only the resin and does not include other materials such as inorganic substances. On the other hand, the gelation degree of a polyolefin microporous membrane having an amorphous part crosslinked structure such as a silane crosslinked structure is preferably 30% or more, more preferably 70% or more.

[0246] <Storage modulus, loss modulus, film softening transition temperature, and film rupture temperature (version 3)> The solid viscoelasticity of the separator is measured using a dynamic viscoelasticity measuring device, and the storage modulus (E'), loss modulus (E''), and film-softening transition temperature can be calculated. The conditions for the solid viscoelasticity measurement were as follows (i) to (iv). (i) Dynamic viscoelasticity measurements were performed under the following conditions: Measurement device used: RSA-G2 (manufactured by TA Instruments) Sample thickness: 200μm to 400μm (However, if the thickness of the sample itself is less than 200μm, multiple samples are stacked together and the dynamic viscoelasticity measurement is performed so that the total thickness is within the range of 200μm to 400μm.) Measurement temperature range: -50℃~250℃ Heating rate: 10℃ / min ·Measurement frequency: 1Hz Deformation mode: Linear tension Initial static tensile load: 0.2N Initial gap distance (at 25°C): 10mm Auto strain adjustment: Disabled It is done by. (ii) The static tensile load refers to the midpoint between the maximum and minimum stresses in each cyclic motion, and the sinusoidal load refers to the oscillatory stress centered on the static tensile load; (iii) The sinusoidal tension mode refers to measuring the vibratory stress while performing periodic motion with a fixed amplitude of 0.1%. In the sinusoidal tension mode, the gap distance and the static tensile load are varied so that the difference between the static tensile load and the sinusoidal load is within 5%, and the vibratory stress is measured. When the sinusoidal load becomes 0.1 N or less, the static tensile load is fixed at 0.1 N and the vibratory stress is measured. (iv) The relationship between the obtained sinusoidal load and the amplitude value, and the following formula: σ * =σ0·Exp[i(ωt+δ)], ε * = ε0·Exp(iωt), σ * =E * ε * E * =E'+iE'' {where, σ * : Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * : Complex modulus, E': Storage modulus, E'': Loss modulus Vibration stress: sinusoidal load / initial cross-sectional area Static tensile load: Load at the minimum point of vibration stress in each cycle (minimum point of gap distance in each cycle) Sinusoidal load: the difference between the measured oscillatory stress and the static tensile load The storage modulus (E') and loss modulus (E'') are calculated from the above. The average of the maximum and minimum values ​​of E' is also taken as the average E' (E' ave) is calculated, and the average value of the maximum value and the minimum value of E’’ is defined as the average E’’ (E’’ ave ) is calculated.

[0247] Note that E’ and E’’ are calculated as the maximum value and the minimum value of each storage modulus or each loss modulus at -50°C to 250°C in the dynamic viscoelasticity measurement data. More specifically, when no breakage (sudden decrease in modulus) of the sample is observed at -50°C to 250°C, the maximum value and the minimum value at -50°C to 250°C are calculated, and the value at the temperature at which breakage of the sample is observed at -50°C to 250°C is taken as the minimum value. Also, in the present technical field, the storage modulus and the loss modulus are interchangeable according to the following formula: tanδ = E’’ / E’ {In the formula, tanδ represents the loss tangent, E’ represents the storage modulus, and E’’ represents the loss modulus.} are interchangeable according to.

[0248] The film softening transition point temperature is defined as the temperature of the minimum value obtained by differentiating the curve of the sample gap distance in the dynamic viscoelasticity measurement data by the first order. Also, the film breakage temperature is defined as the temperature at which breakage (sudden decrease in modulus) of the sample is observed in the dynamic viscoelasticity measurement data, and the measurement limit temperature may be defined as 250°C from the viewpoint that the thermal decomposition reaction of the polyolefin resin proceeds. However, since the phenomenon can be understood in the same way even in measurement at temperatures higher than 250°C, in the present embodiment, a separator for a power storage device having a film breakage temperature of 180°C or higher can be implemented.

[0249] <Film breakage temperature of layer A> Using the constant length mode of TMA50 (trademark) manufactured by Shimadzu Corporation, the environmental temperature was changed from 25 to 250°C, and the temperature at the moment when the load was completely released was defined as the TMA film breakage temperature (the film breakage temperature of layer A measured by TMA). Specifically, a TD of 3 mm and MD of 14 mm was taken from layer A and used as a sample piece (sample piece with MD as the long side). Both ends of the sample piece in MD were set on a dedicated probe so that the chuck distance was 10 mm, and a load of 1.0 g was applied to the sample piece. The furnace in which the test piece was placed was heated, and the temperature at which the load reached 0 g was taken as the film rupture temperature (°C). When measuring a sample piece TD whose long side is TD, layer A is taken at TD 14 mm and MD 3 mm, and this is used as the sample piece. Both ends of TD are chucked to a dedicated probe, the chuck distance is set to 10 mm, an initial load of 1.0 g is applied, and the same operation as above is performed.

[0250] <Heat shrinkage rate at 150℃> A TD100mm and MD100mm sample was taken from the laminate (a laminate including layers A and B) before the formation of the crosslinked structure, and this was used as a sample piece. The sample piece was then left to stand in an oven at 150°C for 1 hour. At this time, the sample piece was sandwiched between two pieces of paper so that the hot air would not directly hit the sample piece. After removing the sample piece from the oven and cooling, the area of ​​the sample piece was measured, and the thermal shrinkage rate (T1) at 150°C before the formation of the crosslinked structure was calculated using the following formula. Heat shrinkage rate at 150℃ (%) = (10,000 (mm 2 )-Area of ​​the sample piece after heating (mm 2 ))×100 / 10,000 In addition, for the laminate after the formation of the crosslinked structure, a sample piece was taken at TD 100 mm and MD 100 mm, and the same operation as above was carried out to calculate the thermal shrinkage rate (T2) at 150°C after the formation of the crosslinked structure. The ratio (T2 / T1) was obtained by dividing the thermal shrinkage rate (T2) by the thermal shrinkage rate (T1). This ratio (T2 / T1) value corresponds to the rate of change in the thermal shrinkage rate (T2) at 150°C after the formation of the crosslinked structure relative to the thermal shrinkage rate (T1) at 150°C before the formation of the crosslinked structure.

[0251] <Battery Destruction Safety Test 1> In the battery destruction safety test 1, an iron nail is driven into a battery charged to 4.5V at a speed of 20mm / sec, penetrating it and causing an internal short circuit. This test can clarify the phenomenon that occurs during an internal short circuit by measuring the time change behavior of the voltage drop of the battery due to an internal short circuit and the behavior of the rise in the battery surface temperature due to an internal short circuit. In addition, insufficient shutdown function of the separator or rupture at low temperatures during an internal short circuit may cause the battery to suddenly heat up, which may cause the electrolyte to ignite and the battery to smoke and / or explode.

[0252] (Preparation of batteries used in battery destruction safety test 1) 1a. Preparation of the positive electrode As the positive electrode active material, 92.2 mass% of lithium cobalt composite oxide LiCoO2, 2.3 mass% each of flake graphite and acetylene black as conductive materials, and 3.2 mass% of polyvinylidene fluoride (PVDF) as a resin binder were collected and dispersed in N-methylpyrrolidone (NMP) to prepare a slurry. This slurry was applied to one side of a 20 μm thick aluminum foil that serves as a positive electrode current collector using a die coater, dried at 130 ° C for 3 minutes, and then compression molded using a roll press machine. At this time, the amount of active material applied to the positive electrode was 250 g / m 2 , the bulk density of the active material is 3.00 g / cm 3 It was adjusted to be.

[0253] 1b. Preparation of negative electrode A slurry was prepared by dispersing 96.9% by mass of artificial graphite as the negative electrode active material, and 1.4% by mass of ammonium salt of carboxymethylcellulose and 1.7% by mass of styrene-butadiene copolymer latex as the resin binder in purified water. This slurry was applied to one side of a 12 μm-thick copper foil serving as a negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press. At this time, the amount of active material applied to the negative electrode was 106 g / m 2 , the bulk density of the active material is 1.35 g / cm 3 It was adjusted to be.

[0254] 1c. Preparation of non-aqueous electrolyte A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L.

[0255] 1d. Battery assembly The separator was cut to 60 mm in the transverse (TD) direction and 1000 mm in the longitudinal (MD) direction, folded zigzag around the separator, and the positive and negative electrodes were alternately stacked between the separators (12 positive electrodes, 13 negative electrodes). The positive electrodes had an area of ​​30 mm x 50 mm, and the negative electrodes had an area of ​​32 mm x 52 mm. The zigzag laminate was placed in a laminate bag, and the nonaqueous electrolyte obtained in c. above was poured in and sealed. After leaving it at room temperature for one day, the battery was charged at a current value of 3 mA (0.5 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and the current value was started to be reduced from 3 mA so as to maintain 4.2 V after reaching that voltage, for a total of 6 hours, in the first charge after the battery was made. Then, the battery was discharged at a current value of 3 mA (0.5 C) down to a battery voltage of 3.0 V.

[0256] (Maximum heat release rate) After an iron nail was inserted into the resulting battery, the battery surface temperature was measured over a period of 300 seconds using a thermocouple. From the temperature change graph, the rate at which the temperature rise per second was the greatest was determined to be the maximum heat generation rate.

[0257] (Voltage drop time) An iron nail was inserted into the resulting battery, and the time required for the voltage to drop from 4.5 V to 3 V was determined as the voltage drop time (3 V drop time).

[0258] <Evaluation of cycle characteristics and method of fabricating the battery> A battery for evaluating cycle characteristics was prepared according to the same methods as 1a. to 1c. of the battery preparation method used in the above item <Battery Destruction Safety Test 1>, except that the assembly was performed according to the following 1d-2.

[0259] 1d-2. Battery assembly The separator was cut into a circle with a diameter of 18 mm, and the positive and negative electrodes were cut into a circle with a diameter of 16 mm. The positive electrode, separator, and negative electrode were stacked in this order so that the active material surfaces of the positive and negative electrodes faced each other, and then stored in a stainless steel metal container with a lid. The container and the lid were insulated, and the container was in contact with the copper foil of the negative electrode, and the lid was in contact with the aluminum foil of the positive electrode. The nonaqueous electrolyte obtained in 1c. of the above item <Battery Destruction Safety Test 1> was poured into this container and sealed. After leaving it at room temperature for one day, the battery was charged at a current value of 3 mA (0.5 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and after reaching the voltage, the current value was started to be reduced from 3 mA so as to maintain 4.2 V, for a total of 6 hours, in the first charging after the battery was made. Then, the battery was discharged at a current value of 3 mA (0.5 C) down to a battery voltage of 3.0 V.

[0260] The obtained battery was charged and discharged 100 times in an atmosphere of 60°C. The battery was charged at a current value of 6.0mA (1.0C) until the battery voltage reached 4.2V, and then the current value was reduced from 6.0mA to maintain the battery voltage at 4.2V. The battery was discharged at a current value of 6.0mA (1.0C) until the battery voltage reached 3.0V.

[0261] (Cycle characteristic evaluation 1) The capacity retention rate was calculated from the discharge capacity at the 100th cycle and the discharge capacity at the 1st cycle. A high capacity retention rate was evaluated as having good cycle characteristics.

[0262] (Cycle characteristic evaluation 2) The capacity retention rate (%) was calculated from the discharge capacity at the 300th cycle and the discharge capacity at the 1st cycle according to the following formula. A high capacity retention rate was evaluated as having good cycle characteristics. Evaluation result (%) = (100 x retention capacity after 300 cycles / discharge capacity at 1st cycle)

[0263] <Fuse / Meltdown (F / MD) characteristics> (i) 0.5 MPa pressure and 2°C / min heating rate The positive electrode, separator, and negative electrode were cut into a circular shape with a diameter of 200 mm, overlapped, and a nonaqueous electrolyte was added to the resulting laminate and allowed to soak into the entire laminate. The laminate was sandwiched in the center of a circular aluminum heater with a diameter of 600 mm, and the aluminum heater was pressurized from above and below to 0.5 MPa with a hydraulic jack, completing the preparation for the measurement. The resistance (Ω) between the electrodes was measured while the laminate was heated with the aluminum heater at a temperature increase rate of 2°C / min. The temperature at which the resistance between the electrodes, including the separator fuse, rose and exceeded 1000Ω for the first time was taken as the fuse temperature (shutdown temperature). Furthermore, the temperature at which the resistance dropped to 1000Ω or less after further heating was taken as the meltdown temperature (film rupture temperature).

[0264] (ii) Maximum pressure of 10 MPa and heating rate of 15°C / min The positive electrode, separator, and negative electrode were cut into a circular shape with a diameter of 200 mm, and the laminate obtained by overlapping them was added with a nonaqueous electrolyte and permeated throughout. The laminate was sandwiched in the center of a circular aluminum heater with a diameter of 600 mm, and pressure was applied to the aluminum heater from above and below with a hydraulic jack up to 10 MPa, completing preparation for measurement. The resistance (Ω) between the electrodes was measured while heating the laminate with the aluminum heater at a temperature increase rate of 15°C / min. The temperature at which the resistance between the electrodes rose and exceeded 1000Ω for the first time was taken as the shutdown temperature (°C). Furthermore, heating was continued, and the temperature at which the resistance dropped to 1000Ω or less was taken as the meltdown temperature (°C).

[0265] For both evaluations of (i) and (ii), a wire for measuring resistance was attached with conductive silver paste to the back of the aluminum foil of the positive electrode prepared in "1a. Preparation of the positive electrode" in the above item <Battery Destruction Safety Test 1>. Also, a wire for measuring resistance was attached with conductive silver paste to the back of the copper foil of the negative electrode prepared in "1b. Preparation of the negative electrode" in the above item <Battery Destruction Safety Test 1>. Furthermore, the electrolyte-containing electrolyte prepared in "1c. Preparation of the non-aqueous electrolyte" in the above item <Battery Destruction Safety Test 1> was also used for the F / MD characteristic test.

[0266] <Safety test (nail penetration test) 2> 2a. Preparation of the positive electrode The positive electrode active material was nickel, manganese, and cobalt composite oxide (NMC) (Ni:Mn:Co=1:1:1 (element ratio), density 4.70 g / cm 3 ) 90.4% by mass, graphite powder (KS6) (density 2.26 g / cm3) as a conductive additive 3 , number average particle diameter 6.5 μm) at 1.6 mass%, and acetylene black powder (AB) (density 1.95 g / cm 3 , number average particle diameter 48 nm) 3.8 mass%, and PVDF (density 1.75 g / cm3) as a resin binder. 3 ) at a ratio of 4.2% by mass, and dispersed in NMP to prepare a slurry. This slurry was applied to one side of an aluminum foil having a thickness of 20 μm, which was to be a positive electrode current collector, using a die coater, and dried at 130° C. for 3 minutes, and then compression molded using a roll press to prepare a positive electrode. At this time, the amount of the positive electrode active material applied was 109 g / m 2 It was.

[0267] 2b. Preparation of negative electrode Graphite powder A (density 2.23 g / cm) was used as the negative electrode active material. 3 , number average particle size 12.7 μm) 87.6 mass%, and graphite powder B (density 2.27 g / cm 3 A slurry was prepared by dispersing 9.7% by mass of carboxymethylcellulose (number average particle diameter 6.5 μm) as a resin binder (solid content equivalent) (aqueous solution with a solid content concentration of 1.83 mass%) and 1.7% by mass of diene rubber latex (solid content equivalent) (aqueous solution with a solid content concentration of 40 mass%) in purified water. This slurry was applied to one side of a 12 μm-thick copper foil serving as a negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press machine to produce a negative electrode. At this time, the amount of negative electrode active material applied was 52 g / m 2 It was.

[0268] 2c. Preparation of non-aqueous electrolyte A non-aqueous electrolyte solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate=1:2 (volume ratio) to a concentration of 1.0 mol / L.

[0269] 2d. Battery construction Using the positive electrodes, negative electrodes, and nonaqueous electrolytes obtained in 2a to 2c above, as well as a separator (the separator of the Example or the separator of the Comparative Example), a laminate-type secondary battery having a size of 100 mm × 60 mm and a capacity of 3 Ah was produced by constant-current constant-voltage (CCCV) charging for 3 hours under conditions of a current value of 1 A (0.3 C) and an end-of-battery voltage of 4.2 V.

[0270] 2e. Nail penetration evaluation The laminated secondary battery thus fabricated was placed on an iron plate in a temperature-controllable explosion-proof booth. The temperature in the explosion-proof booth was set to 40°C, and an iron nail with a diameter of 3.0 mm was inserted into the center of the laminated secondary battery at a speed of 2 mm / sec. The nail was then maintained in the penetrated state. The temperature of a thermocouple installed inside the nail so that the temperature inside the laminated battery could be measured after the nail had penetrated was measured, and the presence or absence of ignition was evaluated. The evaluation was repeated using newly prepared laminated secondary batteries in the same manner, and the number of samples that did not ignite (no ignition) was calculated as a percentage using the following formula. Evaluation result (%) = (100 x number of samples that did not ignite / total number of samples) The pass rate for the nail penetration evaluation is preferably, for example, 50% or more at 200 cycles and 5% or more at 1000 cycles.

[0271] <Experimental Group I> [Method for producing silane-grafted polyolefin] The raw polyolefin used for the silane graft modified polyolefin may have a viscosity average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number average molecular weight of 10,000 or more and 150,000 or less, and may be a propylene or butene copolymerized α-olefin. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) is added to generate radicals in the polymer chain of the α-olefin, and then a trimethoxyalkoxide-substituted vinylsilane is injected to introduce an alkoxysilyl group into the α-olefin polymer by an addition reaction, forming a silane graft structure. At the same time, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-tetra-butyl-4-hydroxyphenyl) propionate]) is added to adjust the radical concentration in the system, suppressing the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water and pelletized, and then heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is about 10 to 1500 ppm. The silane-grafted modified polyolefin obtained by the above-mentioned production method is referred to as "Silane-modified polyolefin (B)" in Table 8.

[0272] [Example I-1] A mixture was obtained by dry blending 79.2% by mass of homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by mass of silane-grafted polyethylene (silane-modified polyethylene (B)) with a MFR (190°C) of 0.4 g / min obtained by modifying polyolefin with a viscosity average molecular weight of 20,000 with trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 0.8 and 0.2, respectively), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C 7.59×10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled at 25° C., to obtain a gel sheet (sheet-shaped molded product) having a thickness of 1,400 μm. Next, the sheet-shaped molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 6.0 times (i.e., 7×6 times), and the biaxial stretching temperature was 125° C. Next, the stretched gel sheet was introduced into a methyl ethyl ketone tank and thoroughly immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then the methyl ethyl ketone was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for heat setting (HS), and HS was performed at a heat setting temperature of 125°C and a stretch ratio of 1.8 times, and then a relaxation operation of 0.5 times in the TD direction (i.e., the HS relaxation rate was 0.5 times) was performed to obtain a microporous membrane. Thereafter, the ends of the obtained microporous membrane were cut off and taken up into a mother roll having a width of 1,100 mm and a length of 5,000 m. In the above evaluation, the microporous membrane unwound from the mother roll was slit as necessary and used as a separator for evaluation.

[0273] [Examples I-2 to I-6] The microporous membranes shown in Table 8 were obtained in the same manner as in Example I-1 above, except that the ratio of components A and B and the crosslinking method and conditions were changed as shown in Table 8.

[0274] [Comparative Examples I-1, I-2] A mixture was obtained by dry blending 79.2% by mass of homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by mass of silane-grafted polyethylene (silane-modified polyethylene (B)) with a MFR (190°C) of 0.4 g / min obtained by modifying polyolefin with a viscosity average molecular weight of 20,000 with trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 0.8 and 0.2, respectively), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C 7.59×10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled at 25° C., to obtain a gel sheet (sheet-shaped molded product) having a thickness of 1,400 μm. Next, the sheet-shaped molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 6.0 times (i.e., 7×6 times), and the biaxial stretching temperature was 125° C. Next, the stretched gel sheet was introduced into a methyl ethyl ketone tank and thoroughly immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then the methyl ethyl ketone was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for heat setting (HS), where HS was performed at a heat setting temperature of 125° C. and a stretch ratio of 1.8 times, followed by a relaxation operation of 0.5 times in the TD direction (i.e., the HS relaxation ratio was 0.5 times). The heat-treated porous body was then introduced into an ethanol bath (affinity treatment tank) and allowed to remain there while being immersed for 60 seconds to carry out affinity treatment thereon, thereby obtaining an affinity-treated porous body. Furthermore, in Comparative Example I-1, the affinity-treated porous body was introduced into a 25% caustic soda aqueous solution (temperature 80°C, pH 8.5 to 14), and in Comparative Example I-2, the affinity-treated porous body was introduced into a 10% hydrochloric acid aqueous solution (temperature 60°C, pH 1 to 6.5) and immersed therein for 60 seconds, thereby performing a crosslinking treatment on the affinity-treated porous body and obtaining a crosslinked porous body. The crosslinked porous body was then introduced into water (a water-washing tank) and immersed therein for 60 seconds to wash the crosslinked porous body, which was then introduced into a conveyor dryer and dried at 120° C. for 60 seconds to obtain a microporous membrane. Thereafter, the ends of the obtained microporous membrane were cut off and taken up into a mother roll having a width of 1,100 mm and a length of 5,000 m. In the above evaluation, the microporous membrane unwound from the mother roll was slit as necessary and used as a separator for evaluation.

[0275] [Evaluation Results] The microporous membranes and batteries obtained in Examples I-1 to I-6 and Comparative Examples I-1 to I-2 were subjected to various evaluations according to the evaluation methods described above, and the evaluation results are also shown in Table 8. FIG. 3 shows the relationship between temperature and resistance of a battery equipped with the microporous membrane obtained in Example I-1 as a separator. FIG. 3 and Table 8 show that the shutdown temperature of the separator obtained in Example I-1 is 143°C and the membrane rupture temperature is 200°C or higher. Furthermore, the separator obtained in Example I-1 in a pre-crosslinked state is 1 H and 13 The C-NMR chart (b) is shown in Figure 13.

[0276] [Table 8]

[0277] In addition, "Silane-modified polyethylene (B)" in Table 8 is obtained by a modification reaction with trimethoxyalkoxide-substituted vinylsilane using a polyolefin having a viscosity average molecular weight of 20,000 as a raw material, and has a density of 0.95 g / cm 3 and a silane-modified polyethylene having a melt flow rate (MFR) of 0.4 g / min at 190°C.

[0278] <Experimental Group IIa> [Method for producing silane-grafted polyolefin] The raw polyolefin used for the silane graft modified polyolefin may have a viscosity average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number average molecular weight of 10,000 or more and 150,000 or less, and may be an ethylene homopolymer or a copolymerized α-olefin of ethylene and propylene or butene. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) is added to generate radicals in the polymer chain of the α-olefin, and then a trimethoxyalkoxide-substituted vinylsilane is injected to introduce an alkoxysilyl group into the α-olefin polymer by an addition reaction, forming a silane graft structure. At the same time, in order to adjust the radical concentration in the system, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-tetra-butyl-4-hydroxyphenyl) propionate]) is added to suppress the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water and pelletized, and then heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is about 1500 ppm or less. The silane-grafted modified polyethylene obtained by the above-mentioned production method is referred to as "Silane-modified polyethylene (B)" in Table 9. Example II-1 A mixture was obtained by dry blending a mixture of 80% by mass of homopolymer polyethylene (polyethylene (A)) having a weight average molecular weight of 700,000, 20% by mass of silane-grafted polyethylene (silane-modified polyethylene (B)) having an MFR (190°C) of 0.4 g / min, which is obtained by modifying a polyolefin having a viscosity average molecular weight of 10,000 with a trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 80% and 20%, respectively), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C: 7.59 x 10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die and cast onto a cooling roll whose surface temperature was controlled at 25° C., to obtain a gel sheet (sheet-shaped molded product) having a thickness of 1100 μm. Next, the sheet-like molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 6.2 times, and biaxial stretching temperature of 120°C. Next, the stretched gel sheet was introduced into a dichloromethane tank and thoroughly immersed in dichloromethane to extract and remove the liquid paraffin, and then the dichloromethane was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for heat setting (HS), where HS was performed at a heat setting temperature of 133° C. and a stretch ratio of 2.1 times, and then a relaxation operation was performed to a stretch ratio of 2.0 times in the TD direction. Thereafter, the ends of the obtained microporous membrane were cut off and taken up into a mother roll having a width of 1,100 mm and a length of 5,000 m. In the above evaluation, the microporous membrane unwound from the mother roll was slit as necessary and used as a separator for evaluation.

[0279] [Examples II-2 to II-8, Comparative Examples II-1 to II- 2. Example II-3b 〕 The microporous membranes shown in Table 9 were obtained by the same procedure as in Example II-1, except that the ratio of components A and B, the presence or absence of other resins (C) as additional components, the membrane properties, and the crosslinking method and conditions were changed as shown in Table 9. Note that the component "PP" in Table 9 refers to a PP having an MFR of 2.5 g / 10 min or less and a density of 0.89 g / cm, measured under conditions of a temperature of 230°C and a mass of 2.16 kg. 3 The above silane-unmodified polypropylene was used. In the crosslinking method "alkali treatment crosslinking" in Table 9, the sample was treated with a 25% aqueous solution of caustic soda (temperature 80°C, pH 8.5 to 14).

[0280] [Evaluation results] Examples II-1 to II-8 、 Comparative Examples II-1 to II- 2, and Example II-3b The microporous membrane and battery obtained in were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are also shown in Table 9. Regarding the viscoelasticity measurement when the obtained microporous membrane was used as a separator for an electricity storage device, the relationship between temperature, gap distance, storage modulus, and loss modulus is shown in FIG. 4(a) for Example II-1 and in FIG. 4(b) for Comparative Example II-1, and further, the membrane softening transition temperature determined based on the temperature, gap distance, and first derivative of gap displacement is shown in FIG. 5(a) for Example II-1 and in FIG. 5(b) for Comparative Example II-1. Examples II-1 to II-8 and Example II-3b In this case, no film rupture was observed at the measurement limit temperature of 250° C. In Example II-1 and Comparative Example II-1, 26 films each having a thickness of 8 μm were stacked, and the storage modulus, loss modulus, film softening transition temperature, and film rupture temperature were measured under the condition that the total sample thickness was 208 μm.

[0281] [Table 9A]

[0282] [Table 9B]

[0283] <Experiment Series IIb> [Reference membrane] As a separator for an electricity storage device that does not contain silane-modified polyolefin (hereinafter referred to as the "reference membrane"), a silane-grafted non-modified polyolefin microporous membrane was used, in which the rate of change in solid content before and after heating in a decalin solution at 160°C (hereinafter referred to as the "gelation degree") was about 0%. When measuring the gelation degree, the solid content means only the resin and does not include other materials such as inorganic substances. In this specification, a separator for an electricity storage device that does not contain a silane-grafted modified polyolefin can be produced from a composition in which any one type selected from the group consisting of polyethylene (PE):X (viscosity average molecular weight of 100,000 to 400,000), PE:Y (viscosity average molecular weight of 400,000 to 800,000) and PE:Z (viscosity average molecular weight of 800,000 to 9 million) or two or three types selected from the group consisting of X, Y and Z are mixed in any ratio. Polyolefins composed only of a hydrocarbon skeleton, such as low-density polyethylene:LDPE, linear low-density polyethylene:LLDPE, polypropylene:PP, and olefin-based thermoplastic elastomers, may be added to the mixed composition.

[0284] [Crosslinked membrane] As the separator for the storage battery device after the silane crosslinking reaction (hereinafter referred to as "crosslinked membrane"), the polyolefin microporous membrane of Example II-1 after contact with the electrolyte solution described above, or the polyolefin microporous membrane of Example II-1 taken out from the cell after the first charge / discharge, was dried and used. The gelation degree of the crosslinked membrane was 30% or more or 70% or more.

[0285] [Viscoelastic behavior] The standard membrane and the crosslinked membrane were measured for the above items (storage modulus, loss modulus, membrane softening transition temperature, and membrane rupture temperature (version 3)). The measurement results are shown in Table 10.

[0286] [Table 10]

[0287] <Experimental Group III>

[0288] [Method for producing silane-grafted polyolefin] The raw polyolefin used for the silane graft modified polyolefin may have a viscosity average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number average molecular weight of 10,000 or more and 150,000 or less, and may be a propylene or butene copolymerized α-olefin. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) is added to generate radicals in the α-olefin polymer chain, and then trimethoxyalkoxide-substituted vinylsilane is injected to introduce alkoxysilyl groups into the α-olefin polymer by an addition reaction, forming a silane graft structure. At the same time, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-tetra-butyl-4-hydroxyphenyl) propionate]) is added to adjust the radical concentration in the system, suppressing the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water and pelletized, and then heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is about 1000 to 1500 ppm. The silane-grafted modified polyolefin obtained by the above-mentioned method is shown in Tables 11 and 12 as "Silane-modified polyethylene."

[0289] [Production methods of modified PE and copolymers with various functional groups other than silane-modified PE] Modified PE and copolymers having various functional groups other than silane-modified PE were produced by the following methods. For each raw material, the molecular weight of the raw material used was adjusted so that the MI was within the range of 0.5 to 10. Modified PE with hydroxyl groups was produced by saponifying and neutralizing EVA copolymer. Modified resins such as amine-modified and oxazoline-modified resins were produced by reacting the terminal vinyl groups of PE polymerized using a chromium catalyst with a tungsten-based catalyst under hydrogen peroxide conditions to convert the vinyl groups to epoxy groups. After that, the target reaction site was converted to the desired functional group using a known organic reaction for functional group conversion to obtain various modified PEs. For example, in the case of amine-modified PE, primary or secondary amines were injected as a liquid while the modified PE with epoxy groups was melt-kneaded in an extruder at 200°C, and reacted. After that, unreacted amines were removed from the pressure reducing valve, and the obtained amine-modified resin was extruded into strands and cut into pellets. The modified PE obtained by the above-mentioned method is shown in Tables 11 and 12 as a type of "Modified PE or Copolymer (B)".

[0290] [Example III-1] A mixture was obtained by dry blending 79.2% by mass of homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by mass of silane-grafted polyethylene (PE (B)) with an MFR of 0.4 g / min obtained by modifying polyolefin with a viscosity average molecular weight of 20,000 with trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 0.8 and 0.2, respectively), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C: 7.59×10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled at 25° C., to obtain a gel sheet (sheet-shaped molded product) having a thickness of 1,400 μm. Next, the sheet-shaped molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 6.0 times (i.e., 7×6 times), and the biaxial stretching temperature was 125° C. Next, the stretched gel sheet was introduced into a methyl ethyl ketone tank and thoroughly immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then the methyl ethyl ketone was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for heat setting (HS), and HS was performed at a heat setting temperature of 125°C and a stretch ratio of 1.8 times, and then a relaxation operation of 0.5 times in the TD direction (i.e., the HS relaxation rate was 0.5 times) was performed to obtain a microporous membrane. Thereafter, the ends of the obtained microporous membrane were cut off and taken up into a mother roll having a width of 1,100 mm and a length of 5,000 m. In the above evaluation, the microporous membrane unwound from the mother roll was slit as necessary and used as a separator for evaluation. The separator and battery for evaluation were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are shown in Table 11.

[0291] [Examples III-2 to III-18] Microporous membranes and batteries shown in Table 11 or Table 12 were obtained by the same operation as in Example III-1, except that the types, amount ratio, and crosslinking method and conditions of Resins A and B were changed as shown in Table 11 or Table 12. The obtained microporous membranes and batteries were evaluated in accordance with the above-mentioned evaluation methods, and the evaluation results are also shown in Table 11 or Table 12. In Examples III-8 to III-10 and III-15 to III-18, an appropriate amount of an additive shown in Table 11 or Table 12 was dissolved in the electrolyte beforehand when the electrolyte was injected.

[0292] [Comparative Examples III-1, III-2] The same operation as in Example III-1 was performed to obtain the microporous membranes shown in Table 12, except that the types, amount ratios, and crosslinking methods and conditions of Resins A and B were changed as shown in Table 12. The obtained microporous membranes were irradiated with a predetermined dose of electron beam crosslinking. The obtained electron beam crosslinked microporous membranes and batteries were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are also shown in Table 12.

[0293] For Comparative Example III-2 and Example III-1, the strain amount-crystal refinement rate graph is shown in Figure 8 to observe the change in X-ray crystal structure during the tensile fracture test. In Figure 8, the microporous membrane of Comparative Example III-2 is shown as a dotted line "EB crosslinking", and the microporous membrane of Example III-1 is shown as a solid line "before chemical crosslinking" and a dashed line "after chemical crosslinking".

[0294] [Table 11A]

[0295] [Table 11B]

[0296] [Table 12A]

[0297] [Table 12B]

[0298] Explanation of Abbreviations in Tables 11 and 12 * "Silane-modified polyethylene" is obtained by a modification reaction with trimethoxyalkoxide-substituted vinylsilane using a polyolefin with a viscosity-average molecular weight of 20,000 as a raw material, and has a density of 0.95 g / cm 3 and is a silane-modified polyethylene with a melt flow rate (MFR) of 0.4 g / min at 190 °C. "-COOH modified PE", "-oxazoline modified PE", "-oxazoline, -OH modified PE", "-OH modified PE", "-OH, -NH- modified PE", and "-OH, amine modified PE" are all modified PEs obtained by the above [Production method of modified PEs and copolymers having various functional groups other than silane-modified PE]. ** (I) Condensation reaction of a plurality of identical functional groups (II) Reaction between a plurality of different functional groups (III) Chain condensation reaction of a functional group and an electrolyte (IV) Reaction of a functional group and an additive (V) Reaction in which a plurality of identical functional groups crosslink through a coordination bond with an eluted metal ion *** EC: Ethylene carbonate **** BS(PEG)5: Bis-succinimide at both ends, EO unit repeat number 5 Diisocyanate: A compound in which bis-isocyanate is linked to a hexane unit through a urethane bond Diepoxy compound: A compound in which bis-epoxide groups at both ends are linked to a butane unit

[0299] <Experimental Group IV>

[0300] [Example IV-1] [Preparation of Layer A] (Preparation of Silane Graft-Modified Polyolefin) The raw polyethylene was polyethylene with a viscosity average molecular weight of 120,000. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) was added to generate radicals in the polymer chain of the α-olefin, and then trimethoxyalkoxide-substituted vinylsilane was injected to introduce alkoxysilyl groups into the α-olefin polymer by an addition reaction to form a silane graft structure. At the same time, in order to adjust the radical concentration in the reaction system, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-tetra-butyl-4-hydroxyphenyl) propionate]) was added to suppress the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, pelletized, and then heated and dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets was about 1500 ppm or less. The modification reaction using trimethoxyalkoxide-substituted vinylsilane as described above yielded a silane-modified polyethylene with a MFR (190° C.) of 0.4 g / min.

[0301] (Preparation of layer A) A resin blend was formed by combining 65% by mass of homopolymer polyethylene having a weight average molecular weight of 800,000 with 35% by mass of the silane-modified polyethylene obtained above, and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] was added as an antioxidant to the blend, and the mixture was dry-blended using a tumbler blender to obtain a mixture. The resulting mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C: 7.59 x 10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. In an extruder, a mixture and liquid paraffin were melt-kneaded, and the feeder and pump were adjusted so that the ratio of the amount of liquid paraffin in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / hour. Subsequently, the melt-kneaded material was extruded and cast onto a cooling roll controlled at a surface temperature of 25°C through a T-die to obtain a gel sheet (sheet-shaped molded body) with an original film thickness of 1400 μm.

[0302] Next, the sheet-shaped molded body was introduced into a simultaneous biaxial tenter and biaxially stretched to obtain a stretched product. The set stretching conditions were an MD magnification of 7.0 times, a TD magnification of 6.3 times (i.e., 7×6.3 times), and a biaxial stretching temperature of 122°C. Next, the stretched gel sheet was introduced into a dichloromethane bath, sufficiently immersed in dichloromethane to extract and remove the liquid paraffin, and then dichloromethane was removed by drying to obtain a porous body. Next, the porous body was introduced into a TD tenter to perform heat setting (HS) at a heat setting temperature of 133°C and a stretching ratio of 1.8 times. Subsequently, a relaxation operation was performed up to 1.7 times in TD to obtain a microporous membrane. Thereafter, the obtained microporous membrane was cut at the ends and wound up as a mother roll with a width of 1,100 mm and a length of 5,000 m. At the time of the above evaluation, the microporous membrane unwound from the mother roll was slit as needed and used as the evaluation A layer. For the obtained evaluation A layer, the film thickness, air permeability, porosity, etc. were measured and shown in Table 13.

[0303] <Fabrication of B layer> A dispersion was prepared by uniformly dispersing 95 parts by mass of aluminum hydroxide oxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by mass (solid content equivalent) of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468 manufactured by San Nopco, solid content concentration 40%) as an ionic dispersant in 100 parts by mass of water. The obtained dispersion was crushed in a bead mill (cell volume 200 cc, zirconia bead diameter 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm, and an inorganic particle-containing slurry was prepared. Next, the microporous membrane was continuously unwound from the microporous membrane mother roll, and one side of the microporous membrane was coated with an inorganic particle-containing slurry using a gravure reverse coater, followed by drying in a dryer at 60°C to remove water and winding up to obtain a separator mother roll. At the time of evaluation, the separator unwound from the mother roll was slit as necessary and used as an evaluation separator.

[0304] [Examples IV-2 to IV-5, and implementation Example IV-1 b ~IV-2 b ] At least one of the weight average molecular weight of the polyethylene homopolymer, the set stretching conditions, the heat setting conditions, and the relaxation operation conditions was changed to achieve the physical property values ​​shown in Table 13. Also, the composition of layer B was changed as shown in Table 13. Apart from these changes, a separator was produced in the same manner as in Example IV-1, and the above evaluations were carried out using the obtained separator. The evaluation results are shown in Table 13. [Table 13]

[0305] <Experimental Group V> [Method for producing silane-grafted polyolefin] The raw polyolefin used for the silane graft modified polyolefin may have a viscosity average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number average molecular weight of 10,000 or more and 150,000 or less, and may be a propylene or butene copolymerized α-olefin. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) is added to generate radicals in the polymer chain of the α-olefin, and then a trimethoxyalkoxide-substituted vinylsilane is injected to introduce an alkoxysilyl group into the α-olefin polymer by an addition reaction, forming a silane graft structure. At the same time, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-tetra-butyl-4-hydroxyphenyl) propionate]) is added to adjust the radical concentration in the system, suppressing the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water and pelletized, and then heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is about 10 to 1500 ppm. The silane-grafted modified polyolefin obtained by the above-mentioned production method is referred to as "silane-modified polyethylene (B)" in Tables 14 to 16. The silane-grafted modified polyolefin used this time has a density of 0.94 g / cm 3 and the MFR is 0.65 g / min.

[0306] [Example V-1] (Formation of microporous membrane) A mixture was obtained by dry blending 79.2% by weight of homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by weight of silane-grafted polyethylene (silane-modified polyethylene (B)) with a MFR (190°C) of 0.4 g / min obtained by modifying polyolefin with a viscosity average molecular weight of 20,000 with trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 80% and 20%, respectively), and 1% by weight of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C 7.59×10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by weight (i.e., the polymer concentration was 30% by weight). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled at 25° C., to obtain a gel sheet (sheet-shaped molded product) having a thickness of 1,400 μm. Next, the sheet-shaped molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 6.0 times (i.e., 7×6 times), and the biaxial stretching temperature was 125° C. Next, the stretched gel sheet was introduced into a methyl ethyl ketone tank and thoroughly immersed in methyl ethyl ketone to extract and remove the liquid paraffin, and then the methyl ethyl ketone was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for heat setting (HS), and HS was performed at a heat setting temperature of 125°C and a stretch ratio of 1.8 times, and then a relaxation operation of 0.5 times in the TD direction (i.e., the HS relaxation rate was 0.5 times) was performed to obtain a microporous membrane. Thereafter, the ends of the obtained microporous membrane were cut off and the membrane was wound up into a microporous membrane mother roll having a width of 1,100 mm and a length of 5,000 m.

[0307] (Acrylic latex manufacturing method) The acrylic latex used as the resin binder is produced by the following method. Into a reaction vessel equipped with a stirrer, a reflux condenser, a dropping tank and a thermometer, 70.4 parts by mass of ion-exchanged water, 0.5 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) as an emulsifier, and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) were added. Next, the temperature inside the reaction vessel was raised to 80°C, and while maintaining the temperature at 80°C, 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate was added to obtain an initial mixture. Five minutes after the addition of the aqueous solution of ammonium persulfate was completed, the emulsion was dropped from the dropping tank into the reaction vessel over 150 minutes. The above emulsion was prepared by mixing 70 parts by mass of butyl acrylate, 29 parts by mass of methyl methacrylate, 1 part by mass of methacrylic acid, 3 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Dai-ichi Kogyo Seiyaku Co., Ltd.) and 3 parts by mass of "Adeka Reasoap SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) as emulsifiers, 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate, and 52 parts by mass of ion-exchanged water using a homomixer for 5 minutes. After the emulsion was added, the temperature inside the reaction vessel was kept at 80°C for 90 minutes, and then cooled to room temperature. The resulting emulsion was adjusted to pH 8.0 with 25% aqueous ammonium hydroxide solution, and a small amount of water was added to obtain an acrylic latex with a solid content of 40%. The resulting acrylic latex had a number average particle size of 145 nm and a glass transition temperature of -23°C.

[0308] (Formation of inorganic porous layer) A dispersion was prepared by uniformly dispersing 95 parts by weight of aluminum hydroxide oxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by weight (solid content equivalent) of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468 manufactured by San Nopco, solid content concentration 40%) as an ionic dispersant in 100 parts by weight of water. The obtained dispersion was crushed with a bead mill (cell volume 200 cc, zirconia bead diameter 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm. A slurry containing inorganic particles was prepared by adding 4.6 parts by weight (solid content equivalent) of acrylic latex (solid content concentration 40%, average particle size 145 nm, glass transition temperature -23 ° C, constituent monomers: butyl acrylate, methyl methacrylate, methacrylic acid) as a resin binder to the dispersion with the adjusted particle size distribution. Next, the microporous membrane was continuously unwound from the microporous membrane mother roll, and one side of the microporous membrane was coated with an inorganic particle-containing slurry using a gravure reverse coater, followed by drying in a dryer at 60°C to remove water and winding up to obtain a separator mother roll. At the time of evaluation, the separator unwound from the mother roll was slit as necessary and used as an evaluation separator.

[0309] [Examples V-2 to V-12, Comparative Example V-2] The microporous membranes shown in Tables 14 to 16 were obtained by the same procedure as in Example V-1, except that the ratio of components A and B, the presence or absence or composition of an inorganic layer, and the crosslinking method and conditions were changed as shown in Tables 14 to 16.

[0311] [Evaluation Results] Examples V-1 to V-1 2nd grade For the microporous membranes and batteries obtained in Comparative Example V-1 and Comparative Example V-2, various evaluations were performed according to the above-mentioned evaluation methods, and the evaluation results are also shown in Tables 14 to 16.

[0312] [Table 14]

[0313] [Table 15]

[0314] [Table 16]

[0315] <Experimental Group VI> Porous membranes were formed in the same manner as in Examples 1 to 3 and Comparative Examples 2 to 3 shown in Patent Document 5 (JP Patent Publication 2001-176484 A), and were designated as porous membranes V-1 to V-5, respectively. For the porous membranes V-1 to V-5, the gel fraction (%), heat resistance temperature (°C) and needle penetration strength (gf / 25 μm) were evaluated according to the method described in Patent Document 5, and further, the storage modulus and loss modulus change ratio R of the porous membrane V-4 before and after contact with the electrolyte solution were measured according to the above item <Storage modulus, loss modulus and transition temperature (version 1)> of this specification. △E’ and R △E’’ The results are shown in Table 17.

[0316] [Table 17]

[0317] The following points are evident from Table 17: (a) Even for the porous membrane V-4, which has the lowest gel fraction (Comparative Example 2 of Patent Document 5, gel fraction 36%), the elastic modulus change ratio remains at 1. This proves that all of the porous membranes V-1 to V-5 have already undergone the crosslinking reaction to the full extent, and that the porous membranes described in Patent Document 5 do not have self-crosslinking properties (uncrosslinked portions). (b) Comparative Example 1 in Patent Document 5 is an unmodified product.

[0318] (c) The separator according to the seventh embodiment of the present invention described above is valuable in that it selectively chemically crosslinks the amorphous zone between the crystalline and crystalline parts. When the silane-unmodified polyolefin and the silane-modified polyolefin form mixed crystals, the modified units are expelled into the amorphous parts and randomly dispersed, and the adjacent crosslinking units come into contact with each other, and the crosslinking reaction proceeds. On the other hand, if multiple crosslinking units are far apart from each other, even if the crosslinking units are present, they cannot contribute to the crosslinking reaction. In particular, the crosslinking reaction from silanol to siloxane in the porous membrane proceeds immediately when (all) reaction conditions are satisfied, and the units that can contribute to crosslinking can be sufficiently crosslinked, so that further crosslinking of the remaining units cannot proceed in the battery including the porous membrane. Therefore, even if residual silanol groups remain in the porous membrane as in the case of the porous membranes V-1 to V-5, if a crosslinking treatment is performed in the manufacturing process of the membrane, the crosslinking reaction will not proceed in the battery containing the membrane (i.e., the residual silanol groups cannot contribute to the crosslinked structure).

[0319] (d) For the separator according to the seventh embodiment of the present invention, the molecular weight, copolymer concentration, and compounding ratio of the raw resin were adjusted, and further, by combining with a stretching film-forming process, a crystal structure having a crystal distance and a dispersion distribution of the crosslinking units that allows the crosslinking reaction of the crosslinking units to proceed with a high probability was experimentally discovered. This made it possible to improve the fracture resistance and heat-resistant safety of the battery, and also to suppress the deterioration of the battery cycle performance due to the remaining heterofunctional groups.

Claims

1. A separator for an electricity storage device containing polyolefin, which is made of a wet biaxially stretched polyolefin microporous membrane, wherein an amorphous portion of the polyolefin has a crosslinked amorphous portion crosslinked structure in which crosslinking points are localized only in the amorphous portion, and in an electricity storage device containing the separator for an electricity storage device and an electrolyte or an additive, the amorphous portion crosslinked structure is formed by reaction between the separator for an electricity storage device and a chemical substance contained in the electrolyte or the additive.

2. A separator for an electricity storage device (excluding a foamed separator) containing a polyolefin, wherein an amorphous portion of the polyolefin has a crosslinked amorphous portion crosslinked structure in which crosslinking points are localized only in the amorphous portion, and in an electricity storage device containing the separator for an electricity storage device and an electrolyte or an additive, the amorphous portion crosslinked structure is formed by reaction between the separator for an electricity storage device and a chemical substance contained in the electrolyte or the additive.

3. The power storage device separator according to claim 1 , wherein the amorphous portion of the polyolefin is selectively crosslinked.

4. The separator for an electricity storage device has the following formula (2): R E’mix =E' / E' 0 (2) In the formula, E' is a storage modulus measured at 160°C to 300°C when the electricity storage device separator has an amorphous crosslinked structure, and E' 0 is the storage modulus of an electricity storage device separator that does not have an amorphous crosslinked structure, measured at 160°C to 300°C.} The mixed storage modulus ratio (R E’mix 4. The electricity storage device separator according to claim 1, wherein the ratio of the cross-linked structure to the total cross-linked structure is 1.5 to 20 times, and the electricity storage device separator not having an amorphous portion cross-linked structure is a polyolefin microporous membrane having a gelation degree of about 0%.

5. The separator for an electricity storage device has the following formula (4): R E’’mix =E'' / E'' 0 (4) In the formula, E″ is a loss modulus measured at 160° C. to 300° C. when the electricity storage device separator has an amorphous crosslinked structure, and E'' 0 is the loss modulus of an electricity storage device separator that does not have an amorphous crosslinked structure, measured at 160°C to 300°C.} The mixed loss modulus ratio (R E’’mix 5. The electricity storage device separator according to claim 1 , wherein the ratio of the cross-linked structure to the total cross-linked structure is 1.5 to 20 times, and the electricity storage device separator not having an amorphous portion cross-linked structure is a polyolefin microporous membrane having a gelation degree of about 0%.

6. The separator for use in an electricity storage device according to any one of claims 1 to 5, wherein the polyolefin is polyethylene.

7. 7. The power storage device separator according to claim 1, wherein the polyolefin is a functional group-modified polyolefin or a polyolefin copolymerized with a monomer having a functional group.

8. The separator for an electricity storage device according to any one of claims 1 to 7, wherein the amorphous part crosslinked structure is formed by a reaction mediated by any one of a covalent bond, a hydrogen bond, or a coordinate bond.

9. The reaction via the covalent bond is represented by the following reactions (I) to (IV): (I) Condensation reactions of multiple identical functional groups; (II) Reactions between multiple different functional groups; (III) a chain condensation reaction between a functional group and the electrolyte; and (IV) reaction of a functional group with the additive; The separator for use in an electric storage device according to claim 8 , which is at least one selected from the group consisting of:

10. The reaction via a coordinate bond is the following reaction (V): (V) A reaction in which a plurality of identical functional groups crosslink through coordinate bonds with metal ions; The separator for an electricity storage device according to claim 8 ,

11. The separator for an electricity storage device according to claim 9 , wherein the reaction mediated by the covalent bond is reaction (I) and / or (II), and reaction (I) and / or (II) is catalytically promoted by a chemical substance inside the electricity storage device.

12. The electricity storage device separator according to claim 9 , wherein the reaction via a covalent bond is reaction (I), and reaction (I) is a condensation reaction of a plurality of silanol groups.

13. The reaction via the covalent bond is the reaction (IV), and the reaction (IV) is a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction between a compound Rx constituting the electricity storage device separator and a compound Ry constituting the additive, the compound Rx having a functional group x, and the compound Ry having a linking reaction unit y 1 The separator for an electricity storage device according to claim 9 ,

14. the reaction via a covalent bond is reaction (IV), and reaction (IV) is a nucleophilic substitution reaction; The functional group x of the compound Rx is -OH, -NH 2 At least one selected from the group consisting of -NH-, -COOH and -SH; The linking reaction unit y of the compound Ry 1 But, CH 3 SO 2 -, CF 3 SO 2 -, ArSO 2 -, CH 3 SO 3 -, CF 3 SO 3 -, ArSO 3 - and the following formula (y 1 −1) to (y 1 -6): 【Chemistry 1】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 2】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 3】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 4】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 5】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 6】 {In the formula, X is a hydrogen atom or a monovalent substituent.} The separator for an electricity storage device according to claim 13 , wherein the at least two are selected from the group consisting of monovalent groups represented by the following formula:

15. the reaction via a covalent bond is reaction (IV), and reaction (IV) is a nucleophilic substitution reaction; The compound Ry is the ligation reaction unit y 1 In addition to the chain unit y 2 and The chain unit y 2 is expressed by the following formula (y 2 −1) to (y 2 -6): 【Chemistry 7】 {wherein m is an integer from 0 to 20, and n is an integer from 1 to 20.} 【Chemistry 8】 {wherein n is an integer from 1 to 20.} 【Chemistry 9】 {wherein n is an integer from 1 to 20.} 【Chemistry 10】 {wherein n is an integer from 1 to 20.} 【Chemistry 11】 {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} 【Chemistry 12】 {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} The separator for an electricity storage device according to claim 13 or 14, wherein the bivalent group is at least one selected from the group consisting of divalent groups represented by the following formula:

16. the reaction via a covalent bond is reaction (IV), and reaction (IV) is a nucleophilic addition reaction; The functional group x of the compound Rx is -OH, -NH 2 At least one selected from the group consisting of -NH-, -COOH and -SH; The linking reaction unit y of the compound Ry 1 is expressed by the following formula (Ay 1 -1) to (Ay 1 -6): 【Chemistry 13】 【Chemistry 14】 【Chemistry 15】 【Chemistry 16】 In the formula, R is a hydrogen atom or a monovalent organic group. 【Chemistry 17】 【Chemistry 18】 The separator for use in an electricity storage device according to claim 13 , wherein the organic group is at least one selected from the group consisting of groups represented by the following formula:

17. the reaction via a covalent bond is reaction (IV), and reaction (IV) is a ring-opening reaction; The functional group x of the compound Rx is -OH, -NH 2 At least one selected from the group consisting of -NH-, -COOH and -SH; The linking reaction unit y of the compound Ry 1 is expressed by the following formula (ROy 1 -1): 【Chemistry 19】 In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent. The separator for use in an electricity storage device according to claim 13 , wherein the R 1 -R 2 groups are each independently selected from the group consisting of 1 to 2.

18. In the reaction (V), the metal ion is Zn 2+ , Mn 2+ , Co 3+ , Ni 2+ and Li + The separator for an electricity storage device according to claim 10 , which is at least one selected from the group consisting of:

19. The following steps: (1) a sheet forming step of extruding a mixture of polyolefin and a plasticizer, cooling and solidifying the mixture, and forming the mixture into a sheet; (2) a stretching step of stretching the sheet in at least one axial direction to obtain a stretched product; (3) a porous body forming step of extracting the plasticizer from the stretched product in the presence of an extraction solvent and making the stretched product porous to form a porous body; and (4) a heat treatment step of subjecting the porous body to a heat treatment; A separator for an electricity storage device, which is produced by a production method comprising the steps of: The polyolefin has one or more functional groups, and A method for manufacturing an electricity storage device using a separator for an electricity storage device, characterized in that after being stored in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a cross-linked structure.

20. A polyolefin-containing separator for an electricity storage device, comprising a wet biaxially stretched polyolefin microporous membrane, The polyolefin has one or more functional groups, and A method for manufacturing an electricity storage device using a separator for an electricity storage device, characterized in that after being stored in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a cross-linked structure.

21. A separator for an electricity storage device (excluding foam separators) containing polyolefin, The polyolefin has one or more functional groups, and A method for manufacturing an electricity storage device using a separator for an electricity storage device, characterized in that after being stored in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a cross-linked structure.

Citation Information

Patent Citations

  • Porous film, and separator for cell and cell using the same

    JP1997216964A

  • Ion conductor for lithium secondary battery, and lithium secondary battery using this ion conductor

    JP1998261435A

  • Porous membrane, battery separator comprising porous membrane, and manufacture thereof

    JP1999144700A

  • Porous film, battery separator comprising porous film, and its production

    JP1999172036A

  • Production of microporous resin film

    JP2000319441A